Molecular mechanisms of the VBNC state induced by polyhexamethylene guanidine in biofilm-associated Staphylococcus aureus - Shuhao Zeng; Tianzheng Ma; Yuxuan Lu; Menghua Duan; Yimo Liu; Na Lü; Kangning Zhao; Haoran Cui; Shaochuang Zhang; Runhua Ji; Ziyi Zhang; Hui Yang; et al. (Food Microbiology, 2027)

Identification and evaluation of potential probiotics with favorable fermentation and storage characteristics for fermented brown milk beverages - Meng Zhang; Hui Qiao; Pengfei Cui; Kaiyang Liu; Lai-Yu Kwok; Wenyi Zhang (Food Microbiology, 2026)

Bone marrow mesenchymal stem cell exosomes in osteonecrosis: pathological mechanisms and therapeutic strategies - Ma Yuele; Wang Yan; Cui Hongwei; Zhang Hui; Li Guang; Li Yanxin; Ma Tiancheng; Ma Jianxiong (Molecular Biology Reports, 2026)

Ectopic expression of the sesuvium portulacastrum L. SpHDZ39 and SpHDZ41 enhances growth and cadmium tolerance in Arabidopsis - Tongjing Cui; Yuxin Li; Xiaoyou Wu; Fengyan Fang; Yaoxiu Li; Yingyi Yu; Guomei Zhang; Zhuangzhuang Nan; Yonghan Wen; Shugang Hui (Functional & Integrative Genomics, 2026)

Genome-wide characterization of WRKYs and identification of SpWRKY40 and SpWRKY51 as transcription activators in Sesuvium portulacastrum - Yaoxiu Li; Fengyan Fang; Xiaoyou Wu; Tongjing Cui; Yingyi Yu; Zhaozhen Xiang; Guomei Zhang; Zhuangzhuang Nan; Shugang Hui (Functional & Integrative Genomics, 2026)

Monsoon intensification as a driver of enhanced biogenic silica burial during the Bajocian cooling event in the western Yarlung Zangbo Suture Zone, southern Tibet - Xiaohui Cui; Xin Li; Jonathan C. Aitchison; Mei-Fu Zhou; Yichun Zhang; Jun Chen; Xuejin Wu; Xiru Li; Jiaqi Song; Hui Luo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Long-term nitrogen deposition weakens the CH4 sink capacity, but enhances the CO2 and N2O source potential of the alpine grassland soil - Hang Shi; Xiaoqing Cui; Shikui Dong; Zilong Liu; Ran Zhang; Ke Zhang; Xueqi Li; Yuhao Zhang; Hui Zuo; Fengcai He; Xianqi Zhou; Mingjie Ran; et al. (Agriculture, Ecosystems & Environment, 2026)

Enterococcus in herbal fermentation: a genus-specific perspective on enzymatic capability, biotransformation outcomes and safety - Jiafei Tang; Shuo Zhang; Gui Xu; Mengxiao Cui; Xiutong Ge; Hui Gao; Fan Zhang (Archives of Microbiology, 2026)

Dual-site magnetic microporous organic networks enabling high-performance capture and quantification of per- and polyfluoroalkyl substances - Chun-Ying Xu; Qing-Zhi Hou; Xiang-Sheng Xue; Zhan-Hui Qiu; Yuan-Yuan Cui; Cheng-Xiong Yang (Water Research, 2026)

Arginine downstream metabolites spermidine and putrescine, but not spermine, contribute to PCV2 replication - Jianwei Zhou; Haoyu Sun; Beiyi Zhou; Xiaoyuan Lan; Weiyin Xu; Peng Hui; Qianqian Zhang; Xue Dong; Wei Gao; Yonghui Qiu; Dedong Wang; Yongqiu Cui; et al. (Veterinary Microbiology, 2026)

Post-cyclic simple shear responses of soft clay under equivalent sequential seismic loading with various degrees of reconsolidation - Long-Ji Zhang; Zhen-Dong Cui; Meng-Hui Huang (Soil Dynamics and Earthquake Engineering, 2026)

From longitudinal dispersal to vertical sequestration: Hydraulic regulation drives divergent antibiotic fates via suspended particulate matter dynamics across natural and engineered waterways - Yang Cui; Hui Xie; Jianwei Dong; Meiqi Shang; Shiya Gu; Wu Wen (Journal of Hydrology, 2026)

Electronic modulation in 3D tubular sulfur-doped carbon nitride via thiophene-skeleton bridging: Promoting n→π* transition for wastewater remediation coupled with H2 evolution - Xuan Guan; Jiachun Wu; Hui Fan; Huixia Li; Liang Zhang; Haijiao Xie; Yanjuan Cui (Journal of Environmental Chemical Engineering, 2026)

Goethite reshapes photodegradation pathways and site selectivity of environmentally relevant polystyrene microplastics - Jinyu Chen; Wen Yu; Jixing Liu; Xiaoxia Chen; Yulun Gu; Jingwen Cui; Jiayi Wei; Haibo Chen; Hui Li (Journal of Environmental Chemical Engineering, 2026)

High internal phase Pickering emulsions as edible inks for 3D food printing: impact of Hofmeister series ions on their functionality - Chao Wu; Tianlong Xiao; Shishuai Cui; Yichen Zheng; Bo Jiao; Xiaojie Ma; Hui Hu; Jinjin Zhu; Qiang Wang; David Julian McClements; Aimin Shi (Food Chemistry, 2026)

Comparison of plant and microbial protein particles fabricated by heat-induced aggregation or enzymatic cross-linking: structure, physicochemical properties, and stability - Xinyu Zhang; Xiaojie Ma; Tianlong Xiao; Shishuai Cui; Hui Hu; David Julian McClements; Qiang Wang; Aimin Shi (Food Chemistry, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

Controllable and fast carbon nanostructure growth in molten-salt CO₂ electrolysis enabled by a high-entropy perovskite anode - Chenbo Gao; Chao Gao; Buming Chen; Hanwen Cui; Hui Huang (Chemical Engineering Journal, 2026)

Microbial mechanisms of sulfamethoxazole biodegradation at bio-anode elucidated by integrated metagenomics and stable-isotope probing - Hongli Lu; Hui Lin; Da Kang; Donglin Wang; Qiaojuan Wang; Jie Mao; Dan Cui; Yaohui Bai; Jiuhui Qu; Yongzhen Peng (Chemical Engineering Journal, 2026)

Deciphering sulfidation chemistry of nanoscale zerovalent iron for enhanced reductive defluorination of trace PFOA: Precursor-driven core-shell engineering and electron transfer - Mi Li; Jing Wang; Qisheng Lu; Cui Hu; Yuping Qiu; Xinyi Zeng; Genhe He; Wei Hui; Kai He; Jun Zhong; Xiaoyu Xiao; Xubiao Luo (Chemical Engineering Journal, 2026)

Simultaneous removal of phenol and ammonium from coking wastewater by fungi-bacteria mixed culture under static magnetic field - Xu-Zhen Liu; You-Wei Cui; Hui-Juan Yan; Ze-You Lu; Ya-Nan Mi; Tong Ren (Bioresource Technology, 2026)

Evaluating the Influence of Nitrogen Fertilizer Types on Nutrient Leaching in Moderately Saline-Alkali Rice Paddies - Qifeng Yang; Xinyi Wang; Hui Zhu; Hu Cui; Shengnan Hou (Water, Air, & Soil Pollution, 2026)

Enantioselective trophic transfer of chiral psychiatric pharmaceuticals in an effluent−impacted river food web - Weimin Wang; Tian Xie; Guozhu Chen; Lei Li; Hui Zhang; Tao Sun; Baoshan Cui; Zongwei Cai (Water Research, 2026)

Linking botany and mineral exploration: Alhagi sparsifolia as a potential indicator for Ni-Cu sulfide deposits - Meng-Meng Cui; Ben-Xun Su; Shan-Ke Liu; Hui-Li Yan; Wen-Jun Li; Bing-Yu Gao; Jing Wang; Zhen-Yan He; Shu-Kuan Wu; Ye-Tao Tang (Journal of Asian Earth Sciences, 2026)

The multi-level synergy of a moderate H2 and lactate mixed environment enhances TCE dechlorination by indigenous microbial community - Weiwei Ouyang; Yao Huang; Cui Li; Wenyi Huang; Hui Liu (International Biodeterioration & Biodegradation, 2026)

From outcrossing to reproductive assurance: Seasonal plasticity in the breeding system of bi-seasonal flowering Tamarix ramosissima Ledeb. (Tamaricaceae) - Meng-Yuan Zhang; Jia-Hui Leng; Hong-Ju Cui; Jun-Xue Shi; Yuan-yuan Li; Xiang Shi (Flora, 2026)

Impact of urban functional zoning on carbon emission from electricity consumption: a multi-source data integration approach on Xuzhou China - Jiawei Xiang; Jia Wang; Hui Yang; Liu Cui; Yina Qiao; Run Cai; Shuzhen Wu; Yuan Zhang (Energy and Buildings, 2026)

NMR DensTrack (Part II): Quantification of adsorbed methane density and volume in different confined coal spaces - Hui Wang; Zhang Xueqing; Yidong Cai; Shike Li; Xiao Cui; Yunlong Ma; Rudy Swennen; Chu Zhang (Chemical Engineering Journal, 2026)

Enhancing selective esterification of conjugated linoleic acid isomers by immobilized Candida rugosa lipase via hydrophobic acyl acceptors - Meijun Du; Jun Jin; Cong Sun; Abdelaziz Elbarbary; Wei Wei; Hui Zhang; Qingzhe Jin; Xingguo Wang; Zhe Cui (Bioresource Technology, 2026)

Contrasting mineral–microbial pathways drive phosphorus bioavailability under moderate pH shifts in agricultural soils - Meng Qi; Rongyang Cui; Anqiang Chen; Xinmei Zhao; Ming Ni; Zhiwu Li; Hui Yan; Chi Wang; Bin Fu (Applied Soil Ecology, 2026)

The histone methyltransferase SETD2 regulates the PI3K/AKT signaling pathway to affect the in vitro fertilization of yak oocytes - Qiyong Zuo; Hui Zhang; Donglan Zhong; Tianhao Li; Yuejiao Liao; Yangyang Pan; Sijiu Yu; Yan Cui (Animal Reproduction Science, 2026)

Estimating high spatiotemporal resolution XCO2 from multi-source satellite using a spatiotemporal stacking model - Yina Qiao; Hui Yang; Liu Cui; Yuan Zhang; Gefei Feng; Qingzhou Lv; Huaiwei Fan; Yuejing Yao; Xinfeng Huang (Advances in Space Research, 2026)

LSTM-Driven Digital Groundwater Monitoring and Environmental Risk Assessment for Coal Mining Areas - Feng-zuo Guo; Guo-hui Wang; Zhen-yang Liu; Yu-min Jiang; Hai-cui Wang (Applied Geophysics, 2026)

Optimal Conditions for Enhanced Water Purification and Carbon Sequestration in Constructed Wetlands - Xinyi Wang; Luyao Yang; Hu Cui; Shengnan Hou; Hui Zhu (Journal of Soil Science and Plant Nutrition, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Opposite effects of garlic essential oil and protein fertilizer on aerial hyphae outbreak of wine-cap mushrooms: Mechanisms involving the redox imbalance and membrane destabilization - Xinran Yin; HongLin An; Xiaoya Zhao; Hui Cui; Lei Yu; Yanan Sun; Weina Li; Demei Meng; Yang Nie; Xia Gao; Dan Zhu; Fansheng Cheng (Postharvest Biology and Technology, 2026)

A polarization-based monocular depth estimation model for three-dimensional measurement of underwater targets - Qin Wei; Xia Hua; Xiaopeng Cui; Wei Guo; Xinhua Xu; Shaohua Qiu; Hui Tian; Jie Wang (Ocean Engineering, 2026)

CO2-absorbed diethanolamine in cement: Strength development regulated by in-situ carbonation - Hui Liu; Chao Yuan; Jianfeng Wang; Tongsheng Zhang; Binjie Zhou; Penghao Xin; Suping Cui (Journal of Environmental Chemical Engineering, 2026)

Enhancing sustainable oil palm management through plantation age mapping and yield estimation - Qiang Zhao; Le Yu; Wenchao Qi; Tao Liu; Hui Wu; Zhenrong Du; Yaoping Cui; Kasturi Kanniah (Journal of Cleaner Production, 2026)

Effect of alkanolamine molecular structure on the complexation activation of steel slag: A mechanistic study - Jianfeng Wang; Jiaqi Zhao; Hao Wan; Binjie Zhou; Hui Liu; Jihui Zhao; Suping Cui (Journal of Cleaner Production, 2026)

Starch coating on low-sodium salt via fluidized bed granulation: Sensory improvement and health benefits - Xinyu Song; Xing Li; Xiangyu Liu; Zhaoxiang Ma; Zhi Fan; Zhiqiang Cui; Hui Xiong; Zhixin Li; Ying Zhou; Mingchun Lv; Yuan Li (Carbohydrate Polymers, 2026)

Correction: MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2026)

Manure compost and gypsum amendments revitalize soil quality via aggregation and pore structure in the Yellow River Delta - Xiaoyang Duan; Xiaoying Jin; Qi Miao; Zhanlonggang Yu; Hui Rong; Xiao Wang; Zhenling Cui; Hu Zhou; Zhangliu Du (Journal of Soils and Sediments, 2026)

Exploring Changes in Fish Communities from the Perspective of Functional Diversity: A Case Study on Interrelationship Between Fishes and Microbial Communities in Yellow Sea, Northern China - Chunhui Feng; Jiyuan Wan; Bin Zhou; Hui Guo; Jiyao Yang; Wangxinze Shu; Zhengang Liu; Xumeng Cui; Tianjing Shi; Jun Wang; Xiaochong Shi; Yong Jiang (Journal of Ocean University of China, 2026)

New Understanding of the Progressive Failure Process of the 2018 Baige Landslide, Tibet, China: A Role of Intermittent Rainfall - Ling Zhu; Shenghua Cui; Zicheng Lu; Xiangjun Pei; Han Cao; Shuang He; Hui Wang; Hailong Yang (Journal of Earth Science, 2026)

Sensory impairment, epigenetic ageing, and later-life functional decline and mortality in older adults - Xiangwei Li; Chongyu Ding; Yaqian Xu; Hui Zhang; Jun Du; Xian Cui (GeroScience, 2026)

Multiscale and Fractal Descriptions of Particle Morphology of Calcareous Sand with Different Grain Sizes - Hui Liang; Dingmao Peng; Yutang Chen; Shizhuang Chen; Changjie Shao; Jiafeng Gu; Zhongxiong Cui (Journal of Marine Science and Engineering, 2026)
The mechanical behavior of calcareous sand differs significantly from that of conventional quartz sands, leading to challenges in offshore geotechnical engineering applications. This distinctive response is closely associated with the complex three-dimensional morphology of calcareous sand particles. However, existing characterization methods are often limited to specific morphological scales and cannot fully describe the multiscale complexity of particle shape. To address this issue, this study performs a comparative morphological analysis of calcareous sand (CS) and Fujian quartz sand (FS) across three particle-size ranges by integrating X-ray micro-computed tomography with spherical harmonic (SH) analysis. Individual particles are reconstructed using SH representation, and a multiscale morphology characterization framework is developed by decomposing particle morphology into three distinct scale levels: large-scale form represented by sphericity, medium-scale angular features represented by roundness, and small-scale surface texture represented by roughness. The results demonstrate that CS and FS exhibit distinct morphological characteristics across different scales, while particle-size effects remain less pronounced within the investigated range. Furthermore, the SH amplitude spectra reveal statistically self-similar characteristics of particle surfaces, allowing the fractal dimension to be correlated with multiscale morphological descriptors. The proposed framework provides a quantitative description of complex particle morphology across multiple scales and may facilitate further investigations of particle-scale mechanical behavior in granular materials.

Experimental study on compression characteristics and resistivity response of sulfate-containing site soil - Hui Liu; Qiang Sun; Jishi Geng; Jingjing Nan; Kai Cui; Yuxin Zhang (Acta Geophysica, 2026)

Unraveling the Exosome-Derived ceRNA Network of Cartilage Injury in Kashin-Beck Disease Chondrocytes - Chaowei Wang; Lulu Bai; Liangyu Cui; Pengyan Jiao; Zhouyun Chen; Yang Liu; Yirong Qin; Hui Wang; Lian Liu; Qi Jing; Yuyang Ma; Yuequan Yuan; et al. (Biological Trace Element Research, 2026)

Pre-adaptive resistance to acequinocyl associated with cross-resistance to bifenazate in field populations of Tetranychus urticae across China - Jin-Cui Chen; Hui-Juan Li; Ming Xue; Bo Peng; Jing-Jing Kang; Qi-Yu Chen; Shuai-Yu Wang; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2026)

Experimental study on co-pyrolysis characteristics of oily sludge and waste textiles targeted at the fuel substitution for cement kilns - Chi Jia; Xiaoyan Li; Hui Li; Qing Huang; Liqiu Feng; Mengmeng Cui (Process Safety and Environmental Protection, 2026)

Scale effects on motion responses and flow characteristics in moonpool of a semi-submersible platform based on CFD - Ying Li; Tenghui Cui; Dongxu Xie; Hui Yang; Huailiang Li (Ocean Engineering, 2026)

Numerical analysis on the boil-off rate of liquefied natural gas in MARK III FLEX tank systems of LNG carriers - Miaomiao Wang; Hui Han; Changan Xu; Yaohua Xiao; Xiaohan Jing; Jiachen Cui; Yuxing Li; Jianlu Zhu (International Journal of Refrigeration, 2026)

Effect of pile foundation on seismic response of adjacent subway station buried in sand site by centrifuge shaking table tests - Long-Ji Zhang; Zhen-Dong Cui; Meng-Hui Huang; Jia-Sen Yan; Su-Yang Wang (Engineering Structures, 2026)

How ScCO2-induced chemical structure transformation affects the wettability of coal - Ling Jiang; Chu Zhang; Hui Wang; Yidong Cai; Siyuan Song; Yu Zhang; Xiao Cui; Shike Li; Xueqing Zhang (Chemical Engineering Journal, 2026)

Self-amplifying ROS nanoplatform with dual responsiveness for tumor-targeted photodynamic therapy - Yiping Zhou; Zhongjian Wang; Ning Tong; Hui Cao; Zhenya Sun; Lixue Chen; Ning Wang; Lei Li; Ran Cui; Lu Liu; Han Bao (Journal of Pharmaceutical Investigation, 2026)

Study on the therapeutic effects of the primary active ingredients in cinnamon oil for constipation-predominant irritable bowel syndrome and their regulatory effects on the 5-HT signaling pathway and gut microbiota - Wanqiu Peng; Tingting Xu; Zhenhai Zhang; Li Cui; Chao Gu; Xiaomeng Sun; Hui Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Divergent assembly mechanisms and network stability of microeukaryotes between water column and sediment in a marginal sea - Feilong Liu; Xiaoli Zhang; Kaiyue Lian; Yi Li; Can Wang; Chuyu Zhang; Honglei Zhang; Bo Wang; Qian Liu; Hui He; Cui Guo; Andrew McMinn; et al. (Marine Pollution Bulletin, 2026)

Mercury methylation network on microplastics: Multipathway coupling, regulatory mechanisms, and environmental risks - Yuhang He; Mengxin Xu; Zhenhua Zhao; Xinying Hui; Yining Liu; Xiaoyu Cui; Yindong Tong (Water Research, 2026)

Light-driven community assembly and functional performance of aeration-free filamentous algae–partial nitrification/anammox granule - Cui-Zhong Chen; Hui-Min Fu; Tong-Xu Li; Xiao-Yu Gao; Qing Hu; Peng Yan; Jin-Song Guo; Xiao-Wei Xu; You-Peng Chen (Water Research, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

Epimedium polysaccharide alleviates adenine-induced oligoasthenozoospermia in mice by inhibiting ferroptosis and inflammation through TLR4/NF-κB and SLC7A11/GPX4 axis - Kun-Yang Tang; Wang Ai; Xiao-Cui Jiang; Min Xiao; Yan-Yan Zhou; Xiao-Ming Yu; Shu-Hui Chen; Jing-Ling Zhao (Reproductive Biology, 2026)

New alkaloids from the marine-derived fungus Penicillium sp. SWMU-WZ04-5 and their cytotoxic activity - Sijing Liu; Jinghao Cui; Mengyu Zhang; Ting Chen; Fengjian Lan; Xiujuan Fu; Siwei Chen; Dan Zhang; Ying Zhang; Hui Lei (Phytochemistry Letters, 2026)

Early-life and lifelong exposure to environmentally relevant enrofloxacin reorganizes a proteobacteria-centered gut-lipid-resistome steady state in marine medaka - Ziyi Guo; Zheyu Wang; Yaxin Liu; Meiru Wang; Hongyue Ma; Ziwei Wang; Siyuan Zhang; Yidan Chang; Hezi Ge; Chenglu Li; Hui Yang; Hui Miao; et al. (Journal of Hazardous Materials, 2026)

Mechanistic insights into the role of nitrogen configurations driving efficient activation of low-dose ferrate (VI) for sulfonamides elimination - Zhikang Deng; Jinyao Zhu; Xi Chen; Minghui Xiang; Hui Lin; Junwei Ma; Song Cui; Zulin Zhang (Journal of Environmental Chemical Engineering, 2026)

Coupling electrostatic and static magnetic fields during drying: A strategy to enhance drying characteristic, functional properties and microstructural modification fresh-cut purple yam - Hui Yang; Dahui Liu; Yu Qiao; Fang Zhu; Yiwei Cui; Lihui Zhang (Food Chemistry, 2026)

Phosphorylation-modified fava bean 11S protein fibril-based oleogels: A novel strategy to enhance network flexibility and alter rheological and textural properties - Zhihao Xu; Xuemei Lin; Wenzhong Zhao; Xiaoqi Ding; Xianglin Sun; Yuting Ding; Hui Chen; Pengbo Cui (Food Hydrocolloids, 2026)

The effects and physiological phenotypic changes in Escherichia coli O157:H7 induced into VBNC state by hydrogen peroxide silver ion treatment in biofilms - Kangning Zhao; Runhua Ji; Can Li; Xiaoya Wang; Menghua Duan; Shuhao Zeng; Shaochuang Zhang; Tianzhen Ma; Haoran Cui; Yajing Kong; Hui Yang; Ziyi Zhang; et al. (Food Microbiology, 2026)

Cultivar-type driven fertilization strategies to decouple the trade-off between wheat yield and grain protein in dryland systems - Xuemei Zhang; Junfeng Xu; Zikang Guo; Cui Huang; Xiaohan Li; Zhiyuan Gao; Jiachuang Fang; Chenrui Liu; Yulan Ding; Jian Hou; Zilin Wang; Yang Feng; et al. (Field Crops Research, 2026)

Traffic noise, air pollution, and greenness in relation to age-related macular degeneration: Evidence from a cross-national cohort study - Xuehao Cui; Jingwen Hui; Quanhong Han (Environmental Pollution, 2026)

Design of millimeter-sized porous carbon spheres guided by hydrodynamic principles - Xiao-Dong Shi; Cheng-Tong Wang; Wen-Cui Li; Hong-Lei Wang; An-Hui Lu (Chemical Engineering Journal, 2026)

The Role of Nitrogen Fertilizers in Controlling NH3 and GHG Emissions in Saline-Alkali Paddy Fields: Microbial Community Insights - Xinyi Wang; Hui Zhu; Shengnan Hou; Cui Hu (Journal of Soil Science and Plant Nutrition, 2026)

Study on deformation characteristics and failure modes of high-altitude ancient landslide in Lijie North Hill, Zhouqu, China - Xiao-hui Yang; Fei Hu; Xiao-jie Liu; Yuan-wen Jiang; Xin Jiang; Xue-liang Cui; Kun-quan Chen; Shi-kui Zhu (Bulletin of Engineering Geology and the Environment, 2026)

Transcriptional regulator Rv2250c affects isoniazid resistance by down-regulating the expression of efflux pump Rv3728 in Mycobacterium tuberculosis - Hui Wang; Yingying Cui; Guanghui Dang; Jiajun Zhang; Yiyi Tang; Tingting Feng; Xinxin Zang; Ningning Song; Siguo Liu (Archives of Microbiology, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Application of antimicrobial peptides expressed by Tetraselmis subcordiformis (Wille) butcher improves the health of turbot via oral administration - Yunyun Liu; Xinhui Jie; Jiaqing Wang; Subing Han; Ping Liu; Chunxiao Meng; Hui Wang; Zhengquan Gao; Yulin Cui (World Journal of Microbiology and Biotechnology, 2026)

Systemic inflammation moderate the association between urinary polycyclic aromatic hydrocarbon metabolites and hypertensive adults - Jing Liu; Ziwei Zhou; Xu Zhu; Gongchang Guan; Feipeng Li; Qianwei Cui; Rutai Hui; Junkui Wang; Runmiao Wu; Zhao Zhao; Hui Pang; Ling Zhu (Toxicology Letters, 2026)

Corrigendum to “Internalization of Escherichia coli O157:H7 in fresh-cut vegetables under different conditions and the role of surface appendages in internalization” [Food Res. Int. 227 (2026) 118275] - Shuai Huang; Cui Wang; Hui Shi (Food Research International, 2026)

Enhanced Therapeutic Effects of Extracellular Vesicles Targeting MiR-137 Contribute to Functional Recovery by Attenuating Neuronal Injury After Ischemic Stroke - Hui-Xin Zhang; Li-Qing Tao; Yi-Hang Chen; Tian-Yi Jiang; Zhi-Yuan Ye; Wen She; Chang-Ying Chen; Ya-Li Han; Cui Qi; Chong Shen; Jun Gao (Neuroscience Bulletin, 2026)

Oncology Education Reform in China: Aligning Clinical Training with the New Medical Science Mandate - Yiyi Hui; He Cui; Zhihao Zhang; Bin Yan (Journal of Cancer Education, 2026)

Machine learning-based disentanglement of meteorological and anthropogenic drivers of ozone pollution in the Chengdu-Chongqing urban agglomeration - Xiaoyong Liu; Hongrui Li; Wei Wei; Hui Gao; Kai Zhang; Xiangchao Cui (Environmental Monitoring and Assessment, 2026)

From discovery to mechanism: novel anti-ulcerative colitis meroterpenoids act through the PI3K/IκB-α/MAPK pathway - Jiafan Yang; Chuxing Liang; Binglin Chang; Jingxin He; Qian Zeng; Jinqin Wei; Yan Zhou; Hui Cui (Marine Life Science & Technology, 2026)

(P)ppGpp synthase Rsh promotes persister cells formation by regulating sulfur metabolism mediated by sulfate reductase CysI in Brucella abortus - Xiaofang Liu; Chenyang Cui; Pingping Wang; Hui Wang; Yunyi Zhai; Yuanhao Yang; Jialu Chen; Wei Liu; Zheng Dong; Dong Zhou; Yaping Jin; Aihua Wang (Veterinary Microbiology, 2026)

A new dameselloid trilobite from the Changhia Formation (Cambrian, Drumian) in central Shandong, North China - Guang-Ying Ren; Jin-Liang Yuan; Yi-Fan Wang; Bai-Zheng An; Kai Chen; Xiao-Hui Cui; Jian Gao; Nan Li (Palaeoworld, 2026)

Early Cretaceous radiolarian assemblages in mélange of Yarlung-Tsangpo suture zone in the Saga area, southern Xizang - Zhi-Hao He; Xin Li; Ya-Lin Li; Atsushi Matsuoka; Hui Luo; Xiao-Hui Cui; Jian-Bo Cheng (Palaeoworld, 2026)

Synergistic utilization of circulating fluidized bed fly ash and pulverized fly ash in low-carbon solid waste cementitious materials: Performance and hydration mechanism - Jianmin Li; Liwen Guo; Ye Li; Jiayong Zhang; Cheng Zhang; Hui Pan; Xiao Cui; Xiaofan Zhao (Journal of Environmental Chemical Engineering, 2026)

Enhanced performance of Cr-doped CeMn/Hβ catalysts for complete oxidation of chlorobenzene-containing volatile organic compounds and their mechanistic insights - Kang Zhou; Shun Wang; Yunrui Zhao; Wei Zhao; Hui Shi; Zhaoyang Fei; Xian Chen; Jihai Tang; Mifen Cui; Xu Qiao; Ming Xia (Journal of Environmental Chemical Engineering, 2026)

Integrated enrichment-photocatalytic platform based on exfoliated vermiculite: Construction of CdS/PTI S-scheme heterojunction and mechanism of photocorrosion resistance - Ning Zhang; Qingyang Xu; Ke Cui; Yi Wang; Xue Yang; Hui Zhao; Huaizhi Shao; Dongping Tao; Yu Zhang; Qian Zhang (Journal of Environmental Chemical Engineering, 2026)

Insight into the oxygen-dependent biotransformation pathways of mercury by a facultative bacterium Raoultella terrigena TGRB3 - Hui Li; Qunyao Cui; Yuping Xiang; PengYu Feng; Lanqing Wang; Jiwu Wang; Yongmin Wang; Dingyong Wang; Hong Shen (Journal of Environmental Sciences, 2026)

Heavier sediment pollution by per- and polyfluoroalkyl substances (PFASs) in tropical coasts compared to temperate regions: An overlooked hotspot - Hui Xie; Shiya Gu; Yang Cui; Jianwei Dong; Hongbing Wang; Guowei Fu (Journal of Environmental Sciences, 2026)

Sensing performance and mechanism of flexible sensing-enabled CB-CNT/PDMS geosynthetics for soil deformation monitoring - Xinzhuang Cui; Shibao Lu; Xu Zhang; Qing Jin; Shiyuan Sun; Hui Li (Geotextiles and Geomembranes, 2026)

Effects of glycosylation, phenolic-binding, pH, and ionic strength on the structural, emulsifying, and antioxidant properties of millet bran gliadin: Mechanism insights - Hui Wang; Ling Dang; Xinling Song; Jie Liu; Yajun Zheng; Na Cui; Zhihui Wei; Zihao Zhang; Yixuan Zhang (Food Chemistry, 2026)

C3a-C3ar1 axis mediates macrophage M1 polarization to drive silicosis inflammation and fibrosis - Xuesong Zhang; Hui Fan; Jianxia Cao; Xiaoge Cui; Yan Xie; Jingwen Fan; Xueyang Zhang; Wu Yao; Changfu Hao (Environmental Pollution, 2026)

Contrast antibiotic activities from muddy and sandy coasts and their potential controls - Shuo Zhang; Lijia Qu; Xintong Li; Ye Lu; Yang Cui; Jianwei Dong; Hui Xie (Environmental Pollution, 2026)

Activating the hydration activity of steel slag via the chelation of BES-Na for waste resource utilization - Lei Chang; Jianfeng Wang; Suping Cui; Hui Liu; Binjie Zhou; Qiang Cui (Chemical Engineering Journal, 2026)

Functionalizing 3D DNA crystals by replacing non-framework strands - Xinyu Feng; Li Xu; Yunhan Zhang; Shuheng Wei; Dongbao Yao; Huichao Chen; Yueye Wang; Yujing Wu; Hui Hou; Xiao Cui; Qian Meng; Yue Gu; et al. (Chemical Engineering Journal, 2026)

Organic material application holds great potential for alleviating soil nitrogen loss from cropland caused by shallow groundwater table fluctuations but increases N2O emissions - Rongyang Cui; Meng Qi; Bin Fu; Xinmei Zhao; Hui Yan; Zhiwu Li; Wanli Hu; Anqiang Chen (Water Research, 2026)

TANK-binding Kinase 1 regulates the intracellular survival of Brucella - Zhiqiang Li; Shuli Wang; Ruirui Li; Yanyan Cui; Jinliang Zhang; Junfang Hao; Huijun Zhang; Qifeng Li; Hui Zhang (Veterinary Microbiology, 2026)

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Unexpected chemicals in the coastal menu: widespread occurrence of legacy and emerging per- and polyfluoroalkyl substances (PFASs) raise concerns for human exposure - Suyu Lei; Meiqi Shang; Jianwei Dong; Wu Wen; Hui Xie; Yang Cui; Chengjun Wu (Journal of Environmental Sciences, 2026)

Temporal dynamics of insecticide-resistance mutations in the diamondback moth Plutella xylostella (Linnaeus, 1758) within northern immigration regions - Ya-Jun Qu; Jin-Cui Chen; Hui-Juan Li; Shuai-Yu Wang; Xue-Yan Zhang; Ary A. Hoffmann; Sen-Shan Wang; Shu-Jun Wei (Journal of Asia-Pacific Entomology, 2026)

Characterization of EGCG-concentration responsive gel of tamarind seed polysaccharide - Huaitian Cui; Zhiqiang Xiong; Lianzhong Ai; Fan Xie; Zibo Song; Hui Zhang (Food Research International, 2026)

Internalization of Escherichia coli O157:H7 in fresh-cut vegetables under different conditions and the role of surface appendages in internalization - Shuai Huang; Cui Wang; Hui Shi (Food Research International, 2026)

Influence of protease type and concentration on protein digestibility, physicochemical and textural properties of extruded high-moisture meat analogues - Grace Cui Fang Ng; Caleb Ong; Alicia Hui Ping Theng; Dayna Shu Min Ong; Chaoyu Dong; Hui Yu Sim; Xin Yi Hua; Felicia Siew Kay Ng; Jie Hong Chiang (Food Hydrocolloids, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

Three-Dimensional Modeling of Surrounding Rock in Tunnels and Identification of Potentially Unstable Blocks - Hongliang Liu; Zhongxu Zhou; Xin Gao; Lanyu Cui; Binggang Yan; Shicheng Wang; Hui Cai; Changyuan Chen (Geotechnical and Geological Engineering, 2026)

Electrical Structure of the Narusongduo Cryptoexplosive Breccia Deposit, Gangdese Belt, Tibet: Insights from Integrated MT/AMT Data Inversion and Implications for Mineral Exploration - Hui-cui Xin; Zhi-min Xu; Guang Li; Cong Zhou; Zhi-ning Jia (Applied Geophysics, 2026)

Investigation of Emission Characteristics of Controlled-source Electromagnetic Transmitters Employing a TSC–GCSC Tunable Impedance Matching Circuit - Quan-hui Guo; Guo-qiang Xue; Qi-hui Zhen; Jun-jie Xue; Fen-xuan Zhang; Jiang-wei Cui; Yan-bo Wang; Wen-bo Guo (Applied Geophysics, 2026)

Three-dimensional transient electromagnetic virtual wave field propagation characteristics of electrical sources - Jun-jie Xue; Fen-xuan Zhang; Quan-hui Guo; Jiang-wei Cui (Applied Geophysics, 2026)

Dynamic succession patterns, nitrogen cycling potential, and multi-scale assembly mechanisms of cross-habitat bacterial communities in lakes driven by seasonal frozen conditions - Jingyi Wang; Shengnan Zhao; Xiaohong Shi; Biao Sun; Zhiqiang Tian; Hui Zhang; Yunxi Zhao; Zhimou Cui; Jinda Zhang (Marine Pollution Bulletin, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Recycling steel slag waste into Portland cement: Hydration, microstructure and properties in the presence of ligand activators - Lei Chang; Yajing Fang; Suping Cui; Jianfeng Wang; Hui Liu; Binjie Zhou; Qiang Cui (Process Safety and Environmental Protection, 2026)

Elucidating the role of Alg14 in governing cell wall architecture and biological functions in the entomopathogenic fungus Beauveria bassiana - Long-Bin Zhang; Yu-Tian Li; Zhi-Hao Yang; Zhou Cui; Yi Guan; Guang-Hui Liu (Pesticide Biochemistry and Physiology, 2026)

How do hydrodynamic conditions and land use drive antibiotic fate in estuarine and bay ecosystems? - Yang Cui; Meiqi Shang; Hui Xie; Jianwei Dong (Journal of Environmental Sciences, 2026)

Impact of CO2 dilution on biogas combustion in a double-layer porous media burner: From ignition to stable combustion - Ning Wang; Hui Wang; Xiangyu Wang; Xiang Liu; Jiashuo Cui (Fuel, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Effects of Lactiplantibacillus plantarum fermentation on sensory and in vitro antioxidant properties of ginger - Hui Dou; Guangqiang Wang; Le Chu; Guangpeng Liu; Fatao He; Xin Song; Yongjun Xia; Nan Zhao; Shumao Cui; Zibo Song; Zhiqiang Xiong; Lianzhong Ai (Food Bioscience, 2026)

The protective effects of dipeptides-WY and YW on blueberry anthocyanins and their interaction mechanism analysis - Yuxi Lang; Xu Si; Hui Tan; Jinlong Tian; Zhihuan Zang; Huijun Cui; Dongdong Zhao; Ying He; Liang Wang; Bin Li (Food Bioscience, 2026)

A novel partitioned anaerobic membrane bioreactor integrated with ferromagnetic biochar for complex pesticide wastewater: Mass balance, membrane fouling mitigation, energy footprint, and life cycle assessment - Yifan Wang; Liwen Jiang; Dongxue Hu; Shiming Cui; Bei Jiang; Hui Ge; Shuya Zhuang; Jitao Yan; Zihan Wang; Pengcheng Zhang; Zhaobo Chen (Environmental Research, 2026)

Evaluation of micro(nano)plastics and additives in human blood: A pilot study with university students - Ming-Hui Huang; Chen-Chou Wu; Wen-Jia Cui; Lei Mai; Eddy Y. Zeng (Environmental Pollution, 2026)

Response patterns and mechanisms of weathering crusts on feldspathic metagreywacke under solar radiation at the Helankou petroglyphs site - Kai Cui; Tangxian Jiao; Guopeng Wu; Hui Yang; Junning Ma; Qiangqiang Pei (Bulletin of Engineering Geology and the Environment, 2026)

Identification and transcriptomic analysis of a new pathogen, Photobacterium damselae SCXP, associated with sea cucumber skin ulceration syndrome - Linwei Yang; Shuming Liu; Hui Lv; Haiyun Wei; Tong Wu; Bilian Lou; Jingsong Yang; Qingmei Huang; Yuxin Shi; Tongxin Lin; Zhengwei Cui; Xinhua Chen; et al. (Aquaculture, 2026)

Pareto fronts guided co-evolutionary algorithm for constrained multi-objective optimization - Hui Wang; Jinyu Xu; Jiayao Qian; Xinyu Zhou; Wei Li; Zhihua Cui; Jia Zhao (Swarm and Evolutionary Computation, 2026)

Cytochalasins from the marine-derived fungus Acremonium implicatum DFFSCS001 and their anti-inflammatory activities - Yu-Qian Tang; Chu-Xing Liang; Hui Cui; Xiao Liang; Shu-Hua Qi (Phytochemistry, 2026)

Preparation of iron oxide/montmorillonite catalyst and its green remediation performance of pyrene-contaminated soil - Yun-rui Zhao; Kang Zhou; Xiao-xiao Qi; Hui Shi; Jihai Tang; Mifen Cui; Xu Qiao; Ming Xia (Journal of Water Process Engineering, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Occurrence, distribution, and risk assessment of antibiotics in post-harvest and drained ponds of Sheyang River estuary in Jiangsu Province: Implications for sustainable aquaculture management - Wenqian Shan; Shiya Gu; Wangrong Cui; Xinyun Feng; Xin Song; Jianwei Dong; Hui Xie; Da Li (Journal of Contaminant Hydrology, 2026)

Enhanced flavor and modified structure of Maillard reaction products from chicken liver protein hydrolysate through composite fermentation pretreatment - Wenchao Chen; Wei Cui; Ping Li; Zhaoming Wang; Xingguang Chen; Hui Zhou; Baocai Xu (Food Chemistry, 2026)

Eye Opening Primes Synaptic Maturation by Enhancing AMPA Receptor-Mediated Transmission and Spinogenesis in the Developing Superior Colliculus - Jiafeng Wang; Yijing Yan; Xue Wang; Xin Cui; Yu Gu; Hui Shen; Xuefeng Shi (Molecular Neurobiology, 2026)

Tree trunk disease mapping using hyperspectral LiDAR - Peilun Hu; Yuwei Chen; Wei Li; Huaguo Huang; Samuli Junttila; Shuanghui He; Yanan Zhao; Xiaoqi Cui; Mohammad Imangholiloo; Changhui Jiang; Jianxin Jia; Haibin Sun; et al. (Computers and Electronics in Agriculture, 2025)

Susceptibility of five thrips pests to spinetoram and the frequency of G275E target-site mutation in a major vegetable production region of China - Hong-Ping Tian; Hong-Xia Tian; Jin-Cui Chen; Fu-Jun Li; Jing-Jing Kang; Hui-Juan Li; Jin-Peng Gao; Guo-Cai Lu; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2025)

Formation and in-situ identification of unique microplastic-rock blends under anthropogenic thermal conditions - Changfu Yang; Qiujie Huang; Yuheng You; Zhihang Yuan; Hui Wang; Jicui Cui; Dong Ma; Long Kong; Nanwen Zhu; Ziyang Lou (Water Research, 2025)

Enhancing the hydration activity of steel slag-Portland cement composite by BES sodium activator - Lei Chang; Suping Cui; Jianfeng Wang; Hui Liu; Binjie Zhou (Sustainable Chemistry and Pharmacy, 2025)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

Ecological sustainability of rebuilding stocks under multiple stressors and evaluation framework for restoration of population - Xu Sun; Zhaopeng Zhang; Cui Liang; Yuanchao Wang; Wenzhuo Cao; Lei Zheng; Hui Zhang; Weiwei Xian (Journal of Environmental Management, 2025)

Pilot scale study on treatment of landfill leachate by short-cut nitrification and denitrification coupling sulfur autotrophic denitrification: Performance, cost and carbon emissions - Jinghai Luo; Huiyu Liang; Liao Meng; Haibo Cui; Qiujin Deng; Hui Lu; Ben Chen (Journal of Environmental Chemical Engineering, 2025)

Photoaging behavior and neurotoxic effects of shower gel-derived microbeads in Caenorhabditis elegans - Yulun Gu; Yajing Han; Xin Li; Ping Ding; Chaoyi Du; Xiaoxia Chen; Yongqi Jiang; Jinyu Chen; Jingwen Cui; Haibo Chen; Hui Li (Journal of Environmental Management, 2025)

From human-driven eutrophication to effective management: Controlling brown tides in the coastal waters of Qinhuangdao, China - Lei Cui; Yue-Lei Dong; Jian-Le Zhang; Wei-Dong Yang; Song-Hui Lu; Lin-Jian Ou (Harmful Algae, 2025)

The effect of enzymatic hydrolysis assisted glycosylation on the allergenicity and digestive characteristics of whey protein isolate - Hui Zhang; Xiuxiu Zhang; Shuming Liu; Xin Tan; Jiayi Zhao; Donghai Hao; Liqin Cui; Xiaodong Li; Lu Liu; Muhammad Muneeb (Food Research International, 2025)

Novel fava bean 11S nanofiber gels for sustained ergothioneine delivery: a calcium ion and κ-carrageenan approach - Hui Chen; Mengyuan Zhou; Zhihao Xu; Xiting Dong; Xiaoqi Ding; Xuxia Zhou; Pengbo Cui (Food Hydrocolloids, 2025)

Structuring camellia seed-derived oleosomes for the fabrication of meat analogs using transglutaminase: Structural, functional, and rheological properties - Shahzad Farooq; Muhammad Ijaz Ahmad; Shijie Zheng; Usman Ali; Yipeng Zhang; Jiawen Xue; Yang Li; Cui Shixiu; Hui Zhang (Food Hydrocolloids, 2025)

School backpacks and commuter bags: A non-negligible source of human exposure to phthalate monoesters - Wen-Jia Cui; Ming-Hui Huang; Chen-Chou Wu; Lian-Jun Bao; Eddy Y. Zeng (Environmental Pollution, 2025)

Characteristics and health risk assessment of groundwater Metal(loid)s in different geomorphological units of the coal-fired power cluster in the “Ji”-Shaped bend of the Yellow River - Hui Tong; Ruizhong Gao; Yinlong Wang; Jiaqi Zhao; Peixin Cui; Xiaowei Jiang (Environmental Pollution, 2025)

A nitric oxide-based Ca2+ nanomodulator induces sustained calcium overload via respiratory inhibition for enhanced cancer immunotherapy - Zongtao Zhou; Hui Hu; Yi Li; Lijiao Yang; Suisui He; Jun Wang; Jinjin Chen; Zhijun Zhang; Jie Li; Xinping Liu; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2025)

Study on the Threshold of Sodium Sulfate Saline Soil Based on the Synergistic Response of Resistivity and Thermal Conductivity - Hui Liu; Qiang Sun; Kai Cui; Qiang Li; Jingjing Nan; Shibo Li; YuXin Zhang (Water, Air, & Soil Pollution, 2025)

Dynamics of convergent plate margins: Progress and challenge - Zhong-Hai Li; Yang Wang; Qihua Cui; Hui-Ying Fu; Fengyuan Cui; Pengpeng Huangfu (Science China Earth Sciences, 2025)

The NLRP3 inflammasome: a pivotal orchestrator of multisystem diseases—from molecular mechanisms to therapeutic innovation - Shu-yan Xiao; Ya-hui Lv; Yin-min Ji; Yi Dong; Mei-cen Liu; Tao Li; Xiao-ran Cui; Yi Hu (Molecular Biology Reports, 2025)

RNA methylation and breast cancer: insights into m6A, m7G and m5C - Yuhan Dai; Shuhan Zhao; Huilin Chen; Wenxin Yu; Ziyi Fu; Yangyang Cui; Hui Xie (Molecular Biology Reports, 2025)

Natural and anthropogenic drivers of salinization in the Bohai Rim: Mechanisms and remediation through pine needle amendments - Baijun Shang; Feng Wang; Tong Li; Zhihong Xu; Bernhard Wehr; Yash P. Dang; Rongxiao Che; Lizhen Cui; Jintong Liu; Hui Gao; Shuhui Yu; Tonggang Fu (Journal of Soils and Sediments, 2025)

Spatiotemporal transcriptomic dynamics of rice defense under bacterial blight challenge - Xiuli Liu; Hui Deng; Weijun Cui; Rumeng Xu; Zaozao Zhu; Shaomin Wang; Jie Zhou; Hongjia Liu; Haiyan He; Chengqi Yan; Wona Ding; Yin Lu; et al. (Journal of Plant Diseases and Protection, 2025)

Smeat-seq transcriptomic profiling unveils key regulatory events during Maternal-to-Zygotic transition and supports High-Efficiency culture system development in Tibetan sheep embryos - Tianhao Li; Yangyang Pan; Tian Zhao; Jinglei Wang; Hui Zhang; Xiaoqing Yang; Xiaolin Ye; Donglan Zhong; Xin Ma; Sijiu Yu; Yan Cui (Functional & Integrative Genomics, 2025)

Aberrant dynamics of the default mode network activity in patients with obsessive-compulsive disorder - Yan Cui; Hui Lei; Shuang Yu; Ke Chen; Yang Xia; Ruxiang Xu; Daqing Guo; Xiongzhao Zhu; Dezhong Yao (Cognitive Neurodynamics, 2025)

Structural study of a deep-seated rock landslide using seismic noise - Hui Wang; Shenghua Cui; Xiangjun Pei; Tao Jiang; Qingwen Yang; Runqiu Huang (Bulletin of Engineering Geology and the Environment, 2025)

Marine antifouling coating based on modified polyurethane and halloweite nanotubes for slow-release of chlorgentianol alcohol - Yuan Feng; Chi Zhang; Yong-Yin Cui; Miao-Qing Sheng; Xian-Dong Zhang; Hui-Jing Li; Yan-Chao Wu (Applied Clay Science, 2025)

Inversion of the Deep Structure of the Northern Margin of the Ordos Block Using Teleseismic Receiver Functions and Gravity Data - Feng-Zhi Cui; Fan Zhang; Juan Li; Dong-Yang Pei; Yi-Hang Bai; Lei Wang; Hui Wang (Applied Geophysics, 2025)

H2 as a potential redox homeostasis modulator: a review of mechanisms targeting key elements of cardiovascular pathogenesis-related pathways - Wanrong Wang; Fusen Yang; Biao Geng; Hui Song; Yue Gao; Jingfei Shi; Gang Wang; Chao Cui (Molecular and Cellular Biochemistry, 2025)

Spatial distribution pattern of heavy metals in sediments of seasonal ice-covered lakes - Shengnan Zhao; Hui Zhang; Jinda Zhang; Xiaohong Shi; Biao Sun; Zhimou Cui; Jingyi Wang (Marine Pollution Bulletin, 2025)

Activation of the cGAS-STING pathway in monocytes exacerbates pulmonary fibrosis induced by paraquat poisoning - Yangyang Sun; Zheming Yuan; Weidong Li; Xueyang Lin; Chen Yang; Yufeng Yang; Hui Miao; Shengran Wang; Ziqi Cui; Zhenghao Bao; Simin Lang; Weiqiang Sun; et al. (Toxicology and Applied Pharmacology, 2025)

Quaternary ammonium cationic surfactants target Vfm quorum sensing to suppress the virulence of rice pathogen Dickeya oryzae - Longhui Luo; Lan-Tu Xiong; Xingnan Zhang; Di Zhu; Lian-Hui Zhang; Zi-Ning Cui (Pesticide Biochemistry and Physiology, 2025)

Host-microbe synergy in pesticide resilience: Rhodococcus-driven fitness compensation in chlorpyrifos-stressed Binodoxys communis - Hui Xue; Xiaojin Qiao; Lingen Du; Li Wang; Kaixin Zhang; Dongyang Li; Jichao Ji; Jinjie Cui; Xiangzhen Zhu; Junyu Luo; Xueke Gao (Pesticide Biochemistry and Physiology, 2025)

A nonlocal strain gradient higher-order beam theory and its application to wave propagation in radially graded nanotubes - Wei-Li Ma; Peng-Yu Wang; Hui-Ru Cui; Xian-Fang Li (Ocean Engineering, 2025)

Dynamic model for charging tight gas reservoirs: A case study from the Xujiahe Formation in the Sichuan Basin, China - Haoming Shao; Min Wang; Junfeng Cui; Hui Jin; Dianshi Xiao; Yidong Jia; Wei Li; Xiaodie Guan; Chen Zhao; Tao Zhang (Marine and Petroleum Geology, 2025)

Decoding soil resilience: The role of eco-corona in alleviating toxicity for aged tire wear particles and benzalkonium chloride (C12) co-exposure - Bei Jiang; Yunhong Pu; Shengnan Shi; Zhaobo Chen; Dongxue Hu; Hui Ge; Shiming Cui; Yifan Wang; Pengcheng Zhang; Zihan Wang (Journal of Hazardous Materials, 2025)

Slightly acidic electrolyzed water induces Staphylococcus aureus to enter the VBNC state: differences between planktonic and biofilm states bacteria - Ziyi Zhang; Jingqi Feng; Haoran Cui; Yu Wu; Yihong Wang; Weipeng Xu; Yiming Lu; Menghua Duan; Hui Yang; Shuai Cheng; Xiaolin Cai; Chunling Zhang; et al. (Food Research International, 2025)

Ionic liquid functionalized magnetic microporous organic network for efficient extraction of phenoxyacetic acid herbicides from vegetables - Xu-Hui Li; Yan-Hong Li; Yuan-Yuan Cui; Cheng-Xiong Yang (Food Chemistry, 2025)

Gelation of tamarind seed polysaccharide induced by tea polyphenols: Screening, gelling kinetics, and properties - Si Xie; Huaitian Cui; Fan Xie; Zibo Song; Hui Zhang; Lianzhong Ai (Food Hydrocolloids, 2025)

Greenhouse gas emissions in a microbial fuel cell-assisted composting system: Microbial insights into bacterial structures and genetic functions - Hu Cui; Sheng-Nan Hou; Xin-Yi Wang; Hui Zhu (Environmental Research, 2025)

Residential greenness modifies the association between long-term exposure to PM2.5 components and allergic diseases in schoolchildren: A large-scale study in Southern China - Hua-Lian Chen; Chao-Yang Chen; Cui-Lan Tang; Wei-Guo Liao; Hui-Xian Zeng; Wen-Jie Meng; Qi-Zhen Wu; Guang-Hui Dong; Jian Chen; Xiao-Wen Zeng (Environmental Pollution, 2025)

Individual girder-level evaluation of assembled multigirder bridges using load transverse distribution identified from moving load test data - Hao-Yan Cui; Hai-Tao Sun; Xu Zheng; Ming-Guang Wei; Ting-Hua Yi; Dong-Hui Yang (Engineering Structures, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

Surface engineering of MOF-derived hierarchical porous carbons for ultrasensitive detection and discrimination of anticancer and antibacterial drugs - Junlin He; Jun Wang; Zhonghui Luo; Jiaheng Zhang; Yongrong Deng; Bo Liu; Hui Zhao; Suisui He; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2025)

Multifunctional TIB molecular bridge for buried interface optimization in high-efficiency p-i-n perovskite solar cells - Yingying Peng; Hu Li; Zhipeng Wu; Hanwen Cui; Jun Guo; Chao Gao; Yapeng He; Hui Huang (Chemical Engineering Journal, 2025)

Optimizing irrigation and nitrogen management enhances apple yield and quality through improving soil quality on the Loess Plateau - Shuaihong Chen; Shaowu Zhang; Hui Li; Tiantian Hu; Guangzhao Sun; Xiaolu Cui; Zhijie Chang; Jie Liu (Plant and Soil, 2025)

Pinocembrin Alleviates Postoperative Cognitive Dysfunction in Aged Mice by Modulating miR-384-5p/FZD1 Axis to Activate the Wnt/β-Catenin Pathway - Jie Li; Xue-li Peng; Xin-yu Cheng; Jun-jun Yang; Cui Cui; Jian-hui Liu (Molecular Neurobiology, 2025)

CAR19-T/NK cell and circular aptamer–drug conjugate (ApDC) combination treatment increases immunotherapy efficacy - Ling-Qi Kong; Su-Yun Chen; Xu Cui; Ya-Hui Hu; Lian Wang; Jia-Yao Zhu; Lan-Xuan Guan; Bing-Kun Wang; Li-Ting Yang; Kai-Ming Chen; Chao-Ming Zhou (Molecular and Cellular Biochemistry, 2025)

Effects of temperature stress on liver histology, oxidative stress, and transcriptome in fat greenling (Hexagrammos otakii) - Zheng Zhang; Yanchao Wei; Hui Liu; Shuai Wang; Yanyan Shi; Dandan Cui; Yan Chen; Xuejie Li; Wei Wang (Aquaculture International, 2025)

Extreme Phenotypic Variation Confounds Acanthocephalan Systematics: A Case Study of Longicollum pagrosomi and Pomphorhynchus zhoushanensis (Acanthocephala: Echinorhynchida) - Cui‐Hong Zhao; Hui‐Xia Chen; Matthew Thomas Wayland; Rui‐Jia Yang; Xiao‐Hong Gu; Liang Li (Zoologica Scripta, 2025)
The phylum Acanthocephala is a ubiquitous group of zooparasites, with major socio‐economic importance. The true diversity of the Acanthocephala is obscured by the phenomena of cryptic speciation and a large degree of intraspecific variation. In this study we describe an example of extreme phenotypic variation in neck morphology. The pomphorhynchid acanthocephalans, Longicollum pagrosomi and Pomphorhynchus zhoushanensis were originally differentiated on the basis of differences in neck morphology; P. zhoushanensis possesses a neck bulb whereas this structure is absent in L. pagrosomi . However, ASAP and phylogenetic analyses of the ITS, 12S, cox 1 and cox 2 sequence data, together with comparative mitogenomics, revealed that the two taxa are in fact conspecific. Therefore, the presence or absence of a neck bulb represents extreme phenotypic variation, and this character is not reliable for distinguishing the genera Pomphorhynchus and Longicollum. In the absence of other characters to discriminate the two genera, Longicollum is relegated to a junior synonym of Pomphorhynchus . A new combination Pomphorhynchus pagrosomi (Yamaguti, 1935) comb. nov. is proposed for L. pagrosomi Yamaguti, 1935 and P. zhoushanensis Li, Chen, Amin & Yang, 2017 is relegated to a junior synonym of P. pagrosomi .

Activation of YAP1 and TAZ enhances the in vitro maturation of yak oocytes and influences subsequent embryonic development - Donglan Zhong; Yangyang Pan; Meng Wang; Hui Zhang; Ruihua Xu; Qiyong Zuo; Tianhao Li; Sijiu Yu; Yan Cui (Theriogenology, 2025)

Effect of initial static shear stress on cyclic properties of soft clay in constant volume simple shear tests - Meng-Hui Huang; Zhen-Dong Cui; Long-Ji Zhang (Soil Dynamics and Earthquake Engineering, 2025)

Energy-based evaluation of cyclic shear behaviors of soft clay under mainshock-aftershock sequence loading - Long-Ji Zhang; Zhen-Dong Cui; Meng-Hui Huang (Soil Dynamics and Earthquake Engineering, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Critical review on magnetic biological effects of microorganisms in the field of wastewater treatment: Theory and application - Hui-Juan Yan; You-Wei Cui; Hui-Kai Liang; Zhen-Ying Li (Journal of Environmental Chemical Engineering, 2025)

Z-scheme Ag2MoO4/g-C3N4 heterojunction photocatalysts for sulfadiazine degradation under sunlight irradiation - Huanbo Ni; Xuejun Zou; Yuying Dong; Jun Ke; Hui Ge; Yubo Cui (Journal of Environmental Chemical Engineering, 2025)

Integrating HS-SPME-GCMS with chemometrics for identifying adulterated flaxseed oils and tracing origins of additives - Yan-Jin Wen; Long-He Wang; Meng Zhai; Hui Ma; Hua-Peng Cui; Lu Han; Guo-Bi Chai; Yi Lv; Qing-Xia Zheng; Yong-Jie Yu; Yuan-bin She (Food Control, 2025)

Effect of biological nitrification inhibitors from sorghum, rice, and signal grass on N2O emission: A multilevel meta-analysis - Hongze Ma; Xiaoyu Jia; Xiaoshan Zhang; Ke Cui; Xi Zhang; Xinyu Wang; Hui Zhang; Zhouping Shangguan; Lucas Pecci Canisares; Yangquanwei Zhong; Jianghua Wu; Weiming Yan (Environmental Research, 2025)

Phosphorus-doped tungsten-based materials on carbon cloth for direct electrochemical lead ion sensing - Jie Gao; Jun Yin; Haijun Liu; Yuanyuan Cui; Xiangyue Wang; Jiaoyan Li; Jingwen Zhang; Dong He; Hui Suo; Lan Ding; Chun Zhao (Environmental Research, 2025)

Ultra-stable and efficient all-solid-state sodium-air hybrid batteries with catalyst via Ag-Co3O4 electrochemical interface reconstruction - Yunhong Luo; Xiaoyi Zhan; Fenwei Cui; Yong Han; Nian Zhang; Hui Zhang; Yimin Li; Zhi Liu (Chemical Engineering Journal, 2025)

Bridging papermaking and zinc-ion batteries: Engineering partial Janus separators from hierarchically porous softwood fibers - Rukun Cui; Siyu Pan; Yonghao Ni; Zhibin He; Hui Mao; Jing Shen (Chemical Engineering Journal, 2025)

Hydrogen bonding-reinforced zwitterionic hydrogel electrolytes for wide-temperature tolerant zinc-ion capacitors - Shuzhen Cui; Leichao Meng; Wenxing Miao; Xuan Xie; Hui Peng; Guofu Ma (Chemical Engineering Journal, 2025)

Sonodynamic nanocatalytic therapy: ultrasound-activated PVA/nanocellulose-tannic acid hydrogels for mechano-antimicrobial plaque disruption and enamel-safe chromophore degradation - Jin Huang; Kai You; Xiangmei Liu; Yi Wang; Congyang Mao; Chaofeng Wang; Yufeng Zheng; Shengli Zhu; Zhaoyang Li; Hui Jiang; Zhenduo Cui; Jie Shen; et al. (Chemical Engineering Journal, 2025)

Accelerating process recovery through “0 + 1 > 1” phenomenon: Enhanced anammox bacteria growth in mixed inactive-active sludge systems - Jing Yang; Danyang Zhu; Hui Gong; Rongrong Cui; Xiaoguang Liu; Yayi Wang; Jacek Makinia; Li Xie; Xiaohu Dai (Bioresource Technology, 2025)

The role of N6-methyladenosine (m6A) modification in plants - Cui-Xian Qin; Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Miao Wang; You-Qiang Pan; Li Zhou; Bao-Qing Zhang; Jian-Hui Zhou; Dong-Liang Huang (Theoretical and Applied Genetics, 2025)

Molecular evolution of chloroplast genome in Triumfetta (Grewioideae, Malvaceae) - Rushan Yan; Yujie Zeng; Chengyu Chen; Abdur Rab; Hui Li; Raza Ullah; Madiha Islam; Ying Cui; Mengyang Liu; Xiaoxuan Tian (Planta, 2025)

Recovery of disintegrated halophilic aerobic granular sludge through ferric ion addition: Dual roles in filamentous fungal inhibition and microbial adhesion enhancement - Hui-Kai Liang; You-Wei Cui; Hui-Juan Yan; Zhen-Ying Li (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

A salt-tolerant tetracycline degrading fungal strain of Candida palmioleophila: Characterization and degradation pathway - Zhen-Ying Li; You-Wei Cui; Hui-Juan Yan; Hui-Kai Liang; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Blue carbon sediments as effective sinks for microplastics: A global meta-analysis - Xue Qi; Hui Zhang; Xiaoxuan Di; Junhong Bai; Baoshan Cui (Journal of Hazardous Materials, 2025)

Understanding policy-volition interactions in urban ecological governance: A simulation framework based on SD-ABM coupling - Wen Zhang; Jianglong Cui; Xiaomin Li; Xiaolin Hou; Yafei Li; Maria Stella Burgio; Hui Li; Qing Yang; Gengyuan Liu (Journal of Cleaner Production, 2025)

Genomic and phylogenetic analyses of the domoic acid biosynthesis genes in the benthic diatom Nitzschia navis-varingica (Bacillariophyceae) - Zongmei Cui; Hui Wang; Po Teen Lim; Suh Nih Tan; Yuichi Kotaki; Chui Pin Leaw; Nansheng Chen (Harmful Algae, 2025)

Effect of modification technologies on characteristics and bioactivities of the pectic polysaccharide from cantaloupe peels - Mingze Gong; Ruizhan Chen; Hui Sun; Helong Bai; Cui Yang; Dongxue Li; Wenjing Wu; Yongtang Wang (Food Bioscience, 2025)

Vacancy-directed Pt-N3Cl1 coordination engineering via flash joule heating for chemoselective nitroarene hydrogenation - Libo Wang; Dejian Xu; Zhiyuan Wang; Fengliang Cao; Shihao Cui; Hui Wang; Honghao Liu; Xiaojie Tan; Qingshan Zhao; Mingbo Wu (Chemical Engineering Journal, 2025)

Built-in electric field-driven interfacial charge transfer for boosted pseudocapacitance - Yue Zhao; Shuyao Zhang; Jiamin Zhu; Liguo Jin; Ling Li; Wence Xu; Yanqin Liang; Hui Jiang; Zhaoyang Li; Zhonghui Gao; Li Xiao; Zhenduo Cui; et al. (Chemical Engineering Journal, 2025)

Advance and perspective of carbon-based aerogels and their composites - Yanfeng Fu; Hui Ye; Ke Yuan; Qinxin Wang; Longhui Ge; Sheng Cui (Chemical Engineering Journal, 2025)

Response of Rice Plants to Hydrogen Sulfide Stress: Physiological Mechanisms and Recovery Thresholds - Xiaoling Jin; Liang-Jun Hu; Bin Wang; Shengnan Hou; Hu Cui; Hui Zhu; Xinyi Wang (Journal of Soil Science and Plant Nutrition, 2025)

Transcriptome Analysis Reveals Impact of S-Methyl Thioacetate on Tomato Seedling Growth - Donghui Zheng; Fangfang Ren; Rongjun Yin; Linmei Li; Hanwen Cui; Hui Shen; Xiaochun Chen; Nan Gao (Journal of Plant Growth Regulation, 2025)

Advanced performance and operational strategies of partitioned anaerobic membrane bioreactor combined with ferromagnetic biochar for pesticide wastewater treatment at low-temperature and insufficient hydraulic load - Yifan Wang; Liwen Jiang; Dongxue Hu; Bei Jiang; Hui Ge; Shiming Cui; Shuya Zhuang; Jitao Yan; Zihan Wang; Pengcheng Zhang; Zhibo Liang; Zhaobo Chen (Water Research, 2025)

Immunotoxic effect and mechanisms of Fusarium mycotoxins on human immune cells: A focus on T cells and macrophages - Jing Yang; Xiaohong Wang; Qiannan Zhang; Hongyang Cui; Lijuan You; Zhisen Zhuang; Yaru Tian; Xiaomin Han; Miaoying Shi; Li Bai; Xudong Jia; Hui Yang (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Soil mineral-associated and particulate organic matter differentially alleviate the toxic effects of 2,4,6-tribromophenol on arylsulfatase - Yu YANG; Ziquan WANG; Hui HUANG; Yan LI; Jiaqi CUI; Ping LÜ; Haixia TIAN; Mallavarapu MEGHARAJ; Wenxiang HE (Pedosphere, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

High enrichment of heterotrophic nitrification-aerobic denitrification bacterial community achieved by shortening anoxic feeding duration in the sequencing batch reactor: feeding mode effect and mechanism - Yuan Sui; You-Wei Cui; Hui-Juan Yan; Rui-Chun Yang (Journal of Environmental Management, 2025)

Alkalinity role in recovery of disintegrated halophilic aerobic granular sludge treating high salt-alkali wastewater: Insights into community ecology of fungi and bacteria - Ya-Nan Mi; You-Wei Cui; Dong-Xu Zhou; Hui-Juan Yan; Liu-Xu Jiang; Ming-Teng Li (Chemical Engineering Journal, 2025)

A quantitative study on the influencing pathways of aerosol acidity: the non-neglectable role of non-ideality - Hanze Cui; Yaxing Du; Hui Zhang; Mingqi Deng; Qi Zhang; Weihua Chen; Shuzhen Su; Xihua Li; Sayantan Sarkar; Liming Yang; Xuemei Wang; Shiguo Jia (Atmospheric Environment, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Mechanisms of reactive intermediates formation in saline-alkali agricultural waters - Xinyi Wang; Jiyang Liu; Songyang Li; Yaqin Miao; Yuting Shen; Hu Cui; Shengnan Hou; Hui Zhu (Water Research, 2025)

SETD2 regulates oocytes in vitro maturation through histone methylation and maternal mRNA degradation in yak - Hui Zhang; Yangyang Pan; Meng Wang; Jinglei Wang; Jiaxin Huang; Rui Ma; Shanshan Yang; Wenbin Ma; Sijiu Yu; Yan Cui (Theriogenology, 2025)

Isolation and identification of triterpenoid saponins with antiproliferative and hemolytic activities from Camellia oleifera Abel seeds - Jian-Fa Zong; Xiao-Xiang Guo; Kang-Kang Zou; Chuan-Jian Cui; Zi-Hui Hu; Ru-Yan Hou (Phytochemistry, 2025)

Control of gummy stem blight in pumpkin using Streptomyces nigrescens NEAU-L66: Insights into its biocontrol mechanisms - Jinzhao Gu; Yanfang Luo; Lijie Cui; Hui Bing; Xinyu Kong; Lanxin Meng; Ruofan Wang; Zihan Ma; Wensheng Xiang; Junwei Zhao; Xiangjing Wang (Physiological and Molecular Plant Pathology, 2025)

Tetracycline degradation by a mixed culture of halotolerant fungi-bacteria under static magnetic field: Mechanism and antibiotic resistance genes transfer - Zhen-Ying Li; You-Wei Cui; Hui-Kai Liang; Hui-Juan Yan; Rui-Chun Yang (Journal of Hazardous Materials, 2025)

Upper Jurassic radiolarian assemblages and chert geochemistry of the Shiquanhe ophiolite, NW Tibet: Implications for the evolution of the Meso–Tethyan ocean - Xiaohui Cui; Yichun Zhang; Xin Li; Jonathan C. Aitchison; Mei-Fu Zhou; Qinggao Zeng; Guangying Ren; Hui Luo (Gondwana Research, 2025)

Assessing decarbonization pathways by weighing carbon mitigation efficiency and risks in China's energy system - Qi Cui; Xinyu Zhang; Lingyu Yang; Tariq Ali; Yong Yang; Hui Wang; Ruoyu Liu (Environmental Impact Assessment Review, 2025)

Enrichment of active hydrogen on nanoporous Ru/Co2P for enhanced electrocatalytic nitrate to ammonia - Yunduo Huang; Yanqin Liang; Hui Jiang; Shuilin Wu; Zhaoyang Li; Zhonghui Gao; Zhenduo Cui; Shengli Zhu; Wence Xu (Chemical Engineering Journal, 2025)

Interfacial polarization-induced microwave pyrolysis for expeditious municipal solid waste transformation and valorization - Wenliang Wang; Hui Miao; Hangzhuo Li; Yangyi Cui; Yishuai Fu; Xinping Li; Lei Chen; Bailiang Xue; Chao Duan; Weikun Jiang (Chemical Engineering Journal, 2025)

Collagen targeting BMSCs-derived extracellular vesicles coupled with decellularized tendon scaffold for anterior cruciate ligament reconstruction - Jie Wang; Jing Cui; Liang-Ju Ning; Yan-Jing Zhang; Fei Xing; Lei-Lei Zhao; Hui-Min Liu; Xuan Li; Min Zhu; Jing-Cong Luo; Zhou Xiang; Ting-Wu Qin (Chemical Engineering Journal, 2025)

Deformation Rate Effects in the Circumferential Strain-Controlled Post-Peak Loading Tests - Guanghao Cui; Fanzhen Meng; Wei Wang; Pengyuan Liu; Yuantao Wen; Zhufeng Yue; Hui Zhou; Liming Zhang (Rock Mechanics and Rock Engineering, 2025)

A Prediction Model of Effective High-Pressure Water Jet Auxiliary Groove Spacing for Hard-Rock Pick Cutting - Jingjing Lu; Jiancheng Xiao; Hui Zhou; Chuanqing Zhang; Xiao Ma; Congcong Hou; Jian Cui (Rock Mechanics and Rock Engineering, 2025)

Research on the preparation of antimicrobial material based on thermoplastic polyurethane and drug release control - Chengzhi Cui; Jinxing Cao; Jianlan Liu; Hui Zhang (Drug Delivery and Translational Research, 2025)

Effects of calcium-sensitive receptors on chondrogenic differentiation of rat bone marrow mesenchymal stem cells - Siyu Li; Xiang Jia; Yongping Cui; Kainan Liu; Tianjie Xu; Jiaxin Fan; Hui Zhang; Yueyuan Li; Qian Wang (Cell and Tissue Banking, 2025)

Co-occurrence and risk emission potential of antibiotics, antibiotic resistance genes, and heavy metals in concentrated leachate in China - Wei Liu; Hui Wang; Ziyang Lou; Changzheng Cui; Zhiyi Sun; Qiujie Huang (Waste Management, 2025)

Flowing biomaterials—lubrication matrix - Hui Yuan; Wenguo Cui (Science Bulletin, 2025)

Eco-friendly multifunctional CeO2/ZnMn2O4 heterojunction with robust photocatalysis for rapid bacteria-killing and highly effective eradication of formaldehyde simultaneously - Caihui Huang; Congyang Mao; Shuilin Wu; Yajun Liu; Dafu Chen; Chaofeng Wang; Khin Wee Lai; Yufeng Zheng; Hanpeng Liu; Zhaoyang Li; Shengli Zhu; Hui Jiang; et al. (Journal of Environmental Chemical Engineering, 2025)

Interaction mechanism of biochar dissolved organic matter (BDOM) and tetracycline for environmental remediation - Yun Zhu; Jinlong Yan; Fengfeng Sui; Hui Wang; Guixiang Quan; Liqiang Cui (Environmental Research, 2025)

Experimental investigation of thermo-hydro-mechanical interactions in frozen soil using an integrated monitoring system - Bing Wu; Hong-Hu Zhu; Xu-Hui Guo; De-Yang Wang; Cui Wang; Mohamed A. Meguid (Engineering Geology, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

RIG-I-driven CDKN1A stabilization reinforces cellular senescence - Cui Wang; Xiaoyu Jiang; Hong-Yu Li; Jianli Hu; Qianzhao Ji; Qiaoran Wang; Xiaoqian Liu; Daoyuan Huang; Kaowen Yan; Liyun Zhao; Yanling Fan; Si Wang; et al. (Science China Life Sciences, 2025)

Quantification of the coupling relationship between human footprint and ecological environment quality of artificial shorelines along the Yangtze River based on satellite observations - Yuanzheng Cui; Mi Zhang; Dong Xu; Hui Zou; Lei Wang; Guixiang Zha; Xuejun Duan (Environment, Development and Sustainability, 2025)

Glycosidase inhibitory isoflavones from the seeds of Cullen corylifolium and their structure–activity relationship study - Ying-Xiao Xiao; Yi-Ran Jiang; Wen-Hui Xu; Yuan Gao; Tian-Tian Bei; Hao Xu; Xue-Feng Wu; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

Polystyrene microplastics trigger colonic inflammation in rats via the TLR4/NF-κB/COX-2 pathway and modulation of intestinal microbiota - Xuemin Feng; Meng Zhang; Tianyang Zhao; Jianwei Cui; Hui Ye; Chunkui Zhou; Lin Ye; Liting Zhou (Toxicology, 2025)

Spatiotemporal transcriptome atlas of developing mouse lung - Xiaogao Meng; Wenjia Li; Jian Xu; Yao Yao; An Gong; Yumeng Yang; Fangfang Qu; Chenkai Guo; Hui Zheng; Guizhong Cui; Shengbao Suo; Guangdun Peng (Science Bulletin, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The enhanced mechanism of peroxymonsulfate activation by FeCo bimetallic metal organic framework: Synergy and active species - Mengjie Qin; Chuanhui Wang; Ding Zhao; Hui Cui; Yaqi Huang; Erkang Chen; Xianfeng Yang; Peng Guo; Yuanyuan Sun; Dongjiang Yang (Journal of Water Process Engineering, 2025)

Surface reconstruction via dissolution-reprecipitation of commercial alumina support to improve propane dehydrogenation performance - Haowei Wang; Wen-Cui Li; Ya-Dong Xie; Huan Yang; Ying Ma; An-Hui Lu (Chemical Engineering Journal, 2025)

Macrophage membrane-based biomimetic nanocarrier system for enhanced immune activation and combination therapy in liver cancer - Wei Ni; Mingzhu Zhang; Yueni Mo; Wei Du; Hui Liu; Zhaosong Wang; Yanfen Cui; He Zhang; Zhiyong Wang; Liming Liu; Hui Guo; Ruifang Niu; et al. (Drug Delivery and Translational Research, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Biologically controllable adhesion interfaces - Hui Yuan; Juan Wang; Wenguo Cui (Science Bulletin, 2025)

Oxygen vacancies in ultrathin BiOCl nanosheets induced Pt for enhanced methanol oxidation - Yukun Chang; Wenyuan Zhou; Yanhui Chen; Guangshun Ran; Fangyan Cui; Zicong Yang; Hui Song; Jinshu Wang; Hongyi Li (Process Safety and Environmental Protection, 2025)

Behavioral and molecular neurotoxicity of thermally degraded polystyrene in Caenorhabditis elegans - Hui Li; Jinyu Chen; Chenyin Dong; Xiaoxia Chen; Yulun Gu; Yongqi Jiang; Jingwen Cui; Haibo Chen (Journal of Hazardous Materials, 2025)

Study on the kinetic characteristics of polyoxymethylene (POM) pyrolysis and hydrothermal conversion - Cui Wang; Peng Liu; Bo Bai; Hui Jin (Journal of Cleaner Production, 2025)

Performance study of high-temperature proton exchange membrane fuel cell based on novel fan-fins gas channel - Zhiqing Zhang; Hui Liu; Feng Jiang; Shuwan Cui; Mingzhang Pan; Dongmei Li; Guangyu Ma; Jiajia Dou (Journal of Environmental Chemical Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Integration of untargeted lipidomics and targeted metabolomics revealed the mechanism of flavor formation in lightly cured sea bass driven via salt - Zi-Chun Zhang; Ji Wang; Meng Dong; Shuang Cui; Xu-Hui Huang; Lei Qin (Food Chemistry, 2025)

Selective asymmetric polarization of PAANa “diapers”: Solving the water challenge of prussian blue cathode in organic sodium ion battery - Yuhang Du; Xusheng Wang; Yucheng Zhu; Huanrong Zhang; Mengzhen Wei; Huimin Zhang; Hui Ma; Bao Wang; Yanbin Cui; Junhui Ji; Yonglin He; Kai Song; et al. (Chemical Engineering Journal, 2025)

Ball milling-induced strain engineering in nanoporous catalysts for tailoring hydrogen evolution reaction - Qite Li; Wence Xu; Zhonghui Gao; Yanqin Liang; Hui Jiang; Zhaoyang Li; Zhenduo Cui; Heng Liu; Shengli Zhu (Chemical Engineering Journal, 2025)

A novel anaerobic membrane bioreactor with magnetotactic bacteria for organic sulfur pesticide wastewater treatment: Improvement of enzyme activities, refractory pollutants removal and methane yield - Shiming Cui; Dongxue Hu; Zhaobo Chen; Yifan Wang; Jitao Yan; Shuya Zhuang; Bei Jiang; Hui Ge; Zihan Wang; Pengcheng Zhang (Chemical Engineering Journal, 2025)

Unraveling microbial community ecology and its effects on function and structure of halophilic aerobic granular sludge under varying salinities - Hui-Juan Yan; You-Wei Cui; Jun Chen; Hui-Kai Liang; Zhen-Ying Li (Bioresource Technology, 2025)

New insights into the progressive failure process and mechanisms of the 2017 Xinmo Slope in Mao County, China - Ling Zhu; Xiangjun Pei; Shenghua Cui; Luguang Luo; Hui Wang (Bulletin of Engineering Geology and the Environment, 2025)

Correction: Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Transcriptional and molecular simulation analysis of the response mechanism of anammox bacteria to 3,4-dimethylpyrazole phosphate stress - Cui-Zhong Chen; Jin Wang; Yi-Cheng Wang; Hui-Min Fu; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Hazardous Materials, 2025)

Numerical simulation on natural gas hydrates exploitation via multilateral well: Impacts on sand production and geomechanical responses - Youkeren An; Yiqun Zhang; Chengyu Hui; Khanjar Hasan; Panpan Zhang; Hongxing Du; Jinshan Wang; Xu Cui (Fuel, 2025)

Antioxidant potential of peptides from poultry hemoglobin via probiotic-assisted hydrolysis: Deciphering mechanisms at the cellular level and through molecular dynamics simulations - Wei Cui; Yong Xie; Yinghui Zhang; Xinlian Su; Tianqi Cui; Xingguang Chen; Zhaoming Wang; Feiran Xu; Hui Zhou; Baocai Xu (Food Research International, 2025)

A new method for quantitative characterization of dynamic migration behavior of NaCl in beef during marinating - Yingjie Feng; Fujia Dong; Cheng Wu; Jiarui Cui; Guangxian Wang; Zhongxiong Zhang; Songmin Cao; Sijia Liu; Hui Li; Yingkun Shi; Jianguo Yu; Songlei Wang (Food Research International, 2025)

Spatial pattern and methylation process of mercury enrichment in lake sediments during glacial periods in cold and arid regions - Jinda Zhang; Hui Zhang; Shengnan Zhao; Xiaohong Shi; Biao Sun; Junping Lu; Yu Liu; Wenbao Li; Yunxi Zhao; Zhimou Cui (Environmental Pollution, 2025)

Diverse loss mechanism enhanced microwave thermal effects of capacitor-like structure Ti3C2Tx MXene/CNT for rapid treatment of osteomyelitis - Mingxue Shi; Liguo Jin; Chaofeng Wang; Congyang Mao; Xiangmei Liu; Zhaoyang Li; Shengli Zhu; Hui Jiang; Zhenduo Cui; Yufeng Zheng; Shuilin Wu (Chemical Engineering Journal, 2025)

High-affinity uric acid clearance based on motile β-CD/F-127 polyrotaxane microspheres for enhanced diabetic wound repair - Xinlin Jiang; Zipeng Wu; Xiaoru Tan; Yichen Lin; Hui Xing; Yinglin Xuan; Dong Ma; Xin Cui (Carbohydrate Polymers, 2025)

Comamonas squillarum sp. nov., Isolated from Intestine of Red Swamp Crayfish (Procambarus clarkii) - Shi Shi; Dao-Feng Zhang; Hong-Chuan Wang; Fu-Hui Jiang; Li-Fan Cui; Ying Huang (Current Microbiology, 2025)

Assessment of the effects of characterization methods selection on the landslide susceptibility: a comparison between logistic regression (LR), naive bayes (NB) and radial basis function network (RBF Network) - Hui Shang; Lixiang Su; Yang Liu; Paraskevas Tsangaratos; Ioanna Ilia; Wei Chen; Shaobo Cui; Zhao Duan (Bulletin of Engineering Geology and the Environment, 2025)

STYX Interacts with FBXW7 to Promote AML Proliferation via Inhibiting the Ubiquitination of CCNE1 - Rui Yang; Jing Ning; Hainan Wang; Hui Ma; Lijuan Cui (Cell Biochemistry and Biophysics, 2025)

From winter dormancy to spring bloom: Regulatory mechanisms in Microcystis aeruginosa post-overwintering recovery - Chenjun Fu; Xinyi Wang; Jing Yu; Hu Cui; Shengnan Hou; Hui Zhu (Water Research, 2025)

The influence of greening management and landscape patterns on plant diversity in urban green spaces in Danzhou, China - Mei-Hui Zhu; Qian Li; Jia-Li Yuan; Josep Padullés Cubino; Joel B. Johnson; Jian-Peng Cui; Mir Muhammad Nizamani; Zhi-Xin Zhu; Hua-Feng Wang (Urban Forestry & Urban Greening, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Homestead withdrawal behaviour of rural migrants in China: The role of joint reform of hukou system and homestead system - Xiao Cui; Eddie Chi Man Hui; Jianfu Shen; Xin Lin; Siyi Wang; Fang He (Journal of Rural Studies, 2025)

Discovery of a polyester polyurethane-degrading bacterium from a coastal mudflat and identification of its degrading enzyme - Liting Zhang; Kaixun Cao; Hao Liu; Yuwei Wang; Bo Zhang; Heming Han; Zhongli Cui; Hui Cao (Journal of Hazardous Materials, 2025)

Experimental study of a gas-coupled pulse tube cold finger with both active piston and cold inertance tube as phase shifters for 8 K applications - Wenting Wu; Xiaoyu Cui; Wang Yin; Hejun Hui; Zhenhua Jiang; Yinong Wu; Shaoshuai Liu (International Journal of Refrigeration, 2025)

Key function mechanism of Na3PO4-modified NaX for enhanced performance and stability in side chain alkylation of toluene with methanol: DFT and experimental perspectives - Faraz Ahmad; Yueli Wen; Muhammad Zeeshan; Bin Wang; Awais Ashraf; Bai Hui; Zheng Cui; Chengda Li; Samia Kausar; Wei Huang (Fuel, 2025)

Integrated microbiome and metabolomics analysis of spoilage characteristics of modified atmosphere packaged pork - Xueya Wang; Ping Li; Xingguang Chen; Wei Cui; Shenyu Ni; Huaxing Xu; Yujuan Xu; Kezhou Cai; Hui Zhou; Baocai Xu (Food Research International, 2025)

Development of endolysin-integrated pH-responsive antiadhesive and antibacterial coatings with nanorods for the prevention of cross-contamination in fresh produce - Hexue Li; Cui Wang; Hui Shi (Food Research International, 2025)

Regional and longitudinal dynamics of human milk protein components assessed by proteome analysis on a fast and robust micro-flow LC–MS/MS system - Junxia Cao; Xinling Cui; Hai Lu; Hui Wang; Wen Ma; Zhan Yue; Kemiao Zhen; Qiaosi Wei; Hongmei Li; Shilong Jiang; Wantao Ying (Food Chemistry, 2025)

Effect of salt-induced supercooling stability on the quality of chicken breast during supercooled storage - Yiping Yang; Hengxun Lin; Yong Chen; Liye Cui; Hongliang Li; Shuangmei Xia; Chunhui Zhang; Junrong Huang; Hui Zhang; Jiansheng He; Xuemei Sun; Xia Li (Food Control, 2025)

Mantle induced hydration and oxidation of intracontinental granite sources in the North China Craton - Chuan-Mao Yang; Yi-Gang Xu; Xiao-Ping Xia; Jin-Hui Yang; Xiao-Long Huang; Christopher J. Spencer; Jin-Feng Sun; Ze-Xian Cui; Meng-Jing Li; Wan-Feng Zhang; Qing Yang (Earth and Planetary Science Letters, 2025)

Biochar supporting and sulfidation synergistically affect reactivity of nanoscale zerovalent iron towards sulfamethoxazole - Mi Li; Tiao Zhang; Jing Wang; Xiaoyu Xiao; Xinyi Zeng; Cui Hu; Xiaoming Zou; Wei Hui; Yuling Zheng (Chemical Engineering Journal, 2025)

A cost-effective, salt-resistant and environmentally stable solar evaporator with a wetting-gradient bilayer structure for long-term seawater desalination - Haoze Du; Yiwei Li; Jing Meng; Renjie Wei; Qingying Meng; Yuhao Cao; Ning Cui; Hongji Liu; Hui Yang (Chemical Engineering Journal, 2025)

Evaluation of Fenton-like reaction for sorption and degradation of kasugamycin in the presence of biochar - Wei Zhang; Liqiang Cui; Jingwen Ma; Shuyan Cui; Guixiang Quan; Jinlong Yan; Fengfeng Sui; Hui Wang; Kiran Hina; Qaiser Hussain (Environmental Geochemistry and Health, 2025)

Biotinylation-based lateral flow assays for pathogenic and total bacteria detection - Yongqiang Cao; Yanlin Chen; Xinyi Zhang; Hui Zeng; Lanyu Cui; Shengbin He (Analytica Chimica Acta, 2025)

Wastewater treatment performance and greenhouse gas emissions in constructed wetlands with different plant species across varying influent concentrations - Hu Cui; Si-Le Hu; Sheng-Nan Hou; Xin-Yi Wang; Jun-Feng Wang; Hui Zhu (Journal of Water Process Engineering, 2025)

Binding mechanisms and phosphorus adsorption performance of soil mineral-BDOM complexes - Jinlong Yan; Xiangqian Zhou; Wei Zhang; Fengli Cheng; Hui Wang; Liqiang Cui; Guixiang Quan (Journal of Water Process Engineering, 2025)

Constructing electron-rich metal sites in M0.5Co0.5O through N substitution for efficient peroxymonosulfate activation to degrade organic pollutants - Hui Cui; Chuanhui Wang; Yaqi Huang; Mengjie Qin; Ding Zhao; Xianfeng Yang; Peng Guo; Yuanyuan Sun; Dongjiang Yang (Journal of Cleaner Production, 2025)

Enhanced removal of sulfonamide antibiotics in water using high-performance S-nZVI/BC derived from rice straw - Xiao-Ming Zou; Tiao Zhang; Yu-Hua Dong; Cui Hu; Li Yin; Yu-Ling Zheng; Mi Li; Xiao-Yu Xiao; Wei Hui (Journal of Environmental Management, 2025)

Effect of active site size in dispersed MoS2 nanocatalysts on slurry-phase hydrocracking of residue - Hui Luo; Cheng Ding; Siqi Yin; Wenan Deng; Chuan Li; Wenlong Cui; Feng Du (Fuel, 2025)

Differences in bacterial community structure and volatile flavor substance of industrial-scale tiger skin chicken feet stored at air packaging and vacuum packaging - Xingguang Chen; Beibei Chu; Wei Cui; Guo Jie; Yinghui Zhang; Hui Zhou; Baocai Xu; Qianhui Gu (Food Research International, 2025)

Potential of probiotic-fermented Flos sophorae as a functional food: Enhanced anti-hyperuricemic activity and modulation of volatile components - Rui Cui; Cong Zhang; Zhen-Hui Pan; Teng-Gen Hu; Hong Wu (Food Bioscience, 2025)

Microbial fuel cell-assisted composting yields higher performance on metals passivation, antibiotics degradation, and resistance genes removal - Hu Cui; Sheng-Nan Hou; Xin-Yi Wang; Lei Li; Xiao-Hu Dai; Hui Zhu (Environmental Research, 2025)

Unveiling the structure–activity correlation in iron phosphorus trichalcogenide to realize enhanced potassium ion storage - Xiao-Hui Wu; Bi-Cui Chen; Zhi-Qiang Gu; Xian Lu; Hou-Yang Zhong; Pei-Weng Huang; Jie Zhang; Xue-You Tan; Yi Zhao (Chemical Engineering Journal, 2025)

Inhibiting overgrowth of filamentous fungi by magnetic powders: Combination effects of particle interface toxicity and magnetic microbe - Dong-Xu Zhou; You-Wei Cui; Ya-Nan Mi; Liu-Xu Jiang; Ming-Teng Li; Hui-Kai Liang; Hui-Juan Yan; Xu Wang (Chemical Engineering Journal, 2025)

Thermal-responsive microgels incorporated PVA composite hydrogels: Integration of two-stage drug release and enhanced self-healing ability for chronic wound treatment - Zeying Liu; Huixia Li; Yalin Huang; Jie Li; Ruiying Dong; Xue Yun; Yuqian Ren; Xiaonan Liu; Hui Hui; Lei Wu; Ziwei Lu; Yali Cui; et al. (Chemical Engineering Journal, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Dynamic transport of Zn2+ in ionic liquid intercalated V2O5 cathode for high-performance aqueous Zn-ion batteries - Wenzhe Su; Zanyu Chen; Xingkai Wang; Peng Cui; Minjie Yao; Hui Sun; Hong Zhang; Yida Deng; Xiaopeng Han; Wenbin Hu (Chemical Engineering Journal, 2025)

Bio-inspired construction of hydrophobic Mg(OH)2/Co-MOF/DOPO hybrids for simultaneously improving flame retardancy and mechanical properties of poly(L-lactic acid) composites - Cui Li; Zhaotian Ba; Bingchen Wu; Xinxin Shi; Hui Liu; Lili Ma; Xin Wen; Pingan Song (Chemical Engineering Journal, 2025)

Deciphering Mn2+ effects on anammox: From reversible inhibition to inactivated hydrazine decomposition, microbial community shifts, and granular sludge lysis - Zheng Fu; Manjie Li; Hui Xu; Shenshen Cui; Xinshan Song; Yuhui Wang (Chemical Engineering Journal, 2025)

Photothermal-thermoelectric synergy coupling localized surface plasmon resonance for enhanced flexible photoelectrochemical sensor performance - Mengqi Chen; Hui Tian; Ling Qi; Yuying Zhang; Hongmei Yang; Shenguang Ge; Lina Zhang; Yan Zhang; Lin Li; Kang Cui; Jinghua Yu (Chemical Engineering Journal, 2025)

Ag,Cd double gradient doping at front interface for high efficiency CZTSSe solar cells - Xiu-Chun Guo; Xin-Pan Cui; Ke Sun; Xue-Ying Luo; Wen-Hui Zhou; Dong-Xing Kou; Si-Xin Wu (Chemical Engineering Journal, 2025)

Integrating aromatic plants into indoor biophilic environments: Species selection based on psychophysiological effects and bioactive volatile compounds - Jingxian Cui; Zhaoming Li; Wenzhu Zhang; Lingshan Wang; Hong Liu; Hui Liu (Building and Environment, 2025)

Activation of 5-HT6 Receptors in the Ventrolateral Orbital Cortex Produces Anti-Anxiodepressive Effects in a Rat Model of Neuropathic Pain - Yu-Long Zhao; Hui-Yuan Yi; Sani Sa’idu Baba; Yi-Xiao Guo; Xiao-Cui Yuan; Xue-Mei Hou; Ling-Li Liang; Fu-Quan Huo (Molecular Neurobiology, 2025)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

The intervention mechanism of Tanshinone IIA in alleviating neuronal injury induced by HMGB1 or TNF-α-mediated microglial activation - Yan-Zhu Quan; Jing-He Wang; Si-Hui Zhang; Guang-Nan Jin; Jing-Mei Lu; Yi-Ming Liu; Hong-Yan Gao; Jin-Yi Zhou; Bing-Zhe Wang; Yan Xin; Yue-Xian Cui; Xiang Xu; et al. (Toxicology in Vitro, 2024)

Analysis on pollutants removal and sludge characteristics of a novel two-phase anaerobic/aerobic/integrated deoxygenated and anoxic reactor associated with membrane process for treating pesticide wastewater - Shuya Zhuang; Zhaobo Chen; Zhibo Liang; Dongxue Hu; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Jitao Yan; Yifan Wang; Shiming Cui (Science of The Total Environment, 2024)

Carbon availability regulates fungal and bacterial populations in halophilic aerobic granular sludge treating saline wastewater - Hui-Kai Liang; You-Wei Cui; Zhen-Ying Li; Hui-Juan Yan; Xu Wang (Science of The Total Environment, 2024)

Control of dissolved H2 concentration enhances electron generation, transport and TCE reduction by indigenous microbial community - Weiwei Ouyang; Yao Huang; Cui Li; Wenyi Huang; Songhu Yuan; Hui Liu (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Influence of core-shell structure design on the preparation of oil-contaminated soil ceramsite and the pollutant decomposition effect - Wukui Zheng; Jinfeng Sun; Tian Cui; Yingying Hu; Yuxuan Yang; Hui Li (Process Safety and Environmental Protection, 2024)

Middle to late Miocene cooling and drying in the northern Tibetan Plateau based on evidence from plant-insect interactions - Cui Wang; Yusheng (Chris) Liu; Natalia Maslova; Hui Jia; Qijia Li; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Synergistic effects of microplastics and sulfonamide on greenhouse gas emissions in agricultural ditch sediments: Insights into microbial interactions - Yu-Ting Shen; Sheng-Nan Hou; Ya-Qin Miao; Xing-Yi Wang; Hu Cui; Hui Zhu (Journal of Hazardous Materials, 2024)

Spatial patterns, source apportionment, and risk assessment of polychlorinated biphenyls (PCBs) in the surface sediments of eastern China lakes along a latitudinal gradient: Insights guided by full-congener analysis - Jing Dong; Xingru Zhao; Ran Dai; Rui Guo; Chengyou Liu; Xiaoai Cui; Yaqing Liu; Hui Wang; Binghui Zheng (Journal of Hazardous Materials, 2024)

Fabrication of fluorinated magnetic microporous organic network for selective and efficient extraction of benzoylurea insecticides in tea beverages - Hui-Ping Yu; Qian-Qian Xu; Xin Wang; Yuan-Yuan Cui; He-Fang Wang; Cheng-Xiong Yang (Food Chemistry, 2024)

Roles of mTOR-p70S6K signaling pathway and HO-1 in ethylbenzene-induced hepatoxic effects in L02 cells - Siyu Liu; Linlin Chen; Hui Peng; Qiang Zhang; Qiang Zeng; Bo Cui; Ming Zhang (Food and Chemical Toxicology, 2024)

Distribution of mercury and methylmercury in ice-water-sediments in lakes during the freezing period under the influence of ice cover - Yunxi Zhao; Shengnan Zhao; Xiaohong Shi; Junping Lu; Zhimou Cui; Fan Zhang; Hui Zhang; Jinda Zhang; Yue Han (Environmental Pollution, 2024)

A novel and cost-effective biological denitrification associated with membrane process for treating pesticide wastewater: Excellent nitrogen removal effect and higher environment benefits - Shuya Zhuang; Dongxue Hu; Zhaobo Chen; Zhibo Liang; Junzhe Song; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Jitao Yan; Yifan Wang; Shiming Cui (Desalination, 2024)

The mechanism of plasma affecting biomass pyrolysis to more H2, activated char and less CO2 - Deng Zhao; Yongxiang Liang; Lei Gou; Yalu Cui; Huashan Wang; Chunsheng Wang; Hui Liu; Shuai Guo; Suning Li (Chemical Engineering Journal, 2024)

Engineering of calcium overload for state-of-the-art tumor therapy - Xinping Liu; Hui Hu; Jinjin Chen; Yi Li; Yaming Cheng; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2024)

Exploration of microwave absorptivity and catalysis of CMF@Co-MoS2 for microwave-initiated depolymerization of lignin - Yishuai Fu; Wenliang Wang; Hui Miao; Yangyi Cui; Yutong Chen; Ziwei Wang; Guowei Xiao; Bailiang Xue; Weikun Jiang (Chemical Engineering Journal, 2024)

High-homogeneous recyclable self-cured epoxy resins based on imine - Changbo Zhao; Guohua Huang; Hao Zhang; Hui Xie; Feixiang Sha; Lukun Feng; Jinze Cui; Xiyan Li; Mingliang Wang; Feng Bao; Zhiyong Xue; Caizhen Zhu; et al. (Chemical Engineering Journal, 2024)

Microbial fuel cell-assisted composting shows stronger capacity to immobilize phosphorus: Emphasized on bacterial structures and functional enzymes - Hu Cui; Lei Li; Hao Zhou; Wei-Jun Zhang; Xiao-Hu Dai; Hui Zhu (Bioresource Technology, 2024)

Acid resistance of different polysaccharide hydrocolloids: pH effects - Huaitian Cui; Lianzhong Ai; Zhiqiang Xiong; Fan Xie; Zibo Song; Hui Zhang (Bioactive Carbohydrates and Dietary Fibre, 2024)

FOXO3a-interacting proteins’ involvement in cancer: a review - Zhiqiang Dong; Zongming Guo; Hui Li; Dequan Han; Wei Xie; Shaoning Cui; Wei Zhang; Shuhong Huang (Molecular Biology Reports, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

The Associations of Urinary DEHP Metabolites in Pregnant Women with Serum Thyroid Hormone and Thyroid-Related Genes in Neonatal Umbilical Cord Blood in Jilin, China - Xueting Zhang; Wen Qi; Zihan Su; Hui Ye; Haotang Zhao; Jianwei Cui; Xiaoqi Fang; Liuwei Shi; Xueying Liu; Ziyu Wang; Hang Xu; Fuju Wu; et al. (Exposure and Health, 2024)

The Temperature-Dependent Monotonic Mechanical Characteristics of Marine Sand–Geomembrane Interfaces - Zhiming Chao; Hongyi Zhao; Hui Liu; Peng Cui; Danda Shi; Hai Lin; Yang Lu; Bing Han; Shuang Chen (Journal of Marine Science and Engineering, 2024)
The utilization of geomembrane reinforcement technology is pervasive in marine sand foundation reinforcement projects. However, the elevated temperatures and intricate stress conditions prevalent in marine environments exert a notable influence on the mechanical characteristics of geomembrane interfaces comprising marine sand, which impedes the efficacy of geomembrane reinforcement in marine sand foundations. Nevertheless, there is a lack of research investigating the temperature-dependent interfacial mechanical performance of geomembranes and marine sand under diverse stress states. In this study, a series of monotonic shear tests were carried out on the interface between geomembranes and marine sand within a temperature range of 5 °C to 80 °C. These experiments were carried out using a self-developed large-scale temperature-controlled interfacial dynamic and static shear device. The experimental results demonstrate that temperature has a pronounced effect on the monotonic mechanical characteristics of the geomembrane–marine sand interface, which displays clear temperature dependence. The findings of this study may help in the design and optimization of offshore projects where a marine sand–polymer layer interface exists.

In-stream attenuation and enantioselective fractionation of psychiatric pharmaceuticals in a wastewater effluent-dominated river basin - Weimin Wang; Tian Xie; Ning Ma; Xiaoman Jiang; Hui Zhang; Tao Sun; Baoshan Cui (Science of The Total Environment, 2024)

Effect of catalysts La2O3/Carbon on the electrochemical and kinetic properties of AB5-type hydrogen storage alloy - Xiangyang Wang; Hui Yong; Yan Cui; Yaoli Xun; Maoxiang Yu; Yingjie Li; Jifan Hu; Yanghuan Zhang (Fuel, 2024)

Cyanide content, nutrient composition, physicochemical properties and sensory quality of flaxseed oil bodies prepared from flaxseeds (Linum usitatissimum L.) treated with different heat treatment methods - Rui Zheng; Hui-Lin Liu; Nan-Nan Cui; Jun-Zhuo Zhou; Xin Sun; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2024)

Molecular cloning and functional characterization of eight galectin genes from Takifugu obscurus - Ying Huang; Sheng-Hao Du; Li-Fan Cui; Fu-Hui Jiang; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Design of graphitic multichannel monolith electrode with in-situ transformed Ni-N-C sites for continuous electrolysis of CO2 - Xu Hu; Hong-Liang Xu; Ling-Yu Dong; Wen-Cui Li; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2024)

Ammonium-ion thermal charging supercapacitors for low-grade heat conversion and storage - Zhiwei Han; Jiaxin Cui; Jing Wang; Hui Dou; Shengliang Zhang; Xiaogang Zhang (Chemical Engineering Journal, 2024)

Long-term organic fertilization increases phosphorus content but reduces its release in soil aggregates - Hu Cui; Brian Shutes; Sheng-Nan Hou; Xin-Yi Wang; Hui Zhu (Applied Soil Ecology, 2024)

Dynamic Response Prediction Model for Jack-Up Platform Pile Legs Based on Random Forest Algorithm - Xiaohui Cui; Hui Liu; Xiang Lin; Jiahe Zou; Yu Wang; Bo Zhou (Journal of Marine Science and Engineering, 2024)
Jack-up offshore platforms are widely used in many fields, and it is of great importance to quickly and accurately predict the dynamic response of platform pile leg structures in real time. The current analytical techniques are founded upon numerical modelling of the platform structure. Although these methods can be used to accurately analyze the dynamic response of the platform, they require a large quantity of computational resources and cannot meet the requirements of real-time prediction. A predictive model for the dynamic response of the pile leg of a jack-up platform based on the random forest algorithm is proposed. Firstly, a pile leg dynamic response database is established based on high-fidelity numerical model simulation calculations. The data are subjected to cleaning and dimensional reduction in order to facilitate the training of the random forest model. Cross-checking and Bayesian optimization algorithms are used for the selection of random forest parameters. The results show that the prediction model is capable of outputting response results for new environmental load inputs within a few milliseconds, and the prediction results remain highly accurate and perform well at extreme values.

Differential allelopathic effects of mangrove plants Kandelia obovata and Aegiceras corniculatum on harmful algal species: Potential applications in algal bloom control - Brian Yu-Keung Wong; Yang-Hang Chen; Kai-Hui Cui; Hai-Chao Zhou; Feng-Lan Li; Nora Fung-Yee Tam; Fred Wang-Fat Lee; Steven Jing-Liang Xu (Marine Pollution Bulletin, 2024)

Anaerobic degradation of pesticide wastewater: Improving sludge characteristics and reducing membrane fouling with combined tandem UASB+membrane system with high velocity settlers - Jitao Yan; Zhaobo Chen; Dongxue Hu; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Shuya Zhuang; Zhibo Liang; Yifan Wang; Shiming Cui (Water Research, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Regional differences in molecular characteristics of atmospheric water-soluble organic carbon over northern China: Comparison of remote, rural, and urban environments - Hui Wen; Yue Zhou; Yuhui He; Tianshuang Wang; Wei Pu; Baoqing Zhang; Jiecan Cui; Jun Liu; Xin Wang (Science of The Total Environment, 2024)

Mechanism on microbial transglutaminase and Tremella fuciformis polysaccharide-mediated modification of lactoferrin: Development of functional food - Kangning Wang; Hui Sun; Jiahui Wang; Zhihan Cui; Jiayi Hou; Fuping Lu; Yihan Liu (Food Chemistry, 2024)

Aqueous extract of pulp of maqui-berry (Aristotelia chilensis) induces apoptosis in human endometrial carcinoma ishikawa cells via mitochondrial and endoplasmic reticulum stress pathways - Wang-Wei Zhang; Yan-Cui Liang; Kiran Thakur; Jian-Guo Zhang; Carla Vidal-San Martin; Jose M. Bastias-Montes; Jose Y. Neira-Hinojosa; Siau Hui Mah; Gokhan Zengin; Hammad Saleem; Mohammed El-Haffidi; Jose G. Avila-Acevedo; et al. (Food Bioscience, 2024)

Tamarind seeds polysaccharide: Structure, properties, health benefits, modification and food applications - Hui Zhang; Huaitian Cui; Fan Xie; Zibo Song; Lianzhong Ai (Food Hydrocolloids, 2024)

Greenhouse gases emissions and microbial assembly mechanism in constructed wetlands for treating saline-alkali and fluoride-laden drainage water - Yaqin Miao; Yuting Shen; Shengnan Hou; Hu Cui; Weihong Zhu; Hui Zhu (Chemical Engineering Journal, 2024)

Unlocking the ultrafast laser response and low initiation energy of perchlorate-free tetrazine-based energetic coordination compounds - Hong-Yi Bian; Yun-Fan Yan; Meng Cui; Hao-Hui Xie; Tian-Tian Song; Xiao-Di Guo; Jian-Gang Xu; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2024)

Shining light on atomic vacancies in electrocatalysts for boosted water splitting - Mingpeng Chen; Huachuan Sun; Qingjie Lu; Dequan Li; Di Liu; Tong Zhou; Baoye Zi; Hongshun Zheng; Bin Xiao; Tianwei He; Jianhong Zhao; Yumin Zhang; et al. (Chemical Engineering Journal, 2024)

A Chromium-Based magnetic resonance probe for in situ gastric pH imaging - Yan Xu; Weitao Yang; Zhuoyao Wu; Hui Wang; Tianming Cui; Weiwei Zeng; Yanjing Yun; Bingbo Zhang (Chemical Engineering Journal, 2024)

Synergistic optimization of baffles and aeration to improve the Light/Dark cycle of microalgae photobioreactor for enhanced nitrogen removal performance: Computational fluid dynamics and experimental verification - Yuanqi Liu; Zhuochao Liu; Zhensheng Xiong; Yanni Geng; Dan Cui; Spyros G. Pavlostathis; Houxing Chen; Qingchun Luo; Genping Qiu; Qiaohong Dong; Liming Yang; Penghui Shao; et al. (Bioresource Technology, 2024)

Estimating high spatio-temporal resolution XCO2 using spatial features deep fusion model - Liu Cui; Hui Yang; Yina Qiao; Xinfeng Huang; Gefei Feng; Qingzhou Lv; Huaiwei Fan (Atmospheric Research, 2024)

A general climatology of categorized Martian ionospheric irregularities - Xin Wan; Jiahao Zhong; Yongqiang Hao; Chao Xiong; Hui Wang; Yutian Cao; Jun Cui; Yiwen Liu; Qiaoling Li; Jiawei Kuai (Science China Earth Sciences, 2024)

Application of unmanned aerial vehicle tilt photography technology in geological hazard investigation in China - Zhi-Hong Zhao; Hao Sun; Nian-Xiao Zhang; Tian-Hui Xing; Guan-Hua Cui; Jin-Xing Lai; Tong Liu; Yi-Bin Bai; Hai-Jun He (Natural Hazards, 2024)

Exosomes from Hypoxia-treated Mesenchymal Stem Cells: Promoting Neuroprotection in Ischemic Stroke Through miR-214-3p/PTEN Mechanism - Qian Wu; Jia-Huan Wu; Zhi-Yuan Ye; Wen She; Wen-Jie Peng; Hui-Xin Zhang; Cui Qi; Tian Tian; Xiao-Yu Hou; Jun Gao (Molecular Neurobiology, 2024)

Site-directed mutagenesis leads to the optimized transglycosylation activity of endo-beta-N-acetylglucosaminidase from Trypanosoma brucei - Yi Ding; Zheng-Hui Chen; Juan Cui; Xin-Yu Ding; Xiao-Dong Gao; Ning Wang (Glycoconjugate Journal, 2024)

Examination of the effects of excess microalgae availability on the disruption of mussel byssus secretion - Ji-Yue Ni; Yan Zhou; Yu-Qing Wang; Shi-Hui Huang; Qian-Wen Cui; Wen-Yi Wang; Xiao-Ying Yang; Deborah M. Power; Yi-Feng Li (Aquaculture, 2024)

Study on the biocontrol effect of Streptomyces sp. NEAU-KT41 and its cell-free culture filtrate against wheat root rot - Yang Cai; Jinzhao Gu; Ling Ling; Hui Bing; Lijie Cui; Ailin Li; Yance Zhang; Xinyu Kong; Xiangjing Wang; Junwei Zhao; Wensheng Xiang (Physiological and Molecular Plant Pathology, 2024)

Low expression of selenoprotein S induces oxidative damage in cartilages - Yixin Cui; Yucheng Liao; Yonghui Chen; Xu Zhao; Yi Zhang; Hui Wang; Lian Li; Xinhe Zhang; Kunpan Chen; Mingzhao Jia; Jing Tian; Xingran Ruan; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Degradation of o-dichlorobenzene by DBD-NTP co-modified titanium gel catalyst - Wenbo Zhang; Yi Xing; Wei Su; Jiaqing Wang; Haoqi Jia; Yongkang Cui; Jing Chen; Hui Zhang (Journal of Environmental Sciences, 2024)

Optimization of ethylene thiourea, cyanide, and heavy metals removal and gas production enhancement in organosulfur pesticide wastewater using ferromagnetic biochar in anaerobic membrane bioreactor - Yifan Wang; Zhaobo Chen; Dongxue Hu; Liwen Jiang; Shiming Cui; Shuya Zhuang; Jitao Yan; Jian Dong; Fei Han; Bei Jiang; Hui Ge; Zhibo Liang (Chemical Engineering Journal, 2024)

The Sequence of Heating and Loading Affects Shear Properties of Granite Fractures Under High Temperature - Fanzhen Meng; Jianhua Han; Zhiyuan Li; Feili Wang; Zhufeng Yue; Qijin Cai; Guanghao Cui; Hui Zhou (Rock Mechanics and Rock Engineering, 2024)

Sedimentary architecture of a sandy braided river with seasonal hydrodynamic variations: insights from the Permian Lower Shihezi Formation, Ordos Basin, China - Xiaohui Li; Yuliang Su; Guanglei Ren; Feixiang Gao; Shuhong Yan; Huachao Sun; Hui Ran; Mengdi Cui (Frontiers of Earth Science, 2024)

International container intermodal competitiveness: An empirical study from Chinese hub ports - Hui Meng; Haonan Xu; Ying Cui; Jiaguo Liu (Ocean & Coastal Management, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Environmental impacts of fertilization during rice production in saline-alkali paddy fields based on life cycle assessment - Xinyi Wang; Hui Zhu; Shengnan Hou; Hu Cui; Baixing Yan (Journal of Cleaner Production, 2024)

Fate and partition of perfluoroalkyl acids (PFAAs) driven by particles in mangrove ecosystems: Mechanistic insights and environmental implications - Jianwei Dong; Shiya Gu; Meiqi Shang; Yang Cui; Xin Song; Hongbing Wang; Hui Xie; Ranran Feng; Dandan Yan; Yongfen Du; Yang Wang (Journal of Cleaner Production, 2024)

Sensitive colorimetric and fluorescence dual-mode detection of thiophanate-methyl based on spherical Fe3O4/GONRs composite nanozyme - Shengmei Tai; Hui Cao; Yingkang Cui; Chifang Peng; Jianguo Xu; Zhouping Wang (Food Chemistry, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

pH-dependent growth of alumina nanorods with a high aspect ratio for enhanced propane dehydrogenation performance - Haowei Wang; Wen-Cui Li; Ying Ma; Yu Zhang; Shu-Zhen Zhou; An-Hui Lu (Chemical Engineering Journal, 2024)

Divergent responses to climatic conditions in radial growth of Abies fargesii along elevation at the eastern edge of the Tibetan Plateau - Shengjie Wang; Yuan Jiang; Junti Liu; Shuai Yuan; Minghao Cui; Qianzhi Xiong; Yizaitiguli Waili; Muyi Kang; Hui Xu (Trees, 2024)

Placenta-targeted Treatment Strategies for Preeclampsia and Fetal Growth Restriction: An Opportunity and Major Challenge - Jianjian Cui; Zejun Yang; Ruilin Ma; Wencong He; Hui Tao; Ya’nan Li; Yin Zhao (Stem Cell Reviews and Reports, 2024)
The placenta plays a crucial role in maintaining normal pregnancy. The failure of spiral artery remodeling (SAR) is a key factor leading to placental ischemia and poor perfusion which is strongly associated with obstetric diseases, including preeclampsia (PE) and fetal growth restriction (FGR). Existing interventions for PE and FGR are limited and termination of pregnancy is inevitable when the maternal or fetus condition deteriorates. Considering the safety of the mother and fetus, treatments that may penetrate the placental barrier and harm the fetus are not accepted. Developing targeted treatment strategies for these conditions is urgent and necessary. With the proven efficacy of targeted therapy in treating conditions such as endometrial cancer and trophoblastic tumors, research on placental dysfunction continues to deepen. This article reviews the studies on placenta-targeted treatment and drug delivery strategies, summarizes the characteristics proposes corresponding improvement measures in targeted treatment, provides solutions for existing problems, and makes suggestions for future studies. Graphical abstract

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Efficient removal of hexavalent chromium from wastewater using a novel sodium alginate-biochar composite adsorbent - Yushi Tian; Xiaolin Sun; Nianhua Chen; Xintong Cui; Hui Yu; Yujie Feng; Defeng Xing; Weihua He (Journal of Water Process Engineering, 2024)

Layer-specific mechanisms of perfluoroalkyl acid (PFAA) transport and partition in estuarine environments: Unveiling the depth-dependent differences - Jianwei Dong; Ranran Feng; Zhiming Yao; Jun Wang; Yang Wang; Hongbing Wang; Dandan Yan; Yang Cui; Hui Xie; Yongfen Du; Xinghui Xia (Journal of Hazardous Materials, 2024)

Novel polyurethane-degrading cutinase BaCut1 from Blastobotrys sp. G-9 with potential role in plastic bio-recycling - Zhitong Jiang; Xue Chen; Huizhen Xue; Zhoukun Li; Jinhui Lei; Muming Yu; Xin Yan; Hui Cao; Jie Zhou; Jiawei Liu; Mingna Zheng; Weiliang Dong; et al. (Journal of Hazardous Materials, 2024)

Inorganic flocculant-based soybean urease extraction and its effect on biomineralization - Han-Jiang Lai; Hui Liu; Ming-Juan Cui; Jun-Jie Zheng; Zhi-Bo Chen; Zhi-Chao Zhang (Journal of Cleaner Production, 2024)

Novel insight into the formation and improvement mechanism of physical property in fermented tilapia sausage by cooperative fermentation of newly isolated lactic acid bacteria based on microbial contribution - Qiaoyan Cui; Laihao Li; Hui Huang; Yanping Yang; Shengjun Chen; Chunsheng Li (Food Research International, 2024)

Multiscale approach to the characterization of the interfacial properties of micellar casein and whey protein blends and their effects on recombined dairy creams - Guosen Yan; Yue Li; Hui Wang; Shibo Cui; Yan Li; Liebing Zhang; Jianguo Yan (Food Research International, 2024)

H*ads dynamics engineering via bimetallic Pd–Cu@MXene catalyst for enhanced electrocatalytic hydrodechlorination - Lan-Ying Liu; Min-Hua Cui; John Justo Ambuchi; Shi-Ming Niu; Xin-Hui Li; Wo-Long Wang; He Liu; Guo-Shuai Liu; Ai-Jie Wang (Environmental Research, 2024)

Water purification capacity of ecological ditch: A systematic review and meta-analysis of influencing factors - Yu-Ting Shen; Sheng-Nan Hou; Si-Le Hu; Ya-Qin Miao; Hu Cui; Hui Zhu (Ecological Engineering, 2024)

Copper ferrite nanoparticles anchored laser-induced graphene as novel nanoenzyme for the electrochemical catalyzing and sensing of β-estradiol in serum - Minghui Cai; Haixu Yao; Mengnan Li; Yan Yan; Yang Cao; Jiaxin Li; Huiyu Su; Wenwen Zhang; Hui Zhu; Feiyun Cui (Chemical Engineering Journal, 2024)

Enhanced medium-chain fatty acid production from sewage sludge by combined electro-fermentation and anaerobic fermentation - Xiaoyan Sun; Hui Chen; Ting Cui; Lei Zhao; Cheng Wang; Xuejun Zhu; Tao Yang; Yanan Yin (Bioresource Technology, 2024)

Picea pungens exhibits greatest tolerance to short-time thermal stress compared to Picea abies, and Picea omorika - Fangqun Ouyang; Meng Sun; Xia Cui; Mulualem Tigabu; Hui Zhang; Junyu Deng; Junhui Wang; Yu Wei; Ran He (New Forests, 2024)

Dominant role of the non‐forest woody vegetation in the post 2015/16 El Niño tropical carbon recovery - Lei Fan; Tianxiang Cui; Jean‐Pierre Wigneron; Philippe Ciais; Stephen Sitch; Martin Brandt; Xin Li; Shuli Niu; Xiangming Xiao; Jérome Chave; Chaoyang Wu; Wei Li; et al. (Global Change Biology, 2024)
The extreme dry and hot 2015/16 El Niño episode caused large losses in tropical live aboveground carbon (AGC) stocks. Followed by climatic conditions conducive to high vegetation productivity since 2016, tropical AGC are expected to recover from large losses during the El Niño episode; however, the recovery rate and its spatial distribution remain unknown. Here, we used low‐frequency microwave satellite data to track AGC changes, and showed that tropical AGC stocks returned to pre‐El Niño levels by the end of 2020, resulting in an AGC sink of Pg C year −1 during 2014–2020. This sink was dominated by strong AGC increases ( Pg C year −1 ) in non‐forest woody vegetation during 2016–2020, compensating the forest AGC losses attributed to the El Niño event, forest loss, and degradation. Our findings highlight that non‐forest woody vegetation is an increasingly important contributor to interannual to decadal variability in the global carbon cycle.

Increased crossing of thermal stress thresholds of vegetation under global warming - Xiangyi Li; Chris Huntingford; Kai Wang; Jiangpeng Cui; Hao Xu; Fei Kan; Nazhakaiti Anniwaer; Hui Yang; Josep Peñuelas; Shilong Piao (Global Change Biology, 2024)
Temperature extremes exert a significant influence on terrestrial ecosystems, but the precise levels at which these extremes trigger adverse shifts in vegetation productivity have remained elusive. In this study, we have derived two critical thresholds, using standard deviations (SDs) of growing‐season temperature and satellite‐based vegetation productivity as key indicators. Our findings reveal that, on average, vegetation productivity experiences rapid suppression when confronted with temperature anomalies exceeding 1.45 SD above the mean temperature during 2001–2018. Furthermore, at temperatures exceeding 2.98 SD above the mean, we observe the maximum level of suppression, particularly in response to the most extreme high‐temperature events. When Earth System Models are driven by a future medium emission scenario, they project that mean temperatures will routinely surpass both of these critical thresholds by approximately the years 2050 and 2070, respectively. However, it is important to note that the timing of these threshold crossings exhibits spatial variation and will appear much earlier in tropical regions. Our finding highlights that restricting global warming to just 1.5°C can increase safe areas for vegetation growth by 13% compared to allowing warming to reach 2°C above preindustrial levels. This mitigation strategy helps avoid exposure to detrimental extreme temperatures that breach these thresholds. Our study underscores the pivotal role of climate mitigation policies in fostering the sustainable development of terrestrial ecosystems in a warming world.

A novel approach for sludge deep-dewatering via flowing-out enhancement but not relying on cell lysis and bound water release - Hao Zhang; Wen-Hui Liu; Yun-Yan Gao; Ping Sun; Yuan-Ping Zeng; Lin-Lin Ma; Jiang-Nan Wu; Shun-Gui Zhou; Xi-Qin Cui; Raymond Jianxiong Zeng; Hou-Feng Wang (Water Research, 2024)

Performance of a novel up-flow electrocatalytic hydrolysis acidification reactor (UEHAR) coupled with anoxic/oxic system for treating coking wastewater - Jian Dong; Zhaobo Chen; Fei Han; Dongxue Hu; Hui Ge; Bei Jiang; Jitao Yan; Shuya Zhuang; Yifan Wang; Shiming Cui; Zhibo Liang (Water Research, 2024)

Insights into the effect of guanylate-binding protein 1 on the survival of Brucella intracellularly - Zhiqiang Li; Shuli Wang; Jincheng Han; Guangli Yang; Li Xi; Chunmei Zhang; Yanyan Cui; Shuanghong Yin; Yu Zhang; Hui Zhang (Veterinary Microbiology, 2024)

Hyposalinity stress reduces mussel byssus secretion but does not cause detachment - Wen-Yi Wang; Ji-Yue Ni; Shi-Hui Huang; Qian-Wen Cui; Yu-Qing Wang; Zhong-Qi Gu; Yi-Feng Li (Science of The Total Environment, 2024)

Greenhouse gases emissions and carbon budget estimation in horizontal subsurface flow constructed wetlands with different plant species - Sile Hu; Weidong Feng; Yuting Shen; Xiaoling Jin; Yaqin Miao; Shengnan Hou; Hu Cui; Hui Zhu (Science of The Total Environment, 2024)

Five new meroterpenes from the seeds of Psoralea corylifolia and their diacylglycerol acyltransferase activity - Xiao-Jing Shao; Meng-Xue Xiu; Xue-Hui Wang; Wen-Hui Xu; Ying-Xiao Xiao; Yuan Gao; Yi-Ran Jiang; Tian-Tian Bei; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2024)

The RNA binding protein EHD6 recruits the m6A reader YTH07 and sequesters OsCOL4 mRNA into phase-separated ribonucleoprotein condensates to promote rice flowering - Song Cui; Peizhe Song; Chaolong Wang; Saihua Chen; Benyuan Hao; Zhuang Xu; Liang Cai; Xu Chen; Shanshan Zhu; Xiangchao Gan; Hui Dong; Yuan Hu; et al. (Molecular Plant, 2024)

Amide and carboxyl dual-functionalized magnetic microporous organic networks for efficient extraction of cephalosporins - Xu-Hui Li; Yuan-Yuan Cui; Shi-Lei Ji; Abdukader Abdukayum; Cheng-Xiong Yang (Food Chemistry, 2024)

A comprehensive evaluation of lipid profiles and nutritional quality in different animal source muscle tissues - Shuang Cui; Ying Wang; Zheng Zhou; Yu-Ying Zhang; Xu-Hui Huang; Da-Yong Zhou; Lei Qin (Food Bioscience, 2024)

Self-supporting high-entropy Co-Cr-Fe-Ni-Nb oxide electrocatalyst with nanoporous structure for oxygen evolution reaction - Yuhan Lin; Wence Xu; Zhonghui Gao; Yanqin Liang; Hui Jiang; Zhaoyang Li; Shuilin Wu; Zhenduo Cui; Huaijun Sun; Huifang Zhang; Shengli Zhu (Chemical Engineering Journal, 2024)

Developmental toxicity and potential mechanisms exposed to polystyrene microplastics and polybrominated diphenyl ethers during early life stages of fat greenling (Hexagrammos otakii) - Yanyan Shi; Xiaoyan Wei; Zheng Zhang; Shuai Wang; Hui Liu; Dandan Cui; Wenyuan Hua; Yanxin Fu; Yan Chen; Zhuang Xue; Xuejie Li; Wei Wang (Aquatic Toxicology, 2024)

Forsythoside A protects against Zearalenone-induced cell damage in chicken embryonic fibroblasts via mitigation of endoplasmic reticulum stress - Hui Hu; Qiang Yu; Yu Zheng; Hongjie Cui; Xiaohong Huang; Kaizhao Zhang (Veterinary Research Communications, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Germ-free status but not subacute polychlorinated biphenyl (PCB) exposure altered hepatic phosphatidylcholine and ether-phosphatidylcholine levels in mice - Xueshu Li; Hui Wang; Hui Wang; Amanda J. Bullert; Julia Yue Cui; Kai Wang; Hans-Joachim Lehmler (Toxicology, 2024)

Patient-derived pathogenic microbe deposition enhances exposure risk in pediatric clinics - Wan Wang; Zongyao Qiu; Hui Li; Xiaorong Wu; Ying Cui; Lixiang Xie; Bozhen Chang; Peipei Li; Hong Zeng; Tao Ding (Science of The Total Environment, 2024)

Soil amendments reduce CH4 and CO2 but increase N2O and NH3 emissions in saline-alkali paddy fields - Hu Cui; Hui Zhu; Fu-Man Zhang; Xin-Yi Wang; Sheng-Nan Hou; Wei-Dong Feng (Science of The Total Environment, 2024)

Mechanistic insights and catalytic enhancement of phenolic wastewater supercritical water gasification: A combined experiment and density functional theory study - Xingang Qi; Jiawei Zhang; Xujun Li; Jinhua Cui; Yunan Chen; Hui Jin; Liejin Guo (Journal of Environmental Management, 2024)

Formation and improvement mechanism of physical property and volatile flavor of fermented tilapia surimi by newly isolated lactic acid bacteria based on two dimensional correlation networks - Chunsheng Li; Qiaoyan Cui; Laihao Li; Hui Huang; Shengjun Chen; Yongqiang Zhao; Yueqi Wang (Food Chemistry, 2024)

Synergistic effects of microbial transglutaminase and apple pectin on the gelation properties of pea protein isolate and its application to probiotic encapsulation - Kangning Wang; Hui Sun; Zhihan Cui; Jiahui Wang; Jiayi Hou; Fuping Lu; Yihan Liu (Food Chemistry, 2024)

A new comprehensive quantitative index for the assessment of essential amino acid quality in beef using Vis-NIR hyperspectral imaging combined with LSTM - Fujia Dong; Yongzhao Bi; Jie Hao; Sijia Liu; Weiguo Yi; Wenjie Yu; Yu Lv; Jiarui Cui; Hui Li; Jinhua Xian; Sichun Chen; Songlei Wang (Food Chemistry, 2024)

DEHP induces apoptosis and autophagy of the thyroid via Rap1 signaling pathway: In vivo and in vitro study - Xu Li; Honghao Qian; Hui Ye; Haotang Zhao; Jianwei Cui; Xiaoqi Fang; Zhili Ge; Jingjing Shi; Wen Qi; Lin Ye (Food and Chemical Toxicology, 2024)

Response of TCE biodegradation to elevated H2 and O2: Implication for electrokinetic-enhanced bioremediation - Weiwei Ouyang; Yao Huang; Cui Li; Chen Xue; Minghui Liu; Jie Ma; Songhu Yuan; Hui Liu (Environmental Research, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

In situ confined growth of Cu2-xSe nanoparticles in highly defective nitrogen-doped carbon for high-rate sodium-ion battery anodes - Hui Peng; Wenxing Miao; Shuzhen Cui; Zhiyuan Liu; Xin Wang; Bo Tao; Wenbo Hou; Zhe Zhang; Guofu Ma (Chemical Engineering Journal, 2024)

Carboxymethyl chitosan-based hydrogel-Janus nanofiber scaffolds with unidirectional storage-drainage of biofluid for accelerating full-thickness wound healing - Xinhao Chen; Hui Huang; Xinru Song; Ting Dong; Jiafei Yu; Jieyan Xu; Rui Cheng; Tingting Cui; Jun Li (Carbohydrate Polymers, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Sublethal acetamiprid affects reproduction, development and disrupts gene expression in Binodoxys communis - Likang Zhao; Hui Xue; Punniyakotti Elumalai; Xiangzhen Zhu; Li Wang; Kaixin Zhang; Dongyang Li; Jichao Ji; Junyu Luo; Jinjie Cui; Xueke Gao (Environmental Science and Pollution Research, 2024)

New butanolide derivatives from the marine derived fungus Aspergillus terreus GZU-31-1 by chemical epigenetic manipulation - Yuwei Zhou; Xiaocong Chen; Yuqian Tang; Yena Liu; Zhongxiang Zhao; Hui Cui (Natural Product Research, 2024)

Many-objective evolutionary algorithm based on parallel distance for handling irregular Pareto fronts - Zichen Wei; Hui Wang; Shuai Wang; Zhixia Zhang; Zhihua Cui; Feng Wang; Hu Peng; Jia Zhao (Swarm and Evolutionary Computation, 2024)

Fe(II)-catalyzed phase transformation of Cd(II)-bearing ferrihydrite-kaolinite associations under anoxic conditions: New insights to role of kaolinite and fate of Cd(II) - Cong Wu; Shuai Wang; Wei Peng; Hui Yin; Weijun Zhou; Wenjuan Liao; Hao-Jie Cui (Journal of Hazardous Materials, 2024)

Machine-learning-assisted hydrogen adsorption descriptor design for bilayer MXenes - Weizhi Tian; Gongchang Ren; Yuanting Wu; Sen Lu; Yuan Huan; Tiren Peng; Peng Liu; Jiangong Sun; Hui Su; Hong Cui (Journal of Cleaner Production, 2024)

Hydration characteristics of steel slag in the presence of diethanol-isopropanolamine - Lei Chang; Jianfeng Wang; Suping Cui; Yali Wang; Hui Liu; Tianrui Pei; Ziqiang Li (Journal of Cleaner Production, 2024)

Evolution of the Neo-Tethys traced by Late Triassic to Early Cretaceous marine remnants in the eastern segment of the Yarlung-Tsangpo suture zone, southern Tibet - Zhihao He; Xin Li; Yalin Li; Atsushi Matsuoka; Hui Luo; Xiaohui Cui; Jianbo Cheng (Journal of Asian Earth Sciences, 2024)

Mechanism study on the inhibitory effect of strawberry (Fragaria×ananassa Duch.) leaves on advanced glycation end-products formation - Xiyun Sun; Baoyue Cui; Kexin Zheng; Yu Zhang; Xuening An; Yujie Nie; Zhi Song; Zhongxia Li; Kuniyoshi Shimizu; Bin Li; Hui Tan (Food Bioscience, 2024)

Efficient Cu-Co Dual-Site promotes selective catalytic oxidation of ammonia over cobalt based catalysts - Hongchun Sun; Hui Wang; Cui Dong; Zhenping Qu (Chemical Engineering Journal, 2024)

Jurassic integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Jianguo Li; Xin Rao; Lin Mu; Xiaohui Cui; Xin Li; Hui Luo; Peixue Liu (Science China Earth Sciences, 2024)

Surfeit Locus Protein 4 as a Novel Target for Therapeutic Intervention in Cerebral Ischemia–Reperfusion Injury - Wenjie Hu; Xiangyi Kong; Yu Cui; Hui Wang; Jingchen Gao; Xiyuran Wang; Shujun Chen; Xiaohua Li; Shifang Li; Fengyuan Che; Qi Wan (Molecular Neurobiology, 2024)

Toxic Effects of Atrazine on Liver and Underlying Mechanism: A Review - Honghao Qian; Haotang Zhao; Hui Ye; Jianwei Cui; Xiaoqi Fang; Yuezhu Zhang; Lin Ye (Exposure and Health, 2024)

Metal element-based adsorbents for phosphorus capture: Chaperone effect, performance and mechanism - Xin Sheng; Shengnan Chen; Zhiwei Zhao; Li Li; Yuanpeng Zou; Hui Shi; Penghui Shao; Liming Yang; Jingsheng Wu; Yaofu Tan; Xinyuan Lai; Xubiao Luo; et al. (Chemosphere, 2024)

Meroterpenoids from the marine-derived fungus Aspergillus terreus GZU-31-1 exerts anti-liver fibrosis effects by targeting the Nrf2 signaling in vitro - Hui Cui; Yuqian Tang; Chunfang Yang; Huimei Deng; Lei Chen; Xueying Fan; Liping Zhu; Yena Liu; Zhongxiang Zhao; Tao Su (Phytochemistry, 2024)

Scouring development and self-burial of a subsea pipeline attached with porous/flexible spoilers - Bo Zhou; Jie Wang; Xiaohui Cui; Chaodong Hu; Hui Liu; Xikun Wang (Ocean Engineering, 2024)

The role of fungi in the formation and instability of halophilic aerobic granular sludge in a continuous flow reactor - Hui-Kai Liang; You-Wei Cui; Jin-Lei Yan; Hui-Juan Yan; Zhen-Ying Li; Yu-Bo Cui (Journal of Water Process Engineering, 2024)

Endophytic Enterobacter sp. YG-14 mediated arsenic mobilization through siderophore and its role in enhancing phytostabilization - Jiawei Chen; Xuan Zhang; Min Kuang; Kunpeng Cui; Ting Xu; Xuanming Liu; Rui Zhuo; Ziwei Qin; Zhigang Bu; Zhongliang Huang; Hui Li; Jing Huang; et al. (Journal of Hazardous Materials, 2024)

Predicting and analyzing the algal population dynamics of a grass-type lake with explainable machine learning - Hao Cui; Yiwen Tao; Jian Li; Jinhui Zhang; Hui Xiao; Russell Milne (Journal of Environmental Management, 2024)

Fundamentals and application in phytoremediation of an efficient arsenate reducing bacterium Pseudomonas putida ARS1 - Ze-Wen Wang; Guang Yang; Jian Chen; Yaoyu Zhou; Avelino Núñez Delgado; Hui-Ling Cui; Gui-Lan Duan; Barry P. Rosen; Yong-Guan Zhu (Journal of Environmental Sciences, 2024)

Mucous cell histopathology and label-free quantitative proteomic analysis of skin mucus in fat greenling (Hexagrammos otakii) infected with Vibrio harveyi - Xiaoyan Wei; Yanyan Shi; Shuai Wang; Hui Liu; Zheng Zhang; Lina Yu; Wenyuan Hua; Dandan Cui; Yan Chen; Xuejie Li; Wei Wang (Fish & Shellfish Immunology, 2024)

Enhanced removal of Cd2+ from water by a bacterioferritin from Candidatus Kuenenia stuttgartiensis within engineering bacteria - Jin Wang; Cui-Zhong Chen; Yi-Cheng Wang; Hui-Min Fu; Peng Yan; You-Peng Chen (Chemical Engineering Journal, 2024)

Enhanced hydroisomerization of n-heptane over bifunctional catalysts with highly dispersed Pd nanoparticles supported on H-Yβ composite zeolite - Yu-Hong Kang; Xiao-Qi Zhang; Juan Gao; Guang-Hui Liu; Yan-Jun Li; Yong Gao; Jin-Jun Bai; Ai-Min Wang; Xian-Yong Wei; Cui-Ying Lu (Chemical Engineering Journal, 2024)

A multifunctional interface optimization strategy for efficient Quasi-2D blue perovskite Light-Emitting diodes - Yuliang Ye; Zhou Cui; Zunxian Yang; Zhiwei Zeng; Zongyi Meng; Hongyi Hong; Songwei Ye; Zhiming Cheng; Qianting Lan; Jiaxiang Wang; Ye Chen; Hui Zhang; et al. (Chemical Engineering Journal, 2024)

Moment Tensor and Stress Field Inversions of Mining-Induced Seismicity in A Thick-Hard Roof Zone - Chun-Hui Song; Cai-Ping Lu; Hai-Quan Liu; Jie-Fang Song; Cheng-Yu Liu; Hua-Wei Cui; Jin-Rui Zhang (Rock Mechanics and Rock Engineering, 2024)

Newcastle disease virus suppresses antigen presentation via inhibiting IL-12 expression in dendritic cells - Fulong Nan; Wenlong Nan; Xin Yan; Hui Wang; Shasha Jiang; Shuyun Zhang; Zhongjie Yu; Xianjuan Zhang; Fengjun Liu; Jun Li; Xiaoqiong Zhou; Delei Niu; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Gut bacterial community and gene expression alterations induced by transgenic Bt maize contribute to insecticidal activity against Mythimna separata - Chao Xu; Junyu Luo; Li Wang; Xiangzhen Zhu; Hui Xue; Ningbo Huangfu; Xueke Gao; Dongyang Li; Kaixin Zhang; Ran Chen; Jichao Ji; Changying Niu; et al. (Journal of Pest Science, 2024)

Spatial distribution, source identification, and transportation paths of plutonium in the Beibu Gulf, South China Sea - Yong-jing Guan; Hua He; Kai-di Fan; Shen-zhen Wang; Zi-chen Guo; Hui-juan Wang; Liang-jia Cui; Wu Chen; Chun-ping Huang; Zhi-yong Liu; Xian-wen He; Kai-xing Guo; et al. (Marine Pollution Bulletin, 2024)

Testate amoebae (Protozoa) in lakes of the Qinghai-Tibet Plateau: Biodiversity, community structures, and protozoic biosilicification in relation to environmental properties and climate warming - Yangmin Qin; Anatoly Bobrov; Daniel Puppe; Hui Li; Baiying Man; Jing Gong; Jie Wang; Yongde Cui; Yansheng Gu; Ulrike Herzschuh; Shucheng Xie (Science of The Total Environment, 2024)

Synthesis and antifungal activity of 2,4-dihydroxy-5-methylphenyl ethanone derivatives against phytopathogenic fungi in vitro - Lin Jia; Cui-Ping Zhang; Yi Zhu; Chun-Yan Zhao; Zeng-Hui Han; Dong-Bao Hu; Wei Shi (Phytochemistry Letters, 2024)

Insights into the effects of steaming on organoleptic quality of salmon (Salmo salar) integrating multi-omics analysis and electronic sensory system - Meng Dong; Feng Liang; Shuang Cui; Bing-Bing Mao; Xu-Hui Huang; Lei Qin (Food Chemistry, 2024)

Beneficial effects of short-term exposure to indoor biophilic environments on psychophysiological health: Evidence from electrophysiological activity and salivary metabolomics - Zhaoming Li; Wenzhu Zhang; Jingxian Cui; Hui Liu; Hong Liu (Environmental Research, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

Mechanochemical synthesis of Ni/MgO dual functional materials at room temperature for CO2 capture and methanation - Zhan-Kuo Guo; Su Gao; Shu-Xiang Xiang; Jin-Peng Wang; Guo-Cui Mao; Hui-Lin Jiang; Bao-Xia Dong; Yun-Lei Teng (Chemical Engineering Journal, 2024)

Molecular engineering of poly(ionic liquid)-based random copolymer electrolytes for enhanced performance of solid-state lithium batteries - Hui Chang; Weiya Li; Haojing Liu; Hongkai Hu; Wei Liu; Yongcheng Jin; Guanglei Cui (Chemical Engineering Journal, 2024)

Biophilic environment with visual-olfactory stimuli contributes to psychophysiological restoration and cognitive enhancement - Zhaoming Li; Wenzhu Zhang; Jingxian Cui; Lingshan Wang; Hui Liu; Hong Liu (Building and Environment, 2024)

A Fault Diagnosis Method for Marine Engine Cross Working Conditions Based on Transfer Learning - Longde Wang; Hui Cao; Zhichao Cui; Zeren Ai (Journal of Marine Science and Engineering, 2024)
Marine engines confront challenges of varying working conditions and intricate failures. Existing studies have primarily concentrated on fault diagnosis in a single condition, overlooking the adaptability of these methods in diverse working condition. To address the aforementioned issues, we propose a cross working condition fault diagnosis method named the Balanced Adaptation Domain Weighted Adversarial Network (BADWAN). This method combines transfer learning to tackle the challenges of cross working condition diagnosis with limited labels. Specifically tailored for scenarios with incomplete labeling in the target working conditions, we designed an Enhanced Centroid Balance scheme to balance the label space, thereby enhancing the model’s transfer capabilities. Additionally, we designed an Instance Affinity Weighting scheme on the foundation of Class-level Weighting, refining the model to the instance level for effective information interaction. Furthermore, we incorporated the Adaptive Uncertainty Suppression strategy to further boost the model’s classification prowess. Two experimental scenarios were designed to demonstrate the effectiveness of the proposed model using a Wärtsilä9L34DF dual-fuel engine as an experimental subject. The results demonstrate an over 90% diagnostic accuracy in scenarios with complete target working condition labels and 86% accuracy in scenarios with incomplete labels, outperforming other transfer learning models. The BADWAN model excels in cross-condition fault diagnosis tasks for marine engines with incomplete target working condition labels, offering a novel solution to this field.

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

ATR induces hepatic lipid metabolism disorder in rats by activating IRE1α/XBP1 signaling pathway - Honghao Qian; Yaming Zhao; Yiming Wang; Haotang Zhao; Jianwei Cui; Ziyu Wang; Hui Ye; Xiaoqi Fang; Zhili Ge; Yuezhu Zhang; Lin Ye (Toxicology, 2024)

Impacts of electric field-magnetic powder coupled membrane bioreactor on phenol wastewater treatment: Performance, synergistic mechanism, antibiotic resistance genes, and eco-environmental benefit evaluation - Bei Jiang; Qianzhi Zeng; Qiangwei Liu; Huiying Chai; Jinxun Xiang; Hongxin Li; Shengnan Shi; Aifu Yang; Zhaobo Chen; Yubo Cui; Dongxue Hu; Hui Ge; et al. (Science of The Total Environment, 2024)

Biogeographic distribution, assembly processes and potential nutrient cycling functions of myxobacteria communities in typical agricultural soils in China - Wei Dai; Yang Liu; Dandan Yao; Ning Wang; Jinpeng Shao; Xianfeng Ye; Zhongli Cui; Hao Zong; Lei Tian; XiuZhai Chen; Hui Wang (Science of The Total Environment, 2024)

Polyethylene upcycling to aromatics by pulse pressurized catalytic pyrolysis - Linyao Ke; Qiuhao Wu; Nan Zhou; Hui Li; Qi Zhang; Xian Cui; Liangliang Fan; Yuhuan Liu; Kirk Cobb; Roger Ruan; Yunpu Wang (Journal of Hazardous Materials, 2024)

The central Qiangtang Metamorphic Belt in northern Tibet is an in-situ Paleo-Tethys Ocean: Evidence from newly discovered Late Devonian radiolarians - Xin Li; Noritoshi Suzuki; Yi-chun Zhang; Hua Zhang; Mao Luo; Dong-xun Yuan; Quan-feng Zheng; Wen-kun Qie; Qi Ju; Feng Qiao; Hai-peng Xu; Xiao-hui Cui (Gondwana Research, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Structure evolution of porous alumina during aging process and its support effect on PtSn/Al2O3 catalyzed propane dehydrogenation - Haowei Wang; Wen-Cui Li; Xinqian Gao; Shuzhen Zhou; Yu Zhang; Fan Wu; An-Hui Lu (Chemical Engineering Journal, 2024)

Transpiration-mimicking wood-based microfluidic aluminum-air batteries: Green power sources for miniaturized applications - Wei Wang; Liu-Liu Shen; Peiran Wu; Hui Yu; Jiansong Wang; Yipu Xu; Xiangzun Dong; Xuanxuan Cui; Gui-Rong Zhang; Donghai Mei (Chemical Engineering Journal, 2024)

A light-responsive poly(urethane-urea) actuator with room temperature self-healing performance - Zhishuai Cui; Xiaolei Yue; Yucheng Wang; Yujie Zhang; Zhi-Hui Ren; Zheng-Hui Guan (Chemical Engineering Journal, 2024)

Introducing back-surface field for efficient inverted CsPbI3 perovskite solar cells - Chunyan Lu; Xiaodong Li; Haobo Yuan; Wenxiao Zhang; Xuemin Guo; Acan Liu; Hui Yang; Wen Li; Zhengbo Cui; YuYang Hu; Junfeng Fang (Chemical Engineering Journal, 2024)

Taurine promotes insulin synthesis by enhancing Isl-1 expression through miR-7a/RAF1/ERK1/2 pathway - Hui Liu; Tongjuan Niu; Guobin Qiu; Sheng Cui; Di Zhang (In Vitro Cellular & Developmental Biology - Animal, 2024)

Estimating Spatiotemporal Fishing Effort of Trawlers with Vessel-Monitoring System Data: A Case Study of the Sea Area of the Bohai Sea and the Yellow Sea, China - Dan Li; Feng Lu; Shuo Xu; Huiyuan Liu; Muhan Xue; Guohui Cui; Zhenhua Ma; Hui Fang; Yu Wang (Journal of Marine Science and Engineering, 2023)
Measuring the distribution of the fishing effort of trawlers is of great significance for describing marine fishery activities, quantifying fishing systems in terms of marine ecological pressure, and revising the regulations of fishing. The purpose of this paper is to develop an efficient learning algorithm to detect the fishing behavior of trawlers to analyze the distribution of fishing effort. The vessel-monitoring system data of more than 4600 trawlers from September 2019 to April 2023 were used for feature extraction. According to the spatiotemporal information provided by the vessel position data, 11-dimensional features were extracted to form the feature vectors. A Slime Mould Algorithm-optimized Light Gradient-Boosting Machine (SMA-LightGBM) algorithm was proposed to classify the feature vectors to recognize fishing behavior. The presented method showed a remarkable generalization ability and high accuracy, sensitivity, specificity, and Matthews correlation coefficient in the test results, with scores of 98.23%, 98.75%, 97.75%, and 0.9646, respectively. Subsequently, the trained model was used to identify the fishing behavior of trawlers belonging to the coastal provinces of the Bohai Sea and the Yellow Sea in the sea area of 117° E~132° E, 26° N~41° N. The fishing effort was calculated and evaluated according to the fishing behavior recognition results. The mean absolute error was 0.3031 kW·h, and the coefficient of determination score was 0.9772. The thermal map of the fishing effort of the trawler was mapped, and the spatiotemporal characteristics were estimated in the region of interest from 2019 to 2023 with a spatial resolution of 18 degree × 18 degree. This method is an efficient way of analyzing the spatiotemporal characteristics of the fishing effort of trawlers. It provides a quantitative basis for the assessment of fishery resources and can inform fishing policies.

Hydrodynamic Interactions between Ships in a Fleet - Zhengyuan Liu; Changming Dai; Xiaohui Cui; Yu Wang; Hui Liu; Bo Zhou (Journal of Marine Science and Engineering, 2023)
There has always been a concern about the hydrodynamic interaction between ships in a flow field. In this study, the RANS method is utilized, and the hydrodynamic interference between two KRISO Container Ships (KCS) operating in still water with identical parameters and sailing at the same speed is investigated. Overlapping grids are used to simulate ship motion, and the VOF method is used to simulate the free surface. A KCS ship model of 1:1 size without propeller is used in the study. In order to study the change principle of the Kelvin flow field created by a single ship, the resistance coefficient and the flow field surrounding the ship are first calculated for the monohull case. Then the influence of interference between two ships is examined at various speeds and intervals and compared with the monohull case. It is discovered that the resistance coefficient of the following ship is reduced in a certain speed interval under the influence of the leading ship, where the maximum reduction can be up to 24.3%. The reason for this phenomenon may be that the wave around the following ship is superimposed on the transverse wave behind the leading ship. When the height of the wave is suppressed, the following ship’s resistance is reduced.

Rationally designed calcium carbonate multifunctional trap for contaminants adsorption - Xin Sheng; Shengnan Chen; Zhiwei Zhao; Li Li; Yuanpeng Zou; Hui Shi; Penghui Shao; Liming Yang; Jingsheng Wu; Yaofu Tan; Xinyuan Lai; Xubiao Luo; et al. (Science of The Total Environment, 2023)

Soil aggregate-driven changes in nutrient redistribution and microbial communities after 10-year organic fertilization - Hu Cui; Hui Zhu; Brian Shutes; Alain N. Rousseau; Wei-Dong Feng; Sheng-Nan Hou; Yang Ou; Bai-Xing Yan (Journal of Environmental Management, 2023)

Geothermal field model in the southeast of Shijiazhuang Region (China) deduced from magnetotelluric data - Gang Wang; Hui Cao; Du Xiao; Wenguo Wang; Wei Zhu; Dayong Wang; Yimin She; Aiming Cui; Gege Zhang (Journal of Applied Geophysics, 2023)

Fabrication of zwitterionic magnetic microporous organic network for efficient extraction of fluoroquinolone antibiotics from meat samples - Xu-Hui Li; Yuan-Yuan Cui; Xun Wu; Abdukader Abdukayum; Cheng-Xiong Yang (Food Chemistry, 2023)

Wood frame structured carbons with integrated sieving layer for propylene/propane separation - Cheng-Tong Wang; Wen-Cui Li; Shuang Xu; Ru-Shuai Liu; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

5-HT4 Receptor is Protective for MPTP-induced Parkinson’s Disease Mice Via Altering Gastrointestinal Motility or Gut Microbiota - Chun Cui; Yun Shi; Hui Hong; Yu Zhou; Chenmeng Qiao; Liping Zhao; Xuebing Jia; Weijiang Zhao; Yanqin Shen (Journal of Neuroimmune Pharmacology, 2023)

Prediction of Rice Yield Based on Multi-Source Data and Hybrid LSSVM Algorithms in China - Long Zhao; Shunhao Qing; Fei Wang; Hui Wang; Hao Ma; Yi Shi; Ningbo Cui (International Journal of Plant Production, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Gas production prediction using AM-BiLSTM model optimized by Whale Optimization Algorithm - Lei Qiao; Hui-Cui Xin; Zhi-Min Xu; Kun Xiao (Applied Geophysics, 2023)

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

Amino acids as methyl donors for the formation of N,N-dimethylpiperidinium (mepiquat) in model systems and cooked mushrooms - Xuenan Li; Bin Liu; Hui Liu; Tianyang Xing; Congcong Cui; Haiyang Yan; Yuan Yuan (Food Chemistry, 2023)

Spatiotemporal response of water quality in fragmented mangroves to anthropogenic activities and recommendations for restoration - Yang Cui; Jianwei Dong; Hongbing Wang; Meiqi Shang; Hui Xie; Yongfen Du; Yufeng Li; Yang Wang (Environmental Research, 2023)

Functional separator with 1 T/2H-MoSe2 nanosheets decorated nitrogen and sulfur co-doped mesoporous hollow carbon spheres for high-performance Li-S batteries - Qidong Sheng; Hui Liu; Yaning Liu; Bo Jin; Mengyang Cui; Yiyang Li; Nan Gao; Xingyou Lang; Qing Jiang (Chemical Engineering Journal, 2023)

Flexible regulation of persulfate activation mechanisms through tuning Cu valence in CuBTC-derived copper oxide catalysts for improved pollutant degradation - Mei-Mei Wang; Yun-Ke Cui; Jia-Tai Wen; Yan-Shan Wang; Meng-Hui Jia; Shu-Zhen He; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Bimetallic alloy Fe Co1-PS3 with boosted lithium reaction kinetics for lithium-ion batteries - Hou-Yang Zhong; Yun Chai; Xian Lu; Pei-Wen Huang; Bi-Cui Chen; Ke-Zhao Du; Xiao-Hui Wu (Chemical Engineering Journal, 2023)

tDCS Regulates ASBT-3-OxoLCA-PLOD2-PTEN Signaling Pathway to Confer Neuroprotection Following Rat Cerebral Ischemia-Reperfusion Injury - Xiangyi Kong; Xujin Yao; Jinyang Ren; Jingchen Gao; Yu Cui; Jiangdong Sun; Xiangyu Xu; Wenjie Hu; Hui Wang; Huanting Li; Oleg O. Glebov; Fengyuan Che; et al. (Molecular Neurobiology, 2023)

FeCa-based layered double hydroxide, a high-performance phosphorus adsorbent in constructed wetlands and ecological dams - A pilot scale study - Wei-Dong Feng; Hu Cui; Hui Zhu; Brian Shutes; Bai-Xing Yan; Sheng-Nan Hou (Chemosphere, 2023)

Association of N, N-diethyl-m-toluamide (DEET) with hyperuricemia among adult participants - Runmiao Wu; Xu Zhu; Yujie Xing; Gongchang Guan; Yong Zhang; Rutai Hui; Qianwei Cui; Zhongwei Liu; Ling Zhu (Chemosphere, 2023)

Single particle tracking reveals SARS-CoV-2 regulating and utilizing dynamic filopodia for viral invasion - Yue Zhang; Xiaowei Zhang; Zhongyi Li; Weisong Zhao; Hui Yang; Shuangshuang Zhao; Daijiao Tang; Qian Zhang; Zonghong Li; Huisheng Liu; Haoyu Li; Bo Li; et al. (Science Bulletin, 2023)

Bioactive ellagitannins and phenylpropanoid glycosides from the seed of Torreya grandis - Xue-Hui Wang; Xiao-Jing Shao; Yi-Ran Jiang; Tian-Tian Bei; Wen-Hui Xu; Bo-Wen Ren; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Experimental study on Diels-Alder addition of conjugated dienes directly from cracking C5 fraction by continuous micro-channel reactors - Zehao Jing; Tingting Ge; Hui Guo; Yuchao Li; Zhou Li; Cuncun Zuo; Ming Wang; Haofei Huang; Lin Guo; Guangjun Cui (Fuel, 2023)

Responses of soil biochemical and microbial properties to vegetation combinations of quarry restoration strategies in mountainous areas in China - Hui Han; Hong Yao; Cui-lan Wei; Jianjun Ma (Ecological Engineering, 2023)

Regulating solvation structure and inducing Zn (0 0 2) plane by a multifunctional electrolyte additive toward dendrite suppression and long-life zinc ion hybrid capacitors - Hui Peng; Xin Wang; Fan Yang; Zhiyuan Liu; Haikuo Lei; Shuzhen Cui; Xuan Xie; Guofu Ma (Chemical Engineering Journal, 2023)

Numerical simulation on high-temperature supercritical CO2/gaseous H2O mixture flowing over a single reactive spherical char particle - Kun Jiang; Chao Fan; Cui Wang; Qiuyang Zhao; Hui Jin (Chemical Engineering Journal, 2023)

Brain amyloid-β deposition associated functional connectivity changes of ultra-large structural scale in mild cognitive impairment - Liang Cui; Zhen Zhang; Yan-Lu Huang; Fang Xie; Yi-Hui Guan; Chun-Yi Zac Lo; Yi-Han Guo; Jie-Hui Jiang; Qi-Hao Guo (Brain Imaging and Behavior, 2023)

Genomic characterization of three bacteriophages infecting donkey-derived Escherichia coli - Jia-Qi Cui; Wen-Hua Liu; Can Zhang; Ling Zou; Hui-Ying Ren (Virus Genes, 2023)

Rapid and sensitive determination of free fatty acids based on in-source microdroplet-driven derivatization coupled with high-resolution mass spectrometry - Jiaqi Cui; Jianxun Zhang; Shihao Sun; Wu Fan; Hui Xi; Xiujuan Xu; Lingbo Ji; Shusheng Zhang; Dingzhong Wang; Wuduo Zhao (Analytica Chimica Acta, 2023)

Genipin protects against acute liver injury by abrogating ferroptosis via modification of GPX4 and ALOX15-launched lipid peroxidation in mice - Xiaofei Fan; Xiaoyu Wang; Yangyang Hui; Tianming Zhao; Lihong Mao; Binxin Cui; Weilong Zhong; Chao Sun (Apoptosis, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Shaking table tests and numerical studies on the seismic behaviors of FPB in railway continuous beam bridges - Qiming Qi; Changjiang Shao; Haomeng Cui; Hui Huang; Wang Wei; Chunyang Wang; Weilin Zhuang (Engineering Structures, 2023)

Dual-modal artificial synapse based on a lead-free halide Cu2AgBiI6 for image processing and information encryption - Shuaifei Mao; Mingqing Cui; Sheng Jiang; Pengfei Zhao; Jie Lao; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Jadranka Travas-sejdic; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2023)

Ultra-high output hybrid nanogenerator for self-powered smart mariculture monitoring and warning system - Liqiang Liu; Jun Li; Zhengxin Guan; Leilei Zhao; Zhiyu Tian; Shouchuang Jia; Hongxin Hong; Zeyu He; Haiyang Wen; Ruiyuan Huang; Hui Cui; Wei Ou-Yang; et al. (Chemical Engineering Journal, 2023)

Study on pre-concentration of trace heavy metal ions in water quality detection using FO-electroosmotic integrated chip - Zhao Cui; Meng Zhang; Yang Yuan; Hui Jia; Huu Hao Ngo; Jie Wang (Chemical Engineering Journal, 2023)

Gas-heat-electricity poly-generation system based on solar-driven supercritical water gasification of waste plastics - Bingru Lu; Weizuo Wang; Cui Wang; Wenwen Wei; Hui Jin (Chemical Engineering Journal, 2023)

Orally Induced High Serum Level of Trimethylamine N-oxide Worsened Glial Reaction and Neuroinflammation on MPTP-Induced Acute Parkinson’s Disease Model Mice - Chen-Meng Qiao; Wei Quan; Yu Zhou; Gu-Yu Niu; Hui Hong; Jian Wu; Li-Ping Zhao; Ting Li; Chun Cui; Wei-Jiang Zhao; Yan-Qin Shen (Molecular Neurobiology, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

The composition characteristics of endophytic communities and their relationship with metabolites profile in Ephedra sinica under wild and cultivated conditions - Hui Zhang; Ye Xia; Jin-Long Cui; Xin Ji; Shuang-Man Miao; Gang Zhang; Yi-Min Li (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Microcystin-leucine-arginine impairs bone microstructure and biomechanics by activating osteoimmune response and inhibiting osteoblasts maturation in developing rats - Yao Tan; Zhiqun Qiu; Hui Zeng; Jiaohua Luo; Lingqiao Wang; Jia Wang; Ke Cui; Guowei Zhang; Yi Zeng; Huidong Jin; Xiaoling Chen; Yujing Huang; et al. (Toxicology, 2023)

Risk assessment of predatory lady beetle Propylea japonica's multi-generational exposure to three non-insecticidal agrochemicals - Guofeng Chang; Hui Xue; Jichao Ji; Li Wang; Xiangzhen Zhu; Kaixin Zhang; Dongyang Li; Xueke Gao; Lin Niu; Mengxue Gao; Junyu Luo; Jinjie Cui (Science of The Total Environment, 2023)

Layered double hydroxides, an effective nanomaterial to remove phosphorus from wastewater: Performance, mechanism, factors and reusability - Weidong Feng; Hu Cui; Hui Zhu; Brian Shutes; Baixing Yan; Shengnan Hou (Science of The Total Environment, 2023)

Variable drivers of surface turbulence under condition of stratified density currents in a tributary bay of Three Gorges Reservoir - Lianghong Long; Hui Xu; Meng Yan; Xia Yang; Xingxing Zhao; Daobin Ji; Yujie Cui; Zhongyong Yang; Defu Liu; Zhengjian Yang (Journal of Hydrology, 2023)

Plasmon Ag/CuInS2/BiVO4 core-shell decahedral S-scheme heterojunction superstructures for robust photocatalytic performance - Hui Peng; Zipeng Xing; Weifeng Kong; Chunxu Wu; Bin Fang; Yongqian Cui; Zhenzi Li; Haixia Liu; Wei Zhou (Fuel, 2023)

Static magnetic field increases aerobic nitrogen removal from hypersaline wastewater in activated sludge with coexistence of fungi and bacteria - Jun Chen; You-Wei Cui; Mei-Qi Huang; Hui-Juan Yan; Dong Li (Bioresource Technology, 2023)

High Arterial Oxygen Saturation in the Acclimatized Lowlanders Living at High Altitude - Yaoxi He; Chaoying Cui; Yongbo Guo; Wangshan Zheng; Tian Yue; Hui Zhang; Ouzhuluobu; Tianyi Wu; Xuebin Qi; Bing Su (Phenomics, 2023)

Short-term exposure to enrofloxacin causes hepatic metabolism disorder associated with intestinal flora dysbiosis in adult marine medaka (Oryzias melastigma) - Meiru Wang; Yifan Qin; Yifan Liu; Hui Yang; Jun Wang; Shaoguo Ru; Pengfei Cui (Marine Pollution Bulletin, 2023)

Enhancing simultaneous nitrate and phosphate removal in sulfur‑iron (II) autotrophic denitrification biofilters by endogenous magnetic fields: Performance and mechanism - Shi-Cai Han; You-Wei Cui; Hui-Juan Yan; Yu-Bo Cui; Zhao-Bo Chen (Journal of Water Process Engineering, 2023)

Surfactant-induced intervention in interfacial polymerization to develop highly-selective thin-film composite membrane for forward osmosis process - Xuan Zhang; Hui-Min Cui; Yu Gao; Zhi-Wei Yan; Xi Yan; Yan Chen; Xiao-Jing Guo; Wan-Zhong Lang (Desalination, 2023)

Channel aggradation triggered by dam failure amplifies the damage of outburst flood - Dingzhu Liu; Yifei Cui; Wen Jin; Hao Wang; Hui Tang (Landslides, 2023)

Associations of Multiple Serum Trace Elements with Abnormal Sleep Duration Patterns in Hospitalized Patient with Cirrhosis - Yangyang Hui; Gaoyue Guo; Lihong Mao; Yifan Li; Mingyu Sun; Xiaoyu Wang; Wanting Yang; Xiaofei Fan; Kui Jiang; Binxin Cui; Chao Sun (Biological Trace Element Research, 2023)

High-throughput and specific detection of microorganisms by intelligent modular fluorescent photoelectric microbe detector - Qian Cui; Shanqun Gan; Yongjie Zhong; Hui Yang; Yi Wan; Yong Zuo; Hao Yang; Mengjia Li; Shurui Zhang; Masoud Negahdary; Yunuo Zhang (Analytica Chimica Acta, 2023)

Mode of innovative green production for concrete engineering: life cycle assessment of accelerators prepared from aluminum mud wastes - Xiao Liu; Hui Xie; Qifeng Luo; Kun Yang; Chunlei Xia; Jianan Guan; Wu Zhou; Boxue Sun; Ziming Wang; Suping Cui (Environmental Science and Pollution Research, 2023)

Long-term exposure to arsenic in drinking water leads to myocardial damage by oxidative stress and reduction in NO - Yi-Xin Cui; Lu Dong; Meng Zhang; Yi-Nan Liu; Yong-Hui Chen; Ming-Zhao Jia; Kun-Pan Chen; Hui Wang; Ya-Wen Shi; Tian-You Ma; Jing-Hong Chen (Toxicology, 2023)

Identification and synergetic mechanism of TCE, H2 and O2 metabolic microorganisms in the joint H2/O2 system - Cui Li; Chen Xue; Weiwei Ouyang; Minghui Liu; Yingtao Sun; Hui Liu (Science of The Total Environment, 2023)

Characteristics and emissions of isoprene and other non-methane hydrocarbons in the Northwest Pacific Ocean and responses to atmospheric aerosol deposition - Ying-Cui Wu; Xu-Xu Gao; Hong-Hai Zhang; Yong-Zheng Liu; Jian Wang; Feng Xu; Gui-Ling Zhang; Zhao-Hui Chen (Science of The Total Environment, 2023)

The BrAFP1 promoter drives gene-specific expression in leaves and stems of winter rapeseed (Brassica rapa L.) under cold induction - Xiaoyun Dong; Zigang Liu; Jiaping Wei; Guoqiang Zheng; Hui Li; Ying Wang; Haiyan Tian; Junmei Cui; Zefeng Wu; Xiaodong Cao; Chunmei Xu (Plant Science, 2023)

Three new sesquilignans from the stems of Eleutherococcus senticosus and their bioactivities - Yue Zhang; Yi-Ming Zhao; Xiao-Jing Shao; Xue-Hui Wang; Tian-Tian Bei; Yi-Ran Jiang; Wen-Hui Xu; Hyun-Sun Lee; Meng-Xue Xiu; Jian Song; Long Cui (Phytochemistry Letters, 2023)

Incorporation of hydrogen into zircon through multi-coupling mechanisms and its geochemical implications - Zexian Cui; Xiao-Ping Xia; Christopher J. Spencer; Hejiu Hui; Qing Yang; Wan-Feng Zhang; Le Zhang; Yongjiang Xu; Jian Xu; Chun-Kit Lai; Yanqiang Zhang (Lithos, 2023)

Mechanism of reactive co-transport of Fe2+ and antibiotics in hyporheic zone simulated by quartz sand column - Cui Gan; Zhaobo Luo; Chengyuan Su; Lei Tong; Hui Liu (Journal of Hydrology, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

A new insight into the potential drivers of antibiotic resistance gene enrichment in the collembolan gut association with antibiotic and non-antibiotic agents - Yi-Fei Wang; Tian-Gui Cai; Zhe-Lun Liu; Hui-Ling Cui; Dong Zhu; Min Qiao (Journal of Hazardous Materials, 2023)

Facile synthesis of nitrogen-doped porous graphene for efficient adsorption of tetracycline: Behavior and mechanism - Hui Wang; Liang Shan; Wen Shi; Ming Wang; Guixiang Quan; Zourui Wang; Liqiang Cui; Jinlong Yan (Journal of Environmental Chemical Engineering, 2023)

Enzyme-responsive microneedle patch for bacterial infection and accelerated healing of diabetic wounds - Shizhou Wu; Boquan Qin; Xiaofang Tang; Ting Cui; Shijiu Yin; Hongxian Dong; Yunjie Liu; Shu Deng; Hui Zhang; Guoying Feng; Huiqi Xie; Lei Lei (Chemical Engineering Journal, 2023)

Warming-driven indirect effects on alpine grasslands: short-term gravel encroachment rapidly reshapes community structure and reduces community stability - Gao-Lin Wu; Hui Fang; Zeng Cui; Jingxue Zhao (Oecologia, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

Design and simulation experiment of ridge planting strawberry picking manipulator - Yaohui Zhang; Kailiang Zhang; Li Yang; Dongxing Zhang; Tao Cui; Yang Yu; Hui Liu (Computers and Electronics in Agriculture, 2023)

Phylogenetic diversity of stochasticity-dominated predatory myxobacterial community drives multi-nutrient cycling in typical farmland soils - Wei Dai; Yang Liu; Dandan Yao; Ning Wang; Xianfeng Ye; Zhongli Cui; Hui Wang (Science of The Total Environment, 2023)

Early Cretaceous monsoonal upwelling along the northern margin of the Gondwana continent: Evidence from radiolarian cherts - Xiaohui Cui; Xin Li; Jonathan C. Aitchison; Hui Luo (Marine Micropaleontology, 2023)

Nitrogen in soil, manure and sewage has become a major challenge in controlling nitrate pollution in groundwater around plateau lakes, Southwest China - Rongyang Cui; Dan Zhang; Wanli Hu; Xinmei Zhao; Hui Yan; Gangcai Liu; Anqiang Chen (Journal of Hydrology, 2023)

Improving the biodegradation of chicken feathers by a Bacillus licheniformis ZSZ6 mutant and application of hydrolysate - Chunhong Cui; Liqiong Sun; Xuelian Chen; Yu Zhu; Zhi Zheng; Dongmei Mao; Mingxu Li; Yuxin Li; Yajun Cao; Bing Feng; Hui Wang; Lin Wang; et al. (International Biodeterioration & Biodegradation, 2023)

Mechanism of loud sound in a powerhouse during operation of a hydropower station based on microseismic monitoring - Yuhang Guo; Chuanqing Zhang; Xiaoshun Li; Yang Gao; Guojian Cui; Hui Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Positive contribution of predatory bacterial community to multiple nutrient cycling and microbial network complexity in arsenic-contaminated soils - Wei Dai; Mingqing Liu; Ning Wang; Xianfeng Ye; Yang Liu; Dandan Yao; Lei Wang; Zhongli Cui; Peirui Yan; Chunxiao Cheng; Zhonglin Huang; Hui Wang (Applied Soil Ecology, 2023)

Laboratory investigation into curing temperature on the mechanical characteristics of cement mortar serving in rock bolting system - Guojian Cui; Chuanqing Zhang; Lingyu Li; Hui Zhou; Luosong Zhang; Qiming Xie (Arabian Journal of Geosciences, 2023)

3D-crumpled graphitic carbon nitride achieving promoted visible-light-driven molecular oxygen activation for phenol degradation - Hui Zhang; Chengwen Wang; Lei Li; Jiaxin Zhang; Jinbo Zhao; Tao Sun; Baoshan Cui (Chemosphere, 2023)

Characterization of imidacloprid-induced hepatotoxicity and its mechanisms based on a metabolomic approach in Xenopus laevis - Xia Zhou; Renyue Ming; Meiting Guo; Hui Jiao; Honghao Cui; Deyu Hu; Ping Lu (Science of The Total Environment, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Design and climbing control of an underwater robot for ship hull cleaning - Lepeng Chen; Rongxin Cui; Weisheng Yan; Hui Xu; Haiyan Zhao; Haoquan Li (Ocean Engineering, 2023)

“Two-in-one” dual-function luminescent MOF hydrogel for onsite ultra-sensitive detection and efficient enrichment of radioactive uranium in water - An-Qi Cui; Xiao-Yi Wu; Jun-Bin Ye; Gang Song; Di-Yun Chen; Jie Xu; Yu Liu; Jia-Ping Lai; Hui Sun (Journal of Hazardous Materials, 2023)

Effects of L-lysine and L-arginine on the structure and gel properties of konjac glucomannan - Xinlian Su; Wei Cui; Zhi Zhang; Jing Zhang; Hui Zhou; Kai Zhou; Yujuan Xu; Zhaoming Wang; Baocai Xu (Food Hydrocolloids, 2023)

The interaction mechanism and the functionality of yeast protein with hydrophilic and hydrophobic bioactive molecules - Haili Sun; Yifei Sun; Xin Tang; Yuanmeng Cui; Demei Meng; Yuyu Zhang; Ku Li; Hui Guo; Hai Chen; Rui Yang (Food Bioscience, 2023)

Wastewater treatment performance and gaseous emissions in MFC-CWs affected by influent C/N ratios - Tingting Niu; Hui Zhu; Brian Shutes; Jing Yu; Chunguang He; Shengnan Hou; Hu Cui; Baixing Yan (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Chinese young people’s perceptions and preferences with regard to various edible urban plants - Wenzhu Zhang; Zhaoming Li; Jingxian Cui; Lingshan Wang; Hui Liu; Hong Liu (Journal of Zhejiang University-SCIENCE B, 2023)

Shifts in the sources and fates of nitrate in shallow groundwater caused by agricultural intensification intensity: Revealed by hydrochemistry, stable isotopic composition and source contribution - Rongyang Cui; Dan Zhang; Hongyuan Wang; Bin Fu; Hui Yan; Wanli Hu; Gangcai Liu; Anqiang Chen (Agriculture, Ecosystems & Environment, 2023)

Selenium treatment promotes anthocyanin accumulation in radish sprouts (Raphanus sativus L.) by its regulation of photosynthesis and sucrose transport - Jiahui Chen; Hui Chen; Haixia Wang; Junyi Zhan; Xingxing Yuan; Jin Cui; Nana Su (Food Research International, 2023)

pH-responsive chitosan-based film containing oregano essential oil and black rice bran anthocyanin for preserving pork and monitoring freshness - Yuanpeng Hao; Jiamu Kang; Xiaoqi Guo; Meiyu Sun; Hui Li; Hongtong Bai; Hongxia Cui; Lei Shi (Food Chemistry, 2023)

SecReT6 update: a comprehensive resource of bacterial Type VI Secretion Systems - Jianfeng Zhang; Jiahao Guan; Meng Wang; Gang Li; Marko Djordjevic; Cui Tai; Hui Wang; Zixin Deng; Zhaoyan Chen; Hong-Yu Ou (Science China Life Sciences, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

Visible-light-driven iron-based heterogeneous photo-Fenton catalysts for wastewater decontamination: A review of recent advances - Qiangshun Wu; Muhammad Saboor Siddique; Huijuan Wang; Liqiang Cui; Hui Wang; Mei Pan; Jinlong Yan (Chemosphere, 2023)

Drivers of aboveground biomass shift with forest stratum in temperate forest of North China - Qinyuan Zhang; Qing Zhang; Yinuo Zhai; Wenjun Yang; Yan Zhang; Hongxiang Liu; Kun Zhang; Xiao Liu; Kening Cui; Hui Wang; Peiming Zheng; Renqing Wang (Science of The Total Environment, 2023)

Novel biocompatible and sensitive visual sensor based on aggregation-induced emission for on-site detection of radioactive uranium in water and live cell imaging - Xiao-Yi Wu; An-Qi Cui; Jun-Bin Ye; Gang Song; Yan-Ni Wu; Yue-Xi Wu; Jia-Ping Lai; Hui Sun (Science of The Total Environment, 2023)

Adaptation of bacterial community in maize rhizosphere for enhancing dissipation of phthalic acid esters in agricultural soil - Yu-Hong Huang; Yu-Jie Yang; Xiaolian Wu; Cui-Lan Zhu; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2023)

Microbiological analysis and characterization of Salmonella and ciprofloxacin-resistant Escherichia coli isolates recovered from retail fresh vegetables in Shaanxi Province, China - Chenyang Cao; Wenxing Zhao; Zexun Lü; Yixin Mo; Wei Hu; Shengyuan Sun; Huabin Cheng; Jiaqi Ma; Sirui Xiong; Xiaorong Jin; Hui Yang; Li Bai; et al. (International Journal of Food Microbiology, 2023)

Development and validation of single-step microwave-assisted digestion method for determining heavy metals in aquatic products: Health risk assessment - Yong Min Lao; Cui Lan Qu; Bing Zhang; Hui Jin (Food Chemistry, 2023)

Three birds with one stone: Design and synthesis of polyurethane actuator for executing heat, light and humidity triggered deformation - Xiaolei Yue; Chen Dong; Yucheng Wang; Zhishuai Cui; Zhihui Ren; Zheng-Hui Guan (Chemical Engineering Journal, 2023)

A universal strategy for preparing tough and smart glassy hydrogels - Xinxing Lin; Xiaolin Wang; Hongyuan Cui; Gangfeng Ouyang; Hui Guo (Chemical Engineering Journal, 2023)

Intracellularly-photosensitized bio-hybrid with biogenic quantum dots for enhanced wastewater denitrification - Shuo Cui; Yang Si; Xian-Zhong Fu; Hui-Hui Li; Xue-Meng Wang; Wen-Zheng Du; Lang Teng; Ru-Li He; Hou-Qi Liu; Ruquan Ye; Wen-Wei Li (Chemical Engineering Journal, 2023)

Constructing robust cathode/Li interfaces and intensifying ion transport kinetics for PEO-based solid-state lithium-sulfur batteries - Jin Li; Haitao Zhang; Yingyue Cui; Haoran Da; Hui Wu; Yingjun Cai; Suojiang Zhang (Chemical Engineering Journal, 2023)

Experimental microwave-assisted air gasification of biomass in fluidized bed reactor - Wenming Fu; Yaning Zhang; Longfei Cui; Hui Liu; Tarique Maqsood (Bioresource Technology, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Human platelet mitochondria improve the mitochondrial and cardiac function of donor heart - Zhi Jun Lin; Soomin Kim; Hui Xing Cui; Kyuboem Han; Hong Kyu Lee; Chun-Hyung Kim; Young Cheol Kang; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Responses of bacterial communities to microplastics: More sensitive in less fertile soils - Peiyan Qin; Tao Li; Zhaowen Cui; Hui Zhang; Xiao Hu; Gehong Wei; Chun Chen (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Experimental study on treatment of mixed ion exchange resins by supercritical water gasification - Le Wang; Jia Chen; Jinhua Cui; Gaoyun Wang; Hui Jin; Liejin Guo (Journal of Cleaner Production, 2023)

Study on two microchannel coolers with different coupling mechanisms of distributed J-T effect and heat transfer - Zhihao Chang; Xiaoyu Cui; Hailong She; Hui Geng (International Journal of Refrigeration, 2023)

Discrimination of the harvesting season of green tea by alcohol/salt-based aqueous two-phase systems combined with chemometric analysis - Xiao-Hua Zhang; Hui-Na Cui; Jing-Jing Zheng; Xiang-Dong Qing; Kai-Long Yang; Ya-Qian Zhang; Lu-Meng Ren; Le-Yuan Pan; Xiao-Li Yin (Food Research International, 2023)

Determination of bacterial toxin toxoflavin and fervenulin in food and identification of their degradation products - Hui Wang; Lili Hu; Xiaotu Chang; Yuge Hu; Yan Zhang; Peng Zhou; Xiaojiao Cui (Food Chemistry, 2023)

Biochemical, histopathological and untargeted metabolomic analyses reveal hepatotoxic mechanism of acetamiprid to Xenopus laevis - Hui Jiao; Tingting Yuan; Xiaohuan Wang; Xia Zhou; Renyue Ming; Honghao Cui; Deyu Hu; Ping Lu (Environmental Pollution, 2023)

Insight into a strategy to improve charge carrier migration in lead-free bismuth-based halide perovskite for efficient selective oxidation of thioanisole under visible light - Zihao Cui; Yaqiang Wu; Shuhui Zhang; Hui Fu; Guoqiang Chen; Zaizhu Lou; Xiaolei Liu; Qianqian Zhang; Zeyan Wang; Zhaoke Zheng; Hefeng Cheng; Yuanyuan Liu; et al. (Chemical Engineering Journal, 2023)

Engineering noble-metal-free metal–organic framework composite catalyst for efficient CO2 conversion under ambient conditions - Hui-Ya Cui; Ya-Xin Zhang; Chun-Shuai Cao; Tian-Ding Hu; Zhi-Lei Wu (Chemical Engineering Journal, 2023)

Screening of new Paenibacillus polymyxa S3 and its disease resistance of grass carp ( Ctenopharyngodon idellus ) - Shijia Yang; Duo Jin; Hui Li; Lingzhi Jiang; Jun Cui; Weitao Huang; Jie Rang; YunLong Li; Liqiu Xia (Journal of Fish Diseases, 2023)
A new strain of Paenibacillus polymyxa S3 with antagonistic effects on 11 major fish pathogens (especially Aeromonas hydrophila ), but had no toxicity to grass carp, was screened from the sediment of fishponds. In vivo colonization studies showed that strain S3 could be colonized and distributed in the gill and abdomen of the grass carp. Bioassay results showed that the weight growth rate of grass carp in the strain S3 oral group (16.01%) and strain S3 immersion group (16.44%) was significantly higher than those of the control group (8.61%). At the same time, the activities of ACP, AKP, CAT and GSH‐Px in the serum of grass carp in oral and immersion groups were significantly higher than those of the control group. In addition, the treatment with strain S3 could significantly upregulate the expression of the antioxidant‐related genes and immune‐related genes Keap1 , Nrf2 , C3 , LZM , IgM , TLR‐4 and MyD‐88 in grass carp tissues. The challenge test showed that strain S3 treatment significantly increased the survival rate of grass carp infected with Aeromonas hydrophila . Whole genome sequencing analysis showed that strain S3 had 16 active metabolite gene clusters, indicating that it had abundant gene resources, which provided important support for its development for fish microecological preparations. In summary, a new strain of Paenibacillus polymyxa S3 with antibacterial activity against a variety of fish pathogens was screened in this study and its probiotic function was evaluated, proving its potential value in fisheries.

Terpenoids and other secondary metabolites produced by the Eutypella fungi and their bioactivities - Yuwei Zhou; Jingxin He; Hui Cui (Frontiers in Marine Science, 2022)
The fungi Eutypella could metabolize a myriad of natural products with unique structures and diverse bioactivities, which were deemed as key sources for lead compounds in drug discovery. Since the first research on the genus Eutypella in 2009, a myriad of secondary metabolites including terpenoids, alkaloids, and polyketides have been discovered in this genus, and most of them exhibited significant pharmacological activities. However, there are no systematic reviews that reported about the structures and bioactivities of Eutypella up to now. In this review, a total of 153 secondary metabolites and 42 references have been systematically summarized, and we found that the terpenoids (68.09%) and alkaloids (19.15%) were the new main components of this fungi, and the primary antiproliferative activity (64.89%) was mainly derived from the terpenoids and alkaloids. Thus, this review about the chemical diversity and biological activities of the metabolites from the fungus Eutypella provided a new perspective for the development of new drugs for pharmacologists.

Digs out and characterization of the resistance gene accountable to soybean mosaic virus in soybean (Glycine max (L.) Merrill) - Tongtong Jin; Adhimoolam Karthikeyan; Liqun Wang; Tingxuan Zong; Tao Wang; Jinlong Yin; Ting Hu; Yunhua Yang; Hui Liu; Yongchun Cui; Tuanjie Zhao; Haijian Zhi (Theoretical and Applied Genetics, 2022)

Increasing soil heterogeneity strengthens the inhibition of a native woody plant by an invasive congener - Yi Hu; Zhen-Wei Xu; Ming-Yan Li; Jordan R. Croy; Zhong-Yi Zhang; Hai-Mei Li; Wei-Hua Guo; Xiao-Lei Jiang; Hui-Cui Lu; Xiao Guo (Plant and Soil, 2022)

Using short-interval landslide inventories to build short-term and overall spatial prediction models for earthquake-triggered landslides based on machine learning for the 2018 Lombok earthquake sequence - Changhu Xue; Kejie Chen; Hui Tang; Chaoqi Lin; Wenfeng Cui (Natural Hazards, 2022)

Transcranial Direct-Current Stimulation Regulates MCT1-PPA-PTEN-LONP1 Signaling to Confer Neuroprotection After Rat Cerebral Ischemia–Reperfusion Injury - Xiangyi Kong; Wenjie Hu; Yu Cui; Jingchen Gao; Xujin Yao; Jinyang Ren; Tao Lin; Jiangdong Sun; Yunyi Gao; Xiaohua Li; Hui Wang; Huanting Li; et al. (Molecular Neurobiology, 2022)
Propionic acid (PPA) is a critical metabolite involved in microbial fermentation, which functions to reduce fat production, inhibit inflammation, and reduce serum cholesterol levels. The role of PPA in the context of cerebral ischemia–reperfusion (I/R) injury has yet to be clarified. Increasing evidence indicate that transcranial direct-current stimulation (tDCS) is a safe approach that confers neuroprotection in cerebral ischemia injury. Here, we show that the levels of PPA were reduced in the ischemic brain following a rat cerebral I/R injury and in the cultured rat cortical neurons after oxygen–glucose deprivation (OGD), an in vitro model of ischemic injury. We found that the decreased levels of transporter protein monocarboxylate transporter-1 (MCT1) were responsible for the OGD-induced reduction of PPA. Supplementing PPA reduced ischemia-induced neuronal death after I/R. Moreover, our results revealed that the neuroprotective effect of PPA is mediated through downregulation of phosphatase PTEN and subsequent upregulation of Lon protease 1 (LONP1). We demonstrated that direct-current stimulation (DCS) increased MCT1 expression and PPA level in OGD-insulted neurons, while tDCS decreased the brain infarct volume in the MCAO rats via increasing the levels of MCT1 expression and PPA. This study supports a potential application of tDCS in ischemic stroke.

Coastline extraction based on multi-scale segmentation and multi-level inheritance classification - Sheng Hui; Guo Mengliang; Gan Yuliang; Xu Mingming; Liu Shanwei; Muhammad Yasir; Cui Jianyong; Wan Jianhua (Frontiers in Marine Science, 2022)
Detailed management of the coastline is critical to the development of coastal states. However, the current classification of the coastline is relatively weak. This study proposed an automatic method to detect coastlines with category attributes based on multi-scale segmentation and multi-level inheritance classification. Fully integrating the advantages of multi-scale segmentation and multi-level classification, it solved the problems that traditional methods could not solve, such as extracting coastlines with categorical attributes, cultivation ponds that are easily affected by tidal flats, and complex coastal terrain. The Chinese GF-2 satellite images are used to extract various types of coastlines in Jiaozhou Bay and its surrounding areas such as the harbor-wharf coastline, silt coastline, pond coastline, rocky coastline, and sandy coastline. Compared with the human interpretation, it is found that the coastline extracted by our proposed method is different by 10.104 km in the harbor-wharf coastline, 0.099 km in the silt coastline, 2.677 km in the pond coastline, 8.831 km in the rocky coastline, and 0.218 km in the sandy coastline. Furthermore, compared to the object-based region growing integrating edge detection (OBRGIE) method, it is increased by 13.52%, 2.16%, 14.48%, 52.57%, and 22.97%, respectively. The results show that our proposed method is algorithmically more reasonable, accurate, and powerful. It can provide data support for refined coastline management.

Dynamics of extracellular polymeric substances and soil organic carbon with mangrove zonation along a continuous tidal gradient - Dong-Xi Liu; Zhi-Mao Mai; Cui-Ci Sun; Yan-Wu Zhou; Hui-Huang Liao; You-Shao Wang; Hao Cheng (Frontiers in Marine Science, 2022)
The importance of mangroves in blue carbon storage has been widely reported. However, the potential contribution of microbial extracellular polymeric substances (EPS) to the carbon pool is still poorly understood in mangrove ecosystems. Thus, a natural mangrove reserve located in Gaoqiao was chosen to investigate the linkage between microbial EPS and sediment organic carbon. Sequential resin extraction, Fourier transform infrared spectroscopy (FTIR), and 16S high-throughput sequencing were employed to determine the variations in EPS and bacterial taxa in different mangrove communities. Both EPS and EPS-C increased significantly with mangrove zonation from seaward to landward, irrespective of the EPS subfractions (colloidal and bound EPS) and components (extracellular protein and polysaccharide). Moreover, both EPS and EPS-C were found to be positively correlated with soil organic carbon. The present data further showed that EPS-C accounted for 1.84~10.69% of TOC in surface sediments. Multiple functional groups (e.g., O-H, N-H, and C=O), which may provide ligands for particle adsorption and complexation, were identified by FTIR. Consistent with the ascend of EPS with mangrove zonation from seaward to landward, the highest transmittance intensity for all functional groups was consistently exhibited in EPS isolated from landward Rhizophoraceae forest. In addition, the present data also indicated an interesting positive linkage between EPS and the abundance of some specific bacterial taxa, such as Rhizobiales, Corynebacteriales, and Gaiellales. In summary, this study claims the importance of EPS in the carbon pool in mangrove ecosystems. The present study may provide a better understanding of the functions of mangroves in carbon stocks.

Alterations in gut microbiota and metabolites associated with altitude-induced cardiac hypertrophy in rats during hypobaric hypoxia challenge - Zhiyuan Pan; Yichen Hu; Zongyu Huang; Ni Han; Yan Li; Xiaomei Zhuang; Jiye Yin; Hui Peng; Quansheng Gao; Wenpeng Zhang; Yong Huang; Yujun Cui; et al. (Science China Life Sciences, 2022)

Evidence for preserved insulin responsiveness in the aging rat brain - Matthew G. Engel; Jeremy Smith; Kai Mao; Gabriela Farias Quipildor; Min-Hui Cui; Maria Gulinello; Craig A. Branch; Samuel E. Gandy; Derek M. Huffman (GeroScience, 2022)
Insulin appears to exert salutary effects in the central nervous system (CNS). Thus, brain insulin resistance has been proposed to play a role in brain aging and dementia but is conceptually complex and unlikely to fit classic definitions established in peripheral tissues. Thus, we sought to characterize brain insulin responsiveness in young (4–5 months) and old (24 months) FBN male rats using a diverse set of assays to determine the extent to which insulin effects in the CNS are impaired with age. When performing hyperinsulinemic-euglycemic clamps in rats, intracerebroventricular (ICV) infusion of insulin in old animals improved peripheral insulin sensitivity by nearly two-fold over old controls and comparable to young rats, suggesting preservation of this insulin-triggered response in aging per se ( p < 0.05). We next used an imaging-based approach by comparing ICV vehicle versus insulin and performed resting state functional magnetic resonance imaging (rs-fMRI) to evaluate age- and insulin-related changes in network connectivity within the default mode network. In aging, lower connectivity between the mesial temporal (MT) region and other areas, as well as reduced MT signal complexity, was observed in old rats, which correlated with greater cognitive deficits in old. Despite these stark differences, ICV insulin failed to elicit any significant alteration to the BOLD signal in young rats, while a significant deviation of the BOLD signal was observed in older animals, characterized by augmentation in regions of the septal nucleus and hypothalamus, and reduction in thalamus and nucleus accumbens. In contrast, ex vivo stimulation of hippocampus with 10 nM insulin revealed increased Akt activation in young ( p < 0.05), but not old rats. Despite similar circulating levels of insulin and IGF-1, cerebrospinal fluid concentrations of these ligands were reduced with age. Thus, these data highlight the complexity of capturing brain insulin action and demonstrate preserved or heightened brain responses to insulin with age, despite dampened canonical signaling, thereby suggesting impaired CNS input of these ligands may be a feature of reduced brain insulin action, providing further rationale for CNS replacement strategies.

Network pharmacology approach and molecular docking to explore the potential mechanism of Wu-Wei-Wen-Tong Chubi capsules in rheumatoid arthritis - Xiaoya Cui; Jian Liu; Lili Zhang; Xiaoli Wang; Xiaochuang Liu; Hui Jiang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Development and Validation of a Diagnostic Nomogram to Predict the Anthracycline-Induced Early Cardiotoxicity in Children with Hematological Tumors - Zhi-yuan Liu; Yun-gong Wang; Xiao-bi Huang; Xiao-hui Qi; Cui-ping Qian; Sheng Zhao (Cardiovascular Toxicology, 2022)
This study aimed to establish and validate an effective nomogram to predict the risk of cardiotoxicity in children after each anthracycline treatment. According to the inclusion and exclusion criteria, the eligible children were randomly divided into the training cohort (75%) and the validation cohort (25%). Least absolute shrinkage and selection operator (LASSO) regression was used to select the predictors and a nomogram was developed. Then, concordance index ( C -index), the area under the curve (AUC), Hosmer–Lemeshow (H–L) test, and decision curve analysis (DCA) were employed to evaluate the performance and clinical utility of nomogram. Internal validation was processed to inspect the stability of the model. A total of 796 eligible children were included in this study and divided into a training set ( n = 597) and a validation set ( n = 199). LASSO regression analysis revealed that cumulative anthracycline dose, ejection fractions, NT-proBNP, and diastolic dysfunction were effective predictors of cardiotoxicity. The nomogram was established based on these variables. The C -index and the AUC of the predicting nomogram were 0.818 in the training cohort and 0.773 in the validation cohort, suggesting that the nomogram had good discrimination. The calibration curve of the nomogram presented no significant deviation from the reference line, and the P -value of the H–L test was 0.283, implying a preferable degree of calibration. The threshold of DCA also reflects that the nomogram is clinically useful. A nomogram was developed to predict anthracycline chemotherapy-induced cardiotoxicity in children with hematological tumors. The nomogram has a good prediction effect and can provide a reference for clinicians’ diagnosis and treatment.

Altered effective connectivity within the cingulo-frontal-parietal cognitive attention networks in chronic low back pain: a dynamic causal modeling study - Cui Ping Mao; Hua Juan Yang; Qiu Juan Zhang; Quan Xin Yang; Xiao Hui Li (Brain Imaging and Behavior, 2022)

Combined technologies for the remediation of soils contaminated by organic pollutants. A review - Wukui Zheng; Tian Cui; Hui Li (Environmental Chemistry Letters, 2022)

Spatial distribution of saline (salinization) frozen soil in the Qinghai-Tibet Engineering Corridor - Shanshan Zhang; Hui Peng; Yuanhong Dong; Xiaosa Yuan; Long Jin; Yunhu Shang; Fuqing Cui (Arabian Journal of Geosciences, 2022)

Estuarine Ichthyoplankton Studies – A Review - Hui Zhang; Yibang Wang; Cui Liang; Shude Liu; Weiwei Xian (Frontiers in Marine Science, 2022)
Estuaries are nutrient-rich environments with a gradient of fresh to salt water. They support high primary productivity and an abundance of zooplankton. Estuaries are used by many fish as nursery grounds because their environmental conditions provide abundant food for larval and adult fish. Ichthyoplankton, which comprise fish eggs and larvae, are important for the recruitment of fish species. At present, there are no systematic reviews on ichthyoplankton in estuaries from a global perspective. Here, research on ichthyoplankton over the last 60 years (1951–2022) was reviewed, focusing on three aspects: evaluation of ichthyoplankton published studies, community structure, and factors affecting community structure. The results show that research on estuarine ichthyoplankton has increased, from less than 1 article per year in the 1950s to more than 30 articles per year in the 2020s. The keyword used most commonly was ‘community structure’ and ‘dynamics’ and the word used most recently was ‘climate change’. Regarding the geographical distribution of the studies carried out on estuarine ichthyoplankton, USA had the most (32.9% of all studies), followed by Australia (8.1%), South Africa (6.1%), Brazil (5.6%), Japan (5.1%), China (4.9%), Canada (4.8%), and Portugal (4.8%). Salinity and turbidity were the main factors affecting the ichthyoplankton community structure in estuaries. Climate change indirectly affected the community structure of estuarine ichthyoplankton by changing the spawning time, spawning location, and hatching time of species. The movement of spawning sites poleward and the advance of spawning time showed a consistent trend. In addition, the development of DNA barcoding techniques will be a useful supplement to traditional taxonomic methods for identifying ichthyoplankton and will provide new opportunities for the development of systematic taxonomy in this field. Our review contributes to a broader understanding of estuarine ichthyoplankton and provides theoretical support for estuarine environmental protection and the sustainable use of estuarine fishery resources.

Influence of Microroughness on Stick–Slip Characteristics of Fault Under Constant Normal Stiffness - Zhang Chuanqing; Xu Jie; Jin Shengji; Li Xiaoshun; Cui Guojian; Guo Yuhang; Meng Fanzhen; Zhou Hui; Yan Shangyuan (Rock Mechanics and Rock Engineering, 2022)

Effects of PHD and HSP90 on erythropoietin production in yak (Bos grunniens) renal interstitial fibroblast-like cells under hypoxia - Yan Cui; Hui Li; Si-Jiu Yu; Seth Yaw Afedo; Xue-Feng Bai (Journal of Molecular Histology, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Norovirus detection in wastewater and its correlation with human gastroenteritis: a systematic review and meta-analysis - Yue Huang; Nan Zhou; Shihan Zhang; Youqin Yi; Ying Han; Minqi Liu; Yue Han; Naiyang Shi; Liuqing Yang; Qiang Wang; Tingting Cui; Hui Jin (Environmental Science and Pollution Research, 2022)

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

Ectopic expression of GmRNF1a encoding a soybean E3 ubiquitin ligase affects Arabidopsis silique development and dehiscence - Zhongyi Yang; Yingjun Chi; Yanmei Cui; Zhen Wang; Dezhou Hu; Hui Yang; Javaid Akhter Bhat; Hui Wang; Guizhen Kan; Deyue Yu; Fang Huang (Planta, 2022)

Sanxicun landslide: an investigation of progressive failure of a gentle bedding slope - Xiangjun Pei; Shenghua Cui; Ling Zhu; Hui Wang; Luguang Luo; Xiaochao Zhang (Natural Hazards, 2022)

Seasonality and Sex-Biased Fluctuation of Birth Weight in Tibetan Populations - Yaoxi He; Jun Li; Tian Yue; Wangshan Zheng; Yongbo Guo; Hui Zhang; Li Chen; Chunxia Li; Hongyan Li; Chaoying Cui; Ouzhuluobu; Xuebin Qi; et al. (Phenomics, 2022)

Rapid visual detection of porcine reproductive and respiratory syndrome virus via recombinase polymerase amplification combined with a lateral flow dipstick - Xiao-Xiao Tian; Tao Wang; Xing-Yang Cui; Xin-Yi Huang; Yue Sun; Da-Song Xia; Yong-Bo Yang; Xue-Hui Cai; Tong-Qing An (Archives of Virology, 2022)

Comparative transcriptome analysis in three sorghum ( Sorghum bicolor ) cultivars reveal genomic basis of differential seed quality - Wei Zhou; Yaxing Zhou; Zhenguo Wang; Yan Li; Hui Liu; Fengjuan Cui; Shoujun Xu; Zhensheng Shi (Plant Biosystems, 2022)

Spring Ichthyoplankton Assemblage Structure in the Yangtze Estuary Under Environmental Factors - Yibang Wang; Cui Liang; Zhaomin Chen; Shude Liu; Hui Zhang; Weiwei Xian (Frontiers in Marine Science, 2021)
Estuaries, where fresh and salty water converge, provide abundant nutrients for ichthyoplankton. Ichthyoplankton, including fish eggs, larvae, and juveniles, are important fishery recruitment resources. The Yangtze Estuary and its adjacent waters comprise a typical large-scale estuary and supply many important fish spawning, feeding, and breeding areas. In this study, 1,291 ichthyoplankton individuals were collected in the Yangtze Estuary in spring, from 2013 to 2020. The aims of the study were to provide detailed information on characteristics of the ichthyoplankton assemblage, explore interannual variation, and evaluate the effects of environmental variables on the temporal variation in assemblage structure. Twenty-six species in seventeen families were identified. The dominant species were Coilia mystus , Chelidonichthys spinosus , Engraulis japonicus , Hypoatherina valenciennei , Larimichthys polyactis , Salanx ariakensis , Stolephorus commersonnii , and Trachidermus fasciatus . The ichthyoplankton assemblage changed significantly over time, and Chelidonichthys spinosus became one of the dominant species. Canonical correspondence analysis showed that temperature and chlorophyll a were the key factors affecting the assemblage structure in the Yangtze Estuary in spring.

Correction to: AGGF1 protects from myocardial ischemia/reperfusion injury by regulating myocardial apoptosis and angiogenesis - Yu Liu; Hui Yang; Lina Song; Nan Li; Qiu-Yue Han; Cui Tian; Erhe Gao; Jie Du; Yun-Long Xia; Hui-Hua Li (Apoptosis, 2021)

Phenolic glycosides and flavonoids with antioxidant and anticancer activities from Desmodium caudatum - Qian-Nan Xu; Dan Zhu; Guang-Hui Wang; Ting Lin; Cui-Ling Sun; Rong Ding; Wen-Jing Tian; Hai-Feng Chen (Natural Product Research, 2021)

Dammarane-type saponins from Gynostemma pentaphyllum and their cytotoxicities - Wei-Ye Cui; Yulian Jin; Hui Liu; Ma-Li Zu; Xin-Fang Zhai; Ce Yang; Yu-Long Gu; Yong Cheng; Xiang-Lan Piao (Natural Product Research, 2021)

Overexpression of SMC4 predicts a poor prognosis in cervical cancer and facilitates cancer cell malignancy phenotype by activating NF-κB pathway - Hui He; Cui Zheng; Yunxian Tang (Human Cell, 2021)

A new ergostane derivative from the leaves of Heynea trijuga Roxburgh - Shou-Bai Liu; Zheng Cui; Hui-Qin Chen; Hao Wang; Wen-Hua Dong; Cai-Hong Cai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Function identification of miR394 in tomato resistance to Phytophthora infestans - Yuan-Yuan Zhang; Yu-Hui Hong; Ya-Rong Liu; Jun Cui; Yu-Shi Luan (Plant Cell Reports, 2021)

Pseudotime Ordering Single-Cell Transcriptomic of β Cells Pancreatic Islets in Health and Type 2 Diabetes - Kaixuan Bao; Zhicheng Cui; Hui Wang; Hui Xiao; Ting Li; Xingxing Kong; Tiemin Liu (Phenomics, 2021)

Field test research on post-grouting effect for super-long cast-in-place bored pile in thick soft foundation - Yun-liang Cui; Chang-guang Qi; Jin-hui Zheng; Xin-quan Wang; Shi-min Zhang (Geotechnical and Geological Engineering, 2021)

MicroRNA-7a inhibits Isl1 expression to regulate insulin secretion by targeting Raf1 and Mapkap1 in NIT-1 cells - Hui Liu; Di Zhang; Yewen Zhou; Sheng Cui (In Vitro Cellular & Developmental Biology - Animal, 2021)

Complex analysis of the personalized pharmacotherapy in the management of COVID-19 patients and suggestions for applications of predictive, preventive, and personalized medicine attitude - Lei-Yun Wang; Jia-Jia Cui; Qian-Ying OuYang; Yan Zhan; Yi-Min Wang; Xiang-Yang Xu; Lu-Lu Yu; Hui Yin; Yang Wang; Chen-Hui Luo; Cheng-Xian Guo; Ji-Ye Yin (EPMA Journal, 2021)
Aims Coronavirus disease 2019 (COVID-19) is rapidly spreading worldwide. Drug therapy is one of the major treatments, but contradictory results of clinical trials have been reported among different individuals. Furthermore, comprehensive analysis of personalized pharmacotherapy is still lacking. In this study, analyses were performed on 47 well-characterized COVID-19 drugs used in the personalized treatment of COVID-19. Methods Clinical trials with published results of drugs use for COVID-19 treatment were collected to evaluate drug efficacy. Drug-to-Drug Interactions (DDIs) were summarized and classified. Functional variations in actionable pharmacogenes were collected and systematically analysed. “Gene Score” and “Drug Score” were defined and calculated to systematically analyse ethnicity-based genetic differences, which are important for the safer use of COVID-19 drugs. Results Our results indicated that four antiviral agents (ritonavir, darunavir, daclatasvir and sofosbuvir) and three immune regulators (budesonide, colchicine and prednisone) as well as heparin and enalapril could generate the highest number of DDIs with common concomitantly utilized drugs. Eight drugs (ritonavir, daclatasvir, sofosbuvir, ribavirin, interferon alpha-2b, chloroquine, hydroxychloroquine (HCQ) and ceftriaxone had actionable pharmacogenomics (PGx) biomarkers among all ethnic groups. Fourteen drugs (ritonavir, daclatasvir, prednisone, dexamethasone, ribavirin, HCQ, ceftriaxone, zinc, interferon beta-1a, remdesivir, levofloxacin, lopinavir, human immunoglobulin G and losartan) showed significantly different pharmacogenomic characteristics in relation to the ethnic origin of the patient. Conclusion We recommend that particularly for patients with comorbidities to avoid serious DDIs, the predictive, preventive, and personalized medicine (PPPM, 3 PM) strategies have to be applied for COVID-19 treatment, and genetic tests should be performed for drugs with actionable pharmacogenes, especially in some ethnic groups with a higher frequency of functional variations, as our analysis showed. We also suggest that drugs associated with higher ethnic genetic differences should be given priority in future pharmacogenetic studies for COVID-19 management. To facilitate translation of our results into clinical practice, an approach conform with PPPM/3 PM principles was suggested. In summary, the proposed PPPM/3 PM attitude should be obligatory considered for the overall COVID-19 management.

Influence of mountain-valley morphology on in-situ stress distribution - Chuan-qing Zhang; Guo-jian Cui; Hui Zhou; Fan-jie Yang; Jing-jing Lu (Journal of Mountain Science, 2021)

Biocontrol mechanism of Myxococcus fulvus B25-I-3 against Phytophthora infestans and its control efficiency on potato late blight - Zhi Hua Wu; Qiang Ma; Zhi Ning Sun; Hai Chen Cui; Hui Rong Liu (Folia Microbiologica, 2021)

Three new 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones and one new dimeric 2-(2-phenylethyl)chromone from agarwood of Aquilaria crassna Pierre ex Lecomte in Laos - Yang-Mei Zhao; Li Yang; Fan-Dong Kong; Wen-Hua Dong; Wei Li; Hui-Qin Chen; Hao Wang; Cai-Hong Cai; Cui-Juan Gai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Identification and phylogenetic analysis of five Crataegus species (Rosaceae) based on complete chloroplast genomes - Liwei Wu; Yingxian Cui; Qing Wang; Zhichao Xu; Yu Wang; Yulin Lin; Jingyuan Song; Hui Yao (Planta, 2021)

Fusarium solani G6, a novel vitexin-producing endophytic fungus: characterization, yield improvement and osteoblastic proliferation activity - Pei-jia Tang; Zhi-hui Zhang; Li-li Niu; Cheng-bo Gu; Wen-yi Zheng; Hai-chao Cui; Xiao-han Yuan (Biotechnology Letters, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

Seismic signal characteristics and interpretation of the 2020 “6.17” Danba landslide dam failure hazard chain process - Yan Yan; Yifei Cui; Dingzhu Liu; Hui Tang; Yongjian Li; Xin Tian; Lei Zhang; Sheng Hu (Landslides, 2021)

Distinct roles of alternative oxidase pathway during the greening process of etiolated algae - Ying Liu; Hua Zhang; Yan Cui; Yanli Zheng; Hui Chen; Zhangli Hu; Qingyu Wu (Science China Life Sciences, 2021)

Spatial prediction of soil calcium carbonate content based on Bayesian maximum entropy using environmental variables - Mei Shan; Shuang Liang; Hongchen Fu; Xiaoli Li; Yu Teng; Jingwen Zhao; Yaxin Liu; Chen Cui; Li Chen; Hai Yu; Shunbang Yu; Yanling Sun; et al. (Nutrient Cycling in Agroecosystems, 2021)

Design, synthesis and evaluation of dihydrotriazine derivatives-bearing 5-aryloxypyrazole moieties as antibacterial agents - Tian-Yi Zhang; Chun-Shi Li; Ming-Yue Cui; Xue-Qian Bai; Jiang-Hui Chen; Ze-Wen Song; Bo Feng; Xue-Kun Liu (Molecular Diversity, 2021)

Coupling InSAR and numerical modeling for characterizing landslide movements under complex loads in urbanized hillslopes - Peifeng Ma; Yifei Cui; Weixi Wang; Hui Lin; Yuanzhi Zhang (Landslides, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Gas Flow Characteristics and Optimization of Gas Drainage Borehole Layout in Protective Coal Seam Mining: A Case Study from the Shaqu Coal Mine, Shanxi Province, China - Zhiheng Cheng; Hui Pan; Quanle Zou; Zhenhua Li; Liang Chen; Jialin Cao; Kun Zhang; Yongguo Cui (Natural Resources Research, 2021)

Characteristics of colloids and their affinity for heavy metals in road runoff with different traffic in Beijing, China - Xiaoli Du; Hui Liang; Xing Fang; Shenshen Cui; Junqi Li (Environmental Science and Pollution Research, 2021)

Biomonitoring of heavy metal contamination with roadside trees from metropolitan area of Hefei, China - Ting Fang; Ting Jiang; Kun Yang; Jing Li; Yangyang Liang; Xiuxia Zhao; Na Gao; Hui Li; Wenxuan Lu; Kai Cui (Environmental Monitoring and Assessment, 2021)

Hydrogen-rich water ameliorates the toxicity induced by Ca(NO3)2 excess through enhancing antioxidant capacities and re-establishing nitrate homeostasis in Brassica campestris spp. chinensis L. seedlings - Xiaonan Wei; Jiahui Chen; Hui Chen; Xue Wu; Jiyuan Tian; Nana Su; Jin Cui (Acta Physiologiae Plantarum, 2021)

A Rehmannia glutinosa cinnamate 4-hydroxylase promotes phenolic accumulation and enhances tolerance to oxidative stress - Yan Hui Yang; Heng Yang; Rui Fang Li; Cui Xiang Li; Lei Zeng; Chao Jie Wang; Na Li; Zhuang Luo (Plant Cell Reports, 2021)

Synthesis and evaluation of benzenesulfonic acid derivatives as human neutrophil elastase (hNE) inhibitors - Yanzhao Xu; Na Qi; Hui Wen; Gang Zhang; Yuchen Wang; Huaqing Cui (Medicinal Chemistry Research, 2021)

Phenotypic characteristics of ramie (Boehmeria nivea L) germplasm resources based on UAV remote sensing - Dandan Cui; Guoxian Cui; Ruifang Yang; Wei She; Yaoduan Liu; Hui Wang; Xiaohui Su; Jilong Wang; Wanhui Liu; Xinhui Wang; Jieyi Liu; Hongyu Fu (Genetic Resources and Crop Evolution, 2021)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Groundwater resources survey of tongchuan city using the audio magnetotelluric method - Zhi-min Xu; Jing-tian Tang; Guang Li; Hui-Cui Xin; Zhang-jian Xu; Xin-ping Tan; Jin Li (Applied Geophysics, 2020)

A novel alkaloid glycoside isolated from Atalantia buxifolia - Hui-Xian Liang; Jing-Jing Sun; Zhi-Bin Shen; Bang-Wei Yu; Hong-Hua Cui; Yong-Qin Yin (Natural Product Research, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

A new approach for examining the neurovascular structure with phalloidin and calcitonin gene-related peptide in the rat cranial dura mater - Jia Wang; Dongsheng Xu; Jingjing Cui; Shuya Wang; Chen She; Hui Wang; Shuang Wu; Jianliang Zhang; Bing Zhu; Wanzhu Bai (Journal of Molecular Histology, 2020)

Characteristics of the spike and ORF3 genes of porcine epidemic diarrhea virus in Henan and Shanxi provinces of China - Jian-tao Cui; Han Qiao; Cheng-yao Hou; Hui-Hua Zheng; Xin-Sheng Li; Lan-lan Zheng; Hong-Ying Chen (Archives of Virology, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

CSF Brain-Reactive Autoantibodies are Elevated in Patients with Viral Encephalitis - Zhong-Yuan Yu; Jian-Hong Wang; Wei-Wei Li; Ye-Ran Wang; Noralyn B. Mañucat-Tan; Jun Wang; Ju Wang; Gao-Yu Cui; Jie-Xiang Pan; Shui-Xian Zhang; Zu-Juan Liu; Liang Tan; et al. (Neuroscience Bulletin, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Assessment of 12 Fish Species in the Northwest Pacific Using the CMSY and BSM Methods - Yibang Wang; Yuanchao Wang; Cui Liang; Hui Zhang; Weiwei Xian (Frontiers in Marine Science, 2020)

The combination of acyclovir and dexamethasone protects against Alzheimer’s disease-related cognitive impairments in mice - Zhang Hui; Yuan Zhijun; Yan Yushan; Chen Liping; Zhou Yiying; Zhang Difan; Choi Tony Chunglit; Cui Wei (Psychopharmacology, 2020)

Correction to: Water pollution characteristics and analysis of Chaohu Lake basin by using different assessment methods - Xiong Yang; Hongbiao Cui; Xiaosheng Liu; Qiugang Wu; Hui Zhang (Environmental Science and Pollution Research, 2020)

Diversity and Distribution of Methanogenic Community Between Two Typical Alpine Ecosystems on the Qinghai–Tibetan Plateau - Yanfa Wang; Hongpeng Cui; Xin Su; Shiping Wei; Youhai Zhu; Zhenquan Lu; Shouji Pang; Hui Liu; Shuai Zhang; Weiguo Hou (Current Microbiology, 2020)

High-frequency direct shoot organogenesis from garlic (Allium sativum L.) inflorescence and clonal fidelity assessment in regenerants - Yan-Bin Wen; Xiao-Xue Liu; Hong-Jiu Liu; Cui-Nan Wu; Huan-Wen Meng; Zhi-Hui Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Two new species of Neofavolus (Polyporales, Basidiomycota) based on morphological characters and molecular evidence - Jia-Hui Xing; Jun-Liang Zhou; Bao-Kai Cui (Mycological Progress, 2020)

Water pollution characteristics and analysis of Chaohu Lake basin by using different assessment methods - Xiong Yang; Hongbiao Cui; Xiaosheng Liu; Qiugang Wu; Hui Zhang (Environmental Science and Pollution Research, 2020)

Late Pleistocene environmental information on the Diexi paleo-dammed lake of the upper Minjiang River in the eastern margin of the Tibetan Plateau, China - Lan-sheng Wang; Xiao-qun Wang; Jun-hui Shen; Guan Yin; Jie Cui; Xiang-ning Xu; Zhi-long Zhang; Tao Wan; Li-wang Wen (Journal of Mountain Science, 2020)

Stock Assessment Using LBB Method for Eight Fish Species From the Bohai and Yellow Seas - Yibang Wang; Yuanchao Wang; Shude Liu; Cui Liang; Hui Zhang; Weiwei Xian (Frontiers in Marine Science, 2020)

SsHKT1;1 is coordinated with SsSOS1 and SsNHX1 to regulate Na+ homeostasis in Suaeda salsa under saline conditions - Wen-Ying Wang; Ya-Qi Liu; Hui-Rong Duan; Xiu-Xia Yin; Yan-Nong Cui; Wei-Wei Chai; Xin Song; Timothy J. Flowers; Suo-Min Wang (Plant and Soil, 2020)

Laboratory Investigation on Shear Behaviors of Bolt–Grout Interface Subjected to Constant Normal Stiffness - Chuanqing Zhang; Guojian Cui; Liang Deng; Hui Zhou; Jingjing Lu; Feng Dai (Rock Mechanics and Rock Engineering, 2020)

A Review of Functional Near-Infrared Spectroscopy Studies of Motor and Cognitive Function in Preterm Infants - Quan Wang; Guang-Pu Zhu; Li Yi; Xin-Xin Cui; Hui Wang; Ru-Yi Wei; Bing-Liang Hu (Neuroscience Bulletin, 2020)

Impact of Maternal Selenium Supplementation from Late Gestation and Lactation on Piglet Immune Function - Ning-ya Li; Zhi-jian Sun; Abdur Rahman Ansari; Lei Cui; Ya-fang Hu; Zi-wei Li; Mickael Briens; Lei Kai; Lv-hui Sun; Niel A. Karrow; Hua-zhen Liu (Biological Trace Element Research, 2020)

High Canonical Wnt/β-Catenin Activity Sensitizes Murine Hematopoietic Stem and Progenitor Cells to DNA Damage - Yiting Wang; Hui Cui; Si Tao; Ting Zeng; Jianying Wu; Zhendong Tao; Liu Zhang; Bing Zou; Zhiyang Chen; George B. Garside; Duozhuang Tang (Stem Cell Reviews and Reports, 2020)
Aging is characterized by the accumulation of DNA damage and a decrease in stem cell functionality, yet molecular mechanisms that limit the maintenance of stem cells in response to DNA damage remain to be delineated. Here we show in mouse models that DNA damage leads to a transient over-activation of Wnt signaling in hematopoietic stem cells (HSCs), and that high activity of canonical Wnt/β-catenin signaling sensitizes HSCs to DNA damage induced by X-irradiation which results in preferential maintenance of HSCs with low levels of Wnt signaling. The study shows that genetic or chemical activation of canonical Wnt signaling enhances radiosensitivity of HSCs while inhibition of Wnt signaling decreases it. Together, these results indicate that levels of Wnt signaling activity mediate heterogeneity in the sensitivity of HSCs to DNA damage induced depletion. These findings could be relevant for molecular alterations and selection of stem cells in the context of DNA damage accumulation during aging and cancer formation.

Edaravone at high concentrations attenuates cognitive dysfunctions induced by abdominal surgery under general anesthesia in aged mice - Yiying Zhou; Xiang Wu; Luying Ye; Yujing Bai; Hui Zhang; Zhenquan Xuan; Yi Feng; Panpan Zhang; Yi Chen; Yushan Yan; Binbin Zhu; Wei Cui (Metabolic Brain Disease, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

MUC16 facilitates cervical cancer progression via JAK2/STAT3 phosphorylation-mediated cyclooxygenase-2 expression - Hui Shen; Meng Guo; Lu Wang; Xinyue Cui (Genes & Genomics, 2020)

Nocardia panacis sp. nov., a novel actinomycete with antiphytopathogen activity isolated from the rhizosphere of Panax notoginseng - Jia-Yun Hu; Lei Li; Guang Peng; Yi-Qing Li; Li-Hua Xu; Hui-Lin Guan; Li-Xing Zhao; Cui-Ping Miao (Antonie van Leeuwenhoek, 2020)

Numerical Study on Hydrodynamic Responses of Floating Rope Enclosure in Waves and Currents - Hui Yang; Yun-Peng Zhao; Chun-Wei Bi; Yong Cui (Journal of Marine Science and Engineering, 2020)
Enclosure aquaculture is a healthy and ecological aquaculture pattern developed in recent years to relieve the pressure due to the wild fish stock decline and water pollution. The object of this paper was a floating rope enclosure, which mainly consisted of floaters, mooring lines, sinkers and a net. In order to optimize mooring design factors, the hydrodynamic responses of the floating rope enclosure with different mooring systems in combined wave-current were investigated by experimental and numerical methods. Physical model experiments with a model scale of 1:50 were performed to investigate the hydrodynamic characteristics of a floating rope enclosure with 12 mooring lines. Based on the lumped mass method, the numerical model was established to investigate the effects of mooring design factors on the mooring line tension, force acting on the bottom, and the volume retention of the floating rope enclosure. Through the analysis of numerical and experimental results, it was found that the maximum mooring line tension of the floating rope enclosure occurs on both sides of the windward. Increasing the number of mooring lines on the windward side is helpful to reduce the maximum mooring line tension. Waves and current both have an influence on the mooring line tension; in contrast, currents have a more obvious effect on the mooring line tension than waves. However, the influence of the wave period on the maximum mooring line tension is small. The force endured by the bottom of the floating rope enclosure also changes periodically with the wave period. Yet, the maximum force endured by the bottom of floating rope enclosure occurred at the windward and leeward of the structure. The volume retention of the floating rope enclosure increased with the increasing amount of mooring lines.

Wound Healing Potential of Low Temperature Plasma in Human Primary Epidermal Keratinocytes - Hui Song Cui; Yoon Soo Cho; So Young Joo; Chin Hee Mun; Cheong Hoon Seo; June-Bum Kim (Tissue Engineering and Regenerative Medicine, 2019)

Identification of a novel COL4A5 mutation in the proband initially diagnosed as IgAN from a Chinese family with X-linked Alport syndrome - Zhihui Li; Peng Zhu; Hui Huang; Ying Pan; Peng Han; Huanhuan Cui; Zhijuan Kang; Mai Xun; Yi Zhang; Saijun Liu; Jian Wang; Jing Wu (Science China Life Sciences, 2019)

Expressional and Functional Verification of the Involvement of CmEXPA4 in Chrysanthemum Root Development - Hong Ren; Li-zhu Wen; Yun-hui Guo; Yuan-yuan Yu; Cui-hui Sun; Hong-mei Fan; Fang-fang Ma; Cheng-shu Zheng (Journal of Plant Growth Regulation, 2019)

Composition and change in the microbiome of Diaphorina citri infected with Candidatus Liberibacter asiaticus in China - Xiao-bing Song; Ai-tian Peng; Jin-feng Ling; Yi-ping Cui; Bao-ping Cheng; Lian-hui Zhang (International Journal of Tropical Insect Science, 2019)

Correction to: Short-term dietary restriction in old mice rejuvenates the aging-induced structural imbalance of gut microbiota - Ting Zeng; Hui Cui; Duozhuang Tang; George B. Garside; Yiting Wang; Jianying Wu; Zhendong Tao; Liu Zhang; Si Tao (Biogerontology, 2019)
In the original publication of the article, the alphabets in figures were published in upper case and mismatched with the figure legends. The corrected figures and figure legends are given in this Correction.

Short-term dietary restriction in old mice rejuvenates the aging-induced structural imbalance of gut microbiota - Ting Zeng; Hui Cui; Duozhuang Tang; George B. Garside; Yiting Wang; Jianying Wu; Zhendong Tao; Liu Zhang; Si Tao (Biogerontology, 2019)

From Analysis of Ischemic Mouse Brain Proteome to Identification of Human Serum Clusterin as a Potential Biomarker for Severity of Acute Ischemic Stroke - Hailong Song; Hui Zhou; Zhe Qu; Jie Hou; Weilong Chen; Weiwu Cai; Qiong Cheng; Dennis Y. Chuang; Shanyan Chen; Shuwei Li; Jilong Li; Jianlin Cheng; et al. (Translational Stroke Research, 2019)

Refined chronology of prehistoric cultures and its implication for re-evaluating human-environment relations in the Hexi Corridor, northwest China - Yishi Yang; Shanjia Zhang; Chris Oldknow; Menghan Qiu; Tingting Chen; Haiming Li; Yifu Cui; Lele Ren; Guoke Chen; Hui Wang; Guanghui Dong (Science China Earth Sciences, 2019)

Cardiopulmonary Comorbidity, Radiomics and Machine Learning, and Therapeutic Regimens for a Cerebral fMRI Predictor Study in Psychotic Disorders - Xiao-Hui Wang; Angela Yu; Xia Zhu; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2019)

microRNA-7 inhibition protects human osteoblasts from dexamethasone via activation of epidermal growth factor receptor signaling - Jian-bo Fan; Wei Liu; Xin-hui Zhu; Sheng-yu Cui; Zhi-ming Cui; Jian-ning Zhao (Molecular and Cellular Biochemistry, 2019)

3D Reconstruction Approach for Outdoor Scene Based on Multiple Point Cloud Fusion - Hui Chen; Yan Feng; Jian Yang; Chenggang Cui (Journal of the Indian Society of Remote Sensing, 2019)

An overview of heavy metal pollution in Chaohu Lake, China: enrichment, distribution, speciation, and associated risk under natural and anthropogenic changes - Ting Fang; Kun Yang; Wenxuan Lu; Kai Cui; Jing Li; Yangyang Liang; Guanjun Hou; Xiuxia Zhao; Hui Li (Environmental Science and Pollution Research, 2019)

Selenium Content and/or T-2 Toxin Contamination of Cereals, Soil, and Children’s Hair in Some Areas of Heilongjiang and Gansu Provinces, China - Liyan Sun; Silu Cui; Qing Deng; Hui Liu; Yanhong Cao; Shaoping Wang; Jun Yu (Biological Trace Element Research, 2019)

Estrogen modulation of visceral pain - Li-hong Sun; Wen-xin Zhang; Qi Xu; Hui Wu; Cui-cui Jiao; Xin-zhong Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Tamarixetin protects against cardiac hypertrophy via inhibiting NFAT and AKT pathway - Cheng Fan; Yuan Li; Hui Yang; Yuqian Cui; Hao Wang; Heng Zhou; Jianning Zhang; Binfeng Du; Qian Zhai; Dawei Wu; Xiaomei Chen; Haipeng Guo (Journal of Molecular Histology, 2019)

Hormonal regulation and redox reaction of maize under partial root drying irrigation - Hui Yan; Ningbo Cui; Hanmi Zhou (Acta Physiologiae Plantarum, 2019)

Extreme-duration drought impacts on soil CO2 efflux are regulated by plant species composition - Chaoting Zhou; Joel A. Biederman; Hui Zhang; Linfeng Li; Xiaoyong Cui; Yakov Kuzyakov; Yanbin Hao; Yanfen Wang (Plant and Soil, 2019)

MicroRNA-132 in the Adult Dentate Gyrus is Involved in Opioid Addiction Via Modifying the Differentiation of Neural Stem Cells - Meng Jia; Xuewei Wang; Haolin Zhang; Can Ye; Hui Ma; Mingda Yang; Yijing Li; Cailian Cui (Neuroscience Bulletin, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Comprehensive prediction of coal seam thickness by using in-seam seismic surveys and Bayesian kriging - Mengbo Zhu; Jianyuan Cheng; Weixiong Cui; Hui Yue (Acta Geophysica, 2019)

Proteomic identification of lipid-bodies-associated proteins in maize seeds - Cui Du; Aimei Liu; Liangjie Niu; Di Cao; Hui Liu; Xiaolin Wu; Wei Wang (Acta Physiologiae Plantarum, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Central IGF-1 protects against features of cognitive and sensorimotor decline with aging in male mice - Gabriela E. Farias Quipildor; Kai Mao; Zunju Hu; Ardijana Novaj; Min-Hui Cui; Maria Gulinello; Craig A. Branch; Sriram Gubbi; Khushbu Patel; Douglas R. Moellering; Stefano Tarantini; Tamas Kiss; et al. (GeroScience, 2019)

A life support-based comprehensive treatment regimen dramatically lowers the in-hospital mortality of patients with fulminant myocarditis: a multiple center study - Sheng Li; Shengyong Xu; Chenze Li; Xiao Ran; Guanglin Cui; Mengying He; Kun Miao; Chunxia Zhao; Jiangtao Yan; Rutai Hui; Ning Zhou; Yan Wang; et al. (Science China Life Sciences, 2019)

Habitat selection of wintering cranes (Gruidae) in typical lake wetland in the lower reaches of the Yangtze River, China - Cheng Wang; Bin Dong; Ming Zhu; Hui Huang; Yu-huang Cui; Xiang Gao; Li-ping Liu (Environmental Science and Pollution Research, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Satellite-based Observational Study of the Tibetan Plateau Vortex: Features of Deep Convective Cloud Tops - Yi-Xuan Shou; Feng Lu; Hui Liu; Peng Cui; Shaowen Shou; Jian Liu (Advances in Atmospheric Sciences, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Primary molecular basis of androgenic gland endocrine sex regulation revealed by transcriptome analysis in Eriocheir sinensis - Chengwen Song; Lei Liu; Min Hui; Yuan Liu; Hourong Liu; Zhaoxia Cui (Journal of Oceanology and Limnology, 2019)

Spermidine application alleviates salinity damage to antioxidant enzyme activity and gene expression in alfalfa - Yanhong Lou; Rui Guan; Mingjie Sun; Fei Han; Wei He; Hui Wang; Fupeng Song; Xiumin Cui; Yuping Zhuge (Ecotoxicology, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Comparison of diploid and triploid Carassius auratus provides insights into adaptation to environmental change - Li Ren; Xin Gao; Conghui Yang; Hui Tan; Jialin Cui; Shi Wang; Wuhui Li; Chun Zhang; Min Tao; Qinbo Qin; Shaojun Liu (Science China Life Sciences, 2018)

Structure–activity relationship investigation of coumarin–chalcone hybrids with diverse side-chains as acetylcholinesterase and butyrylcholinesterase inhibitors - Lu Kang; Xiao-Hui Gao; Hao-Ran Liu; Xue Men; Hong-Nian Wu; Pei-Wu Cui; Eric Oldfield; Jian-Ye Yan (Molecular Diversity, 2018)

Boron Affects the Development of the Kidney Through Modulation of Apoptosis, Antioxidant Capacity, and Nrf2 Pathway in the African Ostrich Chicks - Haseeb Khaliq; Wang Jing; Xiao Ke; Yang Ke-Li; Sun Peng-peng; Lei Cui; Qiu Wei-wei; Lei Zhixin; Liu Hua-Zhen; Song Hui; Zhong Ju-Ming; Peng Ke-Mei (Biological Trace Element Research, 2018)

Transcriptome-wide identification and expression profile analysis of the bHLH family genes in Camellia sinensis - Xin Cui; Yong-Xin Wang; Zhi-Wei Liu; Wen-Li Wang; Hui Li; Jing Zhuang (Functional & Integrative Genomics, 2018)

Poststack internal multiples attenuation based on virtual events - Meng Chen; Jia-Hui Liu; Yong-Fu Cui; Tian-Yue Hu; Fei-Xu Chen; Wei-Kang Kuang; Zhen Zhang (Applied Geophysics, 2018)

MicroRNA-191, acting via the IRS-1/Akt signaling pathway, is involved in the hepatic insulin resistance induced by cigarette smoke extract - Qianlei Yang; Yan Cui; Fei Luo; Xinlu Liu; Qiushi Wang; Jun Bai; Faqin Dong; Qian Sun; Lu Lu; Hui Xu; Junchao Xue; Chao Chen; et al. (Environmental Science and Pollution Research, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

Identification and characterization of a novel goose-type and chicken-type lysozyme genes in Chinese rare minnow (Gobiocypris rarus) with potent antimicrobial activity - Yingying Zhang; Hui Yang; Weijia Song; Dan Cui; Lixin Wang (Genes & Genomics, 2018)

Transcriptome analysis of Hevea brasiliensis in response to exogenous methyl jasmonate provides novel insights into regulation of jasmonate-elicited rubber biosynthesis - Jin-Ping Liu; Jin Hu; Yan-Hui Liu; Cui-Ping Yang; Yu-Fen Zhuang; Xiu-Li Guo; Yi-Jian Li; Liangsheng Zhang (Physiology and Molecular Biology of Plants, 2018)

Yield enhancement strategies of rare pharmaceutical metabolites from endophytes - Fangxue Xu; Shiyuan Wang; Yujuan Li; Mengmeng Zheng; Xiaozhi Xi; Hui Cao; Xiaowei Cui; Hong Guo; Chunchao Han (Biotechnology Letters, 2018)

Physical and chemical characteristics of PM2.5 and its toxicity to human bronchial cells BEAS-2B in the winter and summer - Hui-hui Zhang; Zheng Li; Yu Liu; Ping Xinag; Xin-yi Cui; Hui Ye; Bao-lan Hu; Li-ping Lou (Journal of Zhejiang University-SCIENCE B, 2018)

Comparative Analyses of Methanogenic and Methanotrophic Communities Between Two Different Water Regimes in Controlled Wetlands on the Qinghai-Tibetan Plateau, China - Hongpeng Cui; Xin Su; Shiping Wei; Youhai Zhu; Zhenquan Lu; Yanfa Wang; Yuejiao Li; Hui Liu; Shuai Zhang; Shouji Pang (Current Microbiology, 2018)

Screen for Inhibitors of Crystal Growth to Identify Desirable Carriers for Amorphous Solid Dispersions Containing Felodipine - Jinping Fu; Lin Cui; Congbin Yang; Hui Xiong; Guobin Ren; Xingyuan Ma; Qiufang Jing; Fuzheng Ren (AAPS PharmSciTech, 2018)

Gene expression profile and long non-coding RNA analysis, using RNA-Seq, in chicken embryonic fibroblast cells infected by avian leukosis virus J - Xuming Hu; Shihao Chen; Chongxin Jia; Songlei Xue; Chunfeng Dou; Zhenqing Dai; Hui Xu; Zhen Sun; Tuoyu Geng; Hengmi Cui (Archives of Virology, 2018)

Dysfunction of GABAergic neurons in the parafacial zone mediates sleep disturbances in a streptozotocin-induced rat model of sporadic Alzheimer’s disease - Jin-Zhi Song; Su-Ying Cui; Xiang-Yu Cui; Xiao Hu; Yu-Nu Ma; Hui Ding; Hui Ye; Yong-He Zhang (Metabolic Brain Disease, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

A new isoflavone from the roots of Ficus auriculata - Cui-Cui Qi; Yan-Hui Fu; Wen-Hao Chen; Guang-Ying Chen; Chun-Yan Dai; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Association of MSI2 Gene Polymorphism with Age-at-Onset of Schizophrenia in a Chinese Population - Zhi-Lin Luan; Xiao-Hui Cui; Hu Xu; He-Yuan Lu; Yu-Yuan Li; Tian-Lan Lu; Dai Zhang (Neuroscience Bulletin, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Interaction of Wip1 and NF-κB regulates neuroinflammatory response in astrocytes - Fan Xu; Lifei Chen; Xin Zhao; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li (Inflammation Research, 2017)

Building capacity in biodiversity monitoring at the global scale - Dirk S. Schmeller; Monika Böhm; Christos Arvanitidis; Shannon Barber-Meyer; Neil Brummitt; Mark Chandler; Eva Chatzinikolaou; Mark J. Costello; Hui Ding; Jaime García-Moreno; Mike Gill; Peter Haase; et al. (Biodiversity and Conservation, 2017)

Glucocorticoid-Potentiated Spinal Microglia Activation Contributes to Preoperative Anxiety-Induced Postoperative Hyperalgesia - Rao Sun; Zhibin Zhao; Jiying Feng; Jinhua Bo; Hui Rong; Yishan Lei; Cui’e Lu; Xiaobao Zhang; Bailing Hou; Yu’e Sun; Yue Liu; Zhengliang Ma; et al. (Molecular Neurobiology, 2017)

Anti-glomerular basement membrane glomerulonephritis with thrombotic microangiopathy: a case report - Xiao-juan Yu; Sha-sha Han; Su-xia Wang; Xiao-yu Jia; Wei-yi Guo; Zhao Cui; Feng Yu; Fu-de Zhou; Ming-hui Zhao (Immunologic Research, 2017)

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

Optimized monitoring sites for detection of biodiversity trends in China - Haigen Xu; Mingchang Cao; Yi Wu; Lei Cai; Yun Cao; Hui Ding; Peng Cui; Jun Wu; Zhi Wang; Zhifang Le; Xiaoqiang Lu; Li Liu; et al. (Biodiversity and Conservation, 2017)

Occurrence, distribution, and attenuation of pharmaceuticals and personal care products in the riverside groundwater of the Beiyun River of Beijing, China - Lei Yang; Jiang-Tao He; Si-Hui Su; Ya-Feng Cui; De-Liang Huang; Guang-Cai Wang (Environmental Science and Pollution Research, 2017)

N2O emission characteristics and its affecting factors in rain-fed potato fields in Wuchuan County, China - Liwei Wang; Cheng Wang; Zhihua Pan; Hui Xu; Lin Gao; Peiyi Zhao; Zhiqiang Dong; Jingting Zhang; Guohui Cui; Sen Wang; Guolin Han; hui Zhao (International Journal of Biometeorology, 2017)

RIPK1/RIPK3/MLKL-mediated necroptosis contributes to compression-induced rat nucleus pulposus cells death - Songfeng Chen; Xiao Lv; Binwu Hu; Zengwu Shao; Baichuan Wang; Kaige Ma; Hui Lin; Min Cui (Apoptosis, 2017)

Adsorption of Dioxin by Bag Filter + Powdered Activated Carbon - Yu-Yong Cui; Guo-Hua Yang; Gui-Hui Xiao; Jiang-Hua Zhou; Guo-Zhu Ding; Xue-Jun Pan (Water, Air, & Soil Pollution, 2017)

A Novel Wheat Nicotianamine Synthase Gene, TaNAS-D, Confers High Salt Tolerance in Transgenic Arabidopsis - Jie Han; Wei Zhang; Lijing Sun; Qiannan Su; Zijing Li; Xiaoli Fan; Na Zhang; Ruiqing Pan; Fa Cui; Jun Ji; Hui Li; Junming Li (Plant Molecular Biology Reporter, 2017)

China is initiating the Aquatic 10-100-1,000 Genomics Program - Yingjie Liu; Pao Xu; Junmin Xu; Yu Huang; Yongxin Liu; Hui Fang; Yinchang Hu; Xinxin You; Chao Bian; Min Sun; Ruobo Gu; Lifeng Cui; et al. (Science China Life Sciences, 2017)

Chemical constituents from the roots of Ampelopsis delavayana and their antibacterial activities - Shuang-Xi Mei; Xu-Hong Li; Li-Guo Yang; Xiao-Hui Li; Jia-Ying Xie; Qi Yao; Mei Su; Tao Cui; Jing-Kun Wang; Zhao-Yun Zhu (Natural Product Research, 2017)

p38 MAPK Participates in the Mediation of GLT-1 Up-regulation During the Induction of Brain Ischemic Tolerance by Cerebral Ischemic Preconditioning - Min Zhang; Jian-Xue Gong; Jia-Lei Wang; Meng-Yang Jiang; Li Li; Yu-Yan Hu; Jie Qi; Ling-Yan Zhang; Hang Zhao; Xin Cui; Xiao-Hui Xian; Wen-Bin Li (Molecular Neurobiology, 2017)

T cell infiltration is associated with kidney injury in patients with anti-glomerular basement membrane disease - Shui-Yi Hu; Xiao-Yu Jia; Jian-Nan Li; Xin Zheng; Jie Ao; Gang Liu; Zhao Cui; Ming-Hui Zhao (Science China Life Sciences, 2016)

Does Fluoride Affect Serum Testosterone and Androgen Binding Protein with Age-Specificity? A Population-Based Cross-Sectional Study in Chinese Male Farmers - Leizhen Duan; Jingyuan Zhu; Keyan Wang; Guoyu Zhou; Yuejin Yang; Liuxin Cui; Hui Huang; Xuemin Cheng; Yue Ba (Biological Trace Element Research, 2016)

Two new sesquiterpenes from Chloranthus japonicus Sieb - Qiang-Qiang Lu; Xin-Wei Shi; Shao-Jun Zheng; Jun-Hui Zhou; Xin-Ai Cui; Jin-Ming Gao (Natural Product Research, 2016)

A HOPS protein, CmVps39, is required for vacuolar morphology, autophagy, growth, conidiogenesis and mycoparasitic functions of Coniothyrium minitans - Xiaoxiang Yang; Hui Cui; Jiasen Cheng; Jiatao Xie; Daohong Jiang; Tom Hsiang; Yanping Fu (Environmental Microbiology, 2016)
Summary Coniothyrium minitans is an important sclerotial and hyphal parasite of the plant pathogen Sclerotinia sclerotiorum . Previously, a conidiation‐deficient mutant, ZS‐1N22225, was screened from a T‐DNA insertional library of C. minitans . CmVps39, a homologue of Vam6p/Vps39p that plays a critical role in vacuolar morphogenesis in yeast, was disrupted by a T‐DNA insertion in this mutant. CmVps39 is composed of 1071 amino acids with an amino‐terminal citron homology domain and a central clathrin homology domain, as observed for other Vam6p/Vps39p family proteins. Abnormal fragmented vacuoles were observed in ΔCmVps39 under light microscopy and transmission electron microscopy, and ΔCmVps39 showed impairment in autophagy. ΔCmVps39 also exhibited significantly reduced hyphal development, poor conidiation and decreased sclerotial mycoparasitism. In addition, deletion of CmVps39 affected osmotic adaptation, pH homeostasis and cell wall integrity. Taken together, our results suggest that CmVps39 has an essential function in vacuolar morphology, autophagy, fungal development and mycoparasitism in C. minitans .

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Phytotoxicity mechanisms of two coumarin allelochemicals from Stellera chamaejasme in lettuce seedlings - Zhiqiang Yan; Dandan Wang; Haiyan Cui; Denghong Zhang; Yuhe Sun; Hui Jin; Xiuzhuang Li; Xiaoyan Yang; Hongru Guo; Xiaofeng He; Le Pan; Xia Ren; et al. (Acta Physiologiae Plantarum, 2016)

Ancient DNA analysis of Panicum miliaceum (broomcorn millet) from a Bronze Age cemetery in Xinjiang, China - Chunxiang Li; Yu Dong; Minxuan Liu; Ping Lu; Wenying Li; Yingnan Wang; Xiyan Cui; Hui Zhou; Yue Xu (Vegetation History and Archaeobotany, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Up-regulation of Wip1 involves in neuroinflammation of retinal astrocytes after optic nerve crush via NF-κB signaling pathway - Haibin Zhong; Ling Cui; Fan Xu; Lifei Chen; Li Jiang; Hui Huang; Jiping Xu; Xin Zhao; Li Li; Siming Zeng; Min Li (Inflammation Research, 2016)

Ecological species groups and interspecific association of vegetation in natural recovery process at Xiejiadian landslide after 2008 Wenchuan earthquake - Qing-wei Yang; Shou-jiang Liu; Cui-hua Hu; Ye-bin Lin; Bin Zhang; Ming-liang Luo; Hui-ling Peng (Journal of Mountain Science, 2016)

The distribution of deep source rocks in the GS Sag: joint MT–gravity modeling and constrained inversion - Yan-Ling Shi; Zu-Zhi Hu; Wen-Hui Huang; Qiang Wei; Sheng Zhang; Cui-Xian Meng; Lian-Sheng Ji (Applied Geophysics, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Association of interleukin-1 family cytokines single nucleotide polymorphisms with susceptibility to systemic sclerosis: an independent case–control study and a meta-analysis - Xiao-Lei Huang; Guo-Cui Wu; Yu-Jie Wang; Xiao-Ke Yang; Guo-Jun Yang; Jin-Hui Tao; Yu Duan; Jun-Wei Yan; Xiang-Pei Li; Dong-Qing Ye; Jing Wang (Immunologic Research, 2016)

Voluntary action and tactile sensory feedback in the intentional binding effect - Ke Zhao; Li Hu; Fangbing Qu; Qian Cui; Qiuhong Piao; Hui Xu; Yanyan Li; Liang Wang; Xiaolan Fu (Experimental Brain Research, 2016)

Effects of Long-Term Mineral Block Supplementation on Antioxidants, Immunity, and Health of Tibetan Sheep - Hui Wang; Zhiqi Liu; Meizhou Huang; Shengyi Wang; Dongan Cui; Shuwei Dong; Shengkun Li; Zhiming Qi; Yongming Liu (Biological Trace Element Research, 2016)

Polypore diversity in North America with an annotated checklist - Li-Wei Zhou; Karen K. Nakasone; Harold H. Burdsall; James Ginns; Josef Vlasák; Otto Miettinen; Viacheslav Spirin; Tuomo Niemelä; Hai-Sheng Yuan; Shuang-Hui He; Bao-Kai Cui; Jia-Hui Xing; et al. (Mycological Progress, 2016)

Optimal growth condition of earthworms and their vermicompost features during recycling of five different fresh fruit and vegetable wastes - Kui Huang; Hui Xia; Fusheng Li; Yongfen Wei; Guangyu Cui; Xiaoyong Fu; Xuemin Chen (Environmental Science and Pollution Research, 2016)

MLL2 is essential for porcine embryo development in vitro - Ming-Hui Zhao; Shuang Liang; Nam-Hyung Kim; Xiang-Shun Cui (In Vitro Cellular & Developmental Biology - Animal, 2016)

Activation of peroxisome proliferator-activated receptor α ameliorates perfluorododecanoic acid-induced production of reactive oxygen species in rat liver - Hui Liu; Hongxia Zhang; Ruina Cui; Xuejiang Guo; Dazhi Wang; Jiayin Dai (Archives of Toxicology, 2016)

Flow cytometric analysis of DNA content for four commercially important crabs in China - Lei Liu; Zhaoxia Cui; Chengwen Song; Yuan Liu; Min Hui; Chunlin Wang (Acta Oceanologica Sinica, 2016)

Dexmedetomidine Dose-Dependently Attenuates Ropivacaine-Induced Seizures and Negative Emotions Via Inhibiting Phosphorylation of Amygdala Extracellular Signal-Regulated Kinase in Mice - Ming-Zhu Zhai; Huang-Hui Wu; Jun-Bin Yin; Yuan-Yuan Cui; Xiao-Peng Mei; Han Zhang; Xia Zhu; Xue-Feng Shen; Alan David Kaye; Guo-Zhong Chen (Molecular Neurobiology, 2016)

Silicon nutrition alleviates the lipid peroxidation and ion imbalance of Glycyrrhiza uralensis seedlings under salt stress - Yue-Tong Li; Wen-Jin Zhang; Jia-Jia Cui; Duo-Yong Lang; Ming Li; Qi-Peng Zhao; Xin-Hui Zhang (Acta Physiologiae Plantarum, 2016)

MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2016)

Resveratrol Represses Pokemon Expression in Human Glioma Cells - Yutao Yang; Jiajun Cui; Feng Xue; Anne-Marie Overstreet; Yiping Zhan; Dapeng Shan; Hui Li; Hui Li; Yongjun Wang; Mengmeng Zhang; Chunjiang Yu; Zhi-Qing David Xu (Molecular Neurobiology, 2016)

Role of microRNA-195 in cardiomyocyte apoptosis induced by myocardial ischaemia–reperfusion injury - CHANG-KUI GAO; HUI LIU; CHENG-JI CUI; ZHAO-GUANG LIANG; HONG YAO; YE TIAN (Journal of Genetics, 2016)

Comprehensive analyses of the initiation and entrainment processes of the 2000 Yigong catastrophic landslide in Tibet, China - Jia-wen Zhou; Peng Cui; Ming-hui Hao (Landslides, 2016)

An approach to jointly invert hypocenters and 1D velocity structure and its application to the Lushan earthquake series - Hui Qian; James Mechie; Haibing Li; Guangqi Xue; Heping Su; Xiang Cui (Journal of Seismology, 2016)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Isolation and characterization of a crude oil degrading bacteria from formation water: comparative genomic analysis of environmental Ochrobactrum intermedium isolate versus clinical strains - Lu-jun Chai; Xia-wei Jiang; Fan Zhang; Bei-wen Zheng; Fu-chang Shu; Zheng-liang Wang; Qing-feng Cui; Han-ping Dong; Zhong-zhi Zhang; Du-jie Hou; Yue-hui She (Journal of Zhejiang University-SCIENCE B, 2015)

Inhibitory role of reactive oxygen species in the differentiation of multipotent vascular stem cells into vascular smooth muscle cells in rats: a novel aspect of traditional culture of rat aortic smooth muscle cells - Haibo Song; Hui Wang; Weiwei Wu; Lei Qi; Lei Shao; Fang Wang; Yimu Lai; Desiree Leach; Bryan Mathis; Joseph S. Janicki; Xing Li Wang; Dongqi Tang; et al. (Cell and Tissue Research, 2015)

Effects and mechanism of flavonoids from Astragalus complanatus on breast cancer growth - Jinhai Zhu; Hui Zhang; Zhengzhi Zhu; Qiong Zhang; Xiaokai Ma; Zhen Cui; Tingjing Yao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Deficient PKR in RAX/PKR Association Ameliorates Ethanol-Induced Neurotoxicity in the Developing Cerebellum - Hui Li; Jian Chen; Yuanlin Qi; Lu Dai; Mingfang Zhang; Jacqueline A. Frank; Jonathan W. Handshoe; Jiajun Cui; Wenhua Xu; Gang Chen (The Cerebellum, 2015)

Dynamics of the worldwide number of fungi with emphasis on fungal diversity in China - Yu-Cheng Dai; Bao-Kai Cui; Jing Si; Shuang-Hui He; Kevin D. Hyde; Hai-Sheng Yuan; Xiao-Yong Liu; Li-Wei Zhou (Mycological Progress, 2015)

Therapeutic potential of human umbilical cord blood mesenchymal stem cells on erectile function in rats with cavernous nerve injury - Jian-Qiang Zhu; Hong-Kai Lu; Zhi-Qiang Cui; Yong-Chuan Wang; Yong-Hui Li; Weixin Zhao; Qiang Fu; Yue-Min Xu; Yong Xu; Lu-Jie Song (Biotechnology Letters, 2015)

Isolation and full-genome sequence of two reticuloendotheliosis virus strains from mixed infections with Marek’s disease virus in China - Ke-yan Bao; Yan-ping Zhang; Hui-wen Zheng; Hong-chao Lv; Yu-long Gao; Jing-fei Wang; Hong-lei Gao; Xiao-le Qi; Hong-yu Cui; Yong-qiang Wang; Xian-gang Ren; Xiao-mei Wang; et al. (Virus Genes, 2015)

Characterization of 1-aminocyclopropane-1-carboxylic acid synthase (ACS) genes during nectarine fruit development and ripening - Wenfang Zeng; Lei Pan; Hui Liu; Liang Niu; Zhenhua Lu; Guochao Cui; Zhiqiang Wang (Tree Genetics & Genomes, 2015)

Identification of 4438 novel lincRNAs involved in mouse pre-implantation embryonic development - Jie Lv; Hui Liu; Shihuan Yu; Hongbo Liu; Wei Cui; Yang Gao; Tao Zheng; Geng Qin; Jing Guo; Tiebo Zeng; Zhengbin Han; Yan Zhang; et al. (Molecular Genetics and Genomics, 2015)

Activation of NOD1 by DAP contributes to myocardial ischemia/reperfusion injury via multiple signaling pathways - Hui Yang; Nan Li; Li-Na Song; Lei Wang; Cui Tian; Chao-Shu Tang; Jie Du; Hui-Hua Li; Xiao-Hong Yu; Hong-Xia Wang (Apoptosis, 2015)

Relationship between haze and acute cardiovascular, cerebrovascular, and respiratory diseases in Beijing - Jin-jun Zhang; Meng-meng Cui; Da Fan; De-shan Zhang; Hui-xin Lian; Zhao-yin Yin; Jin Li (Environmental Science and Pollution Research, 2015)

Novel polymorphic EST-derived microsatellite markers for the red-listed five needle pine, Pinus dabeshanensis - Zhi-Yong Zhang; Bin-Bin Cui; Jian-Feng Mao; Xiao-Ming Pang; Hui Liu; Ying-Yue Li (Conservation Genetics Resources, 2015)

Development of 36 novel polymorphic microsatellites for the critically endangered tree Pinus squamaia, by transcriptome database mining - Jian-Feng Mao; Bin-Bin Cui; Zhi-Yong Zhang; Hui Liu; Ying-Yue Li (Conservation Genetics Resources, 2015)

The role of visfatin on the regulation of inflammation and apoptosis in the spleen of LPS-treated rats - Ke Xiao; Wei-Hua Zou; Zhi Yang; Zia ur Rehman; Abdur Rahman Ansari; Huai-Rui Yuan; Ying Zhou; Lu Cui; Ke-Mei Peng; Hui Song (Cell and Tissue Research, 2015)

Isolation and characterization of a proteinaceous α-amylase inhibitor AAI-CC5 from Streptomyces sp. CC5, and its gene cloning and expression - Zhibin Sun; Weihao Lu; Pingping Liu; Hui Wang; Yan Huang; Yuguo Zhao; Yi Kong; Zhongli Cui (Antonie van Leeuwenhoek, 2015)

EGFR-AKT-mTOR activation mediates epiregulin-induced pleiotropic functions in cultured osteoblasts - Jian-bo Fan; Wei Liu; Xin-hui Zhu; Kun Yuan; Da-wei Xu; Jia-jia Chen; Zhi-ming Cui (Molecular and Cellular Biochemistry, 2015)

The Effects of Wubeizi Ointment on the Proliferation of Keloid-Derived Fibroblasts - Ji-cun Ding; Zhi-ming Tang; Xiao-xiang Zhai; Xiang-hui Chen; Jing-guo Li; Cui-xia Zhang (Cell Biochemistry and Biophysics, 2015)
To evaluate the effectiveness of the Wubeizi (WBZ) ointment on keloid-derived fibroblasts. The primary cells of the keloid-derived fibroblasts were cultured and the effectiveness of the WBZ ointment at different concentrations was examined by MTT colorimetric methods on keloid-derived fibroblasts. The WBZ ointment showed inhibitory effects on proliferating the keloid-derived fibroblasts ( P < 0.01)in a time- and dose-dependent manner. The proportion of cells in S stage was significantly higher in each of the WBZ ointment group than in the control group ( P <0.01), and the proportion of G 2 + M stage cells was significantly lower than that of control group, which was statistically significant ( P < 0.01).The inhibitory effects of the S and G 2 + M stage increased with higher drug concentrations ( P < 0.05). Conclusion: The WBZ ointment can inhibit the proliferation of the keloid-derived fibroblasts in a time- and dose- dependent manner.

Identification and characterization of long intergenic non-coding RNAs related to mouse liver development - Jie Lv; Zhijun Huang; Hui Liu; Hongbo Liu; Wei Cui; Bao Li; Hongjuan He; Jing Guo; Qi Liu; Yan Zhang; Qiong Wu (Molecular Genetics and Genomics, 2014)

Zinc depletion activates porcine metaphase II oocytes independently of the protein kinase C pathway - Ming-Hui Zhao; Nam-Hyung Kim; Xiang-Shun Cui (In Vitro Cellular & Developmental Biology - Animal, 2014)

Association of interleukin-23 receptor gene polymorphisms with risk of bladder cancer in Chinese - Tielong Tang; Hui Xue; Shu Cui; Zhiyong Gong; Zhonghai Fei; Shulin Cheng; Chunyan Gui (Familial Cancer, 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

miR-1246 releases RTKN2-dependent resistance to UVB-induced apoptosis in HaCaT cells - Wei Li; Ya-Fen Wu; Rong-Hua Xu; Hui Lu; Cui Hu; Hua Qian (Molecular and Cellular Biochemistry, 2014)

Selenium Promotes the Growth and Photosynthesis of Tomato Seedlings Under Salt Stress by Enhancing Chloroplast Antioxidant Defense System - Ming Diao; Long Ma; Jianwei Wang; Jinxia Cui; Aifei Fu; Hui-ying Liu (Journal of Plant Growth Regulation, 2014)

Deep-Red Phosphorescent Iridium(III) Complexes Containing 1-(Benzo[b] Thiophen-2-yl) Isoquinoline Ligand: Synthesis, Photophysical and Electrochemical Properties and DFT Calculations - Gao-Nan Li; Ying Zou; Yi-Ding Yang; Jiao Liang; Feng Cui; Tao Zheng; Hui Xie; Zhi-Gang Niu (Journal of Fluorescence, 2014)

AGGF1 protects from myocardial ischemia/reperfusion injury by regulating myocardial apoptosis and angiogenesis - Yu Liu; Hui Yang; Lina Song; Nan Li; Qiu-Yue Han; Cui Tian; Erhe Gao; Jie Du; Yun-Long Xia; Hui-Hua Li (Apoptosis, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Molecular cloning and characterization of 5-enolpyruvylshikimate-3-phosphate synthase gene from Convolvulus arvensis L. - Zhao-Feng Huang; Chao-Xian Zhang; Hong-Juan Huang; Shou-Hui Wei; Yan Liu; Hai-Lan Cui; Jing-Chao Chen; Long Yang; Jin-Yi Chen (Molecular Biology Reports, 2014)

Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2014)

Sedimentary filling and sequence structure dominated by T-R cycles of the Nenjiang Formation in the Songliao Basin - ChenChen Zhang; Shun Zhang; Wei Wei; ChaoDong Wu; JiangPing Liang; Wen Niu; JinXia Du; XiuLi Fu; KunNing Cui; Chao Wang; Hui Wang (Science China Earth Sciences, 2014)

Complete genome sequence analysis of two human enterovirus C99 strains isolated in Xinjiang Uighur Autonomous Region, China, in 2011 - Qiang Sun; Yong Zhang; Hui Cui; Shuangli Zhu; Xiaolei Li; Guohong Huang; Haishu Tang; Dongmei Yan; Dongyan Wang; Wenbo Xu (Archives of Virology, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Involvement of Upregulated P53-Induced Death Domain Protein (PIDD) in Neuronal Apoptosis after Rat Traumatic Brain Injury - Chunhua Wan; Junkang Jiang; Hui Mao; Jianhua Cao; Xiaohong Wu; Gang Cui (Journal of Molecular Neuroscience, 2013)

Characterization of Edenia gomezpompae Isolated from a Patient with Keratitis - Yan Cui; Hui Jia; Dan He; Huimei Yu; Song Gao; Koji Yokoyama; Jing Li; Li Wang (Mycopathologia, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Reducing the oxidative stress mediates the cardioprotection of bicyclol against ischemia-reperfusion injury in rats - Jie Cui; Zhi Li; Ling-bo Qian; Qin Gao; Jue Wang; Meng Xue; Xiao-e Lou; Iain C. Bruce; Qiang Xia; Hui-ping Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Identification of the quantitative trait loci (QTL) underlying water soluble protein content in soybean - Weiguo Lu; Zixiang Wen; Haichao Li; Daohua Yuan; Jinying Li; Hui Zhang; Zhongwen Huang; Shiyou Cui; Weiijun Du (Theoretical and Applied Genetics, 2013)

Expression of RBMX After Spinal Cord Injury in Rats - Jinlong Zhang; Debao Li; Aiguo Shen; Hui Mao; Huricha Jin; Wei Huang; Dawei Xu; Jianbo Fan; Jiajia Chen; Longfei Yang; Zhiming Cui (Journal of Molecular Neuroscience, 2013)

Different Functions of HIPK2 and CtBP2 in Traumatic Brain Injury - Feihui Zou; Jian Xu; Hongran Fu; Jianhua Cao; Hui Mao; Mingjie Gong; Gang Cui; Yang Zhang; Wei Shi; Jian Chen (Journal of Molecular Neuroscience, 2013)

Expression of biologically active human interferon alpha 2b in the milk of transgenic mice - Hui Li; Qingyou Liu; Kuiqing Cui; Jinfeng Liu; Yanping Ren; Deshun Shi (Transgenic Research, 2013)

Development of InDel markers for Brassica rapa based on whole-genome re-sequencing - Bo Liu; Yan Wang; Wen Zhai; Jie Deng; Hui Wang; Yang Cui; Feng Cheng; Xiaowu Wang; Jian Wu (Theoretical and Applied Genetics, 2013)

The binding characteristics of the interaction between 3-(2-cyanoethyl) cytosine and human serum albumin - Feng-Ling Cui; Guang-Quan Hui; Rui-Na Huo; Gui-Rong Qu (Molecular Biology Reports, 2012)

Curcumin protects against staurosporine toxicity in rat neurons - Xiao-Yan Qin; Ji-Hui Lv; Jia Cui; Xue Fang; Yan Zhang (Neuroscience Bulletin, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

Relationships between edema degree and clinical and biochemical parameters in posterior reversible encephalopathy syndrome: a preliminary study - Gao Bo; Liang Hui; Liu Feng-li; Lv Cui (Acta Neurologica Belgica, 2012)

Effects of pyrene on antioxidant systems and lipid peroxidation level in mangrove plants, Bruguiera gymnorrhiza - Hui Song; You-Shao Wang; Cui-Ci Sun; Yu-Tu Wang; Ya-Lan Peng; Hao Cheng (Ecotoxicology, 2012)

Enhancing Effects of Chronic Lithium Treatment on Detour Learning in Chicks - Lei Zhang; Xiaoyun Chen; Wei Feng; Hui Liang; Yonghua Cui; Shiqing Xu; Yi Che (Biological Trace Element Research, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Establishment and characterization of outer root sheath (ORS) cell line from Jining grey goat - Zhifeng Cui; Yanxia Hu; Hui Wang; Yongqing Zeng; Bin Dong; Houshun Zhu; Zhongdian Dong; Zhiyuan Liu (Biotechnology Letters, 2012)

Identification of single nucleotide polymorphisms and haplotypes associated with yield and yield components in soybean (Glycine max) landraces across multiple environments - Derong Hao; Hao Cheng; Zhitong Yin; Shiyou Cui; Dan Zhang; Hui Wang; Deyue Yu (Theoretical and Applied Genetics, 2012)

Physiological responses to salt stress of T2 alfalfa progenies carrying a transgene for betaine aldehyde dehydrogenase - Li-Ping Yan; Cui-Lan Liu; Hui-Min Liang; Xiu-Hong Mao; Fei Wang; Cai-Hong Pang; Jing Shu; Yang Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Thyroid disruption effects of environmental level perfluorooctane sulfonates (PFOS) in Xenopus laevis - Yan Cheng; Yuan Cui; Hui-ming Chen; Wen-ping Xie (Ecotoxicology, 2011)

Skin advanced glycation end product accumulation and muscle strength among adult men - Haruki Momma; Kaijun Niu; Yoritoshi Kobayashi; Lei Guan; Mika Sato; Hui Guo; Masahiko Chujo; Atsushi Otomo; Cui Yufei; Hiroko Tadaura; Tatsunori Saito; Takefumi Mori; et al. (European Journal of Applied Physiology, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Isolation and characterization of phosphate-solubilizing bacteria from walnut and their effect on growth and phosphorus mobilization - Xuan Yu; Xu Liu; Tian Hui Zhu; Guang Hai Liu; Cui Mao (Biology and Fertility of Soils, 2011)

Alternative splicing of the antitrypsin gene in the silkworm, Bombyx mori - Hui-fen Liu; Yi-nü Li; Ru Jia; Wei-zheng Cui; Zhi-mei Mu; Zhi-fang Zhang (Molecular Biology Reports, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

A loop-controlled rrnB P1 promoter for high-level expression of heterologous proteins in Escherichia coli - Xiaoli Zhao; Wenjing Shen; Peipei Ben; Yi Kong; Hui Cao; Zhongli Cui (Biotechnology Letters, 2011)

Molecular characterization of T-DNA integration sites in transgenic birch - Fan-Suo Zeng; Ya-Guang Zhan; Hong-Cui Zhao; Ying Xin; Feng-Hui Qi; Chuan-Ping Yang (Trees, 2010)

Probability assessment of river blocking by debris flow associated with the Wenchuan Earthquake - Jian-Qi Zhuang; Peng Cui; Yong-Gang Ge; Yi-Ping He; Ying-Hui Liu; Xiao-Jun Guo (International Journal of Remote Sensing, 2010)

Zhihengliuella salsuginis sp. nov., a moderately halophilic actinobacterium from a subterranean brine - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhu-Xiang Liu; Qi-Hui Chen; Jian-Wu He; Xiao-Long Cui; Wen-Jun Li (Extremophiles, 2010)

Modification of cambial cell wall architecture during cambium periodicity in Populus tomentosa Carr. - Hui-Min Chen; Jia-Jia Han; Ke-Ming Cui; Xin-Qiang He (Trees, 2010)

Ubiquitin ligase Smurf1 targets TRAF family proteins for ubiquitination and degradation - Shan Li; Kefeng Lu; Jian Wang; Liguo An; Guiwen Yang; Hui Chen; Yu Cui; Xiushan Yin; Ping Xie; Guichun Xing; Fuchu He; Lingqiang Zhang (Molecular and Cellular Biochemistry, 2010)

Regulatory effects of insulin-like growth factor-1 on the expression of sensory neuropeptide mRNAs in cultured dorsal root ganglion neurons with excitotoxicity induced by glutamate - Hui-Cui Gong; Xiang-Dong Yang; Zhen Liu; Zi-Ying Xing; Huai-Jing Wang; Zhen-Zhong Li (Neuroscience Bulletin, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Inhibition of lung metastasis in mice by intravascular injection of dendritic cells and natural killer cells - Hui-fang Lv; Feng Cui; Chang-hua Yu; Li-li Deng; Jing-jing Ji; Dan Lu; Yu Yang; Wen-xiu Wang; Yu-qing Xu (Biotechnology Letters, 2009)

Virgibacillus zhanjiangensis sp. nov., a marine bacterium isolated from sea water - Qing-Zhong Peng; Jun Chen; Yu-Qin Zhang; Qi-Hui Chen; De-Jiao Peng; Xiao-Long Cui; Wen-Jun Li; Yi-Guang Chen (Antonie van Leeuwenhoek, 2009)

Activation of extracellular signal-regulated kinase in the anterior cingulate cortex contributes to the induction of long-term potentiation in rats - Hong Cao; Yi-Hui Cui; Zhi-Qi Zhao; Xiao-Hua Cao; Yu-Qiu Zhang (Neuroscience Bulletin, 2009)

Soil CO2 efflux, carbon dynamics, and change in thermal conditions from contrasting clear-cut sites during natural restoration and uncut larch forests in northeastern China - Yuan-Gang Zu; Wen-Jie Wang; Hui-Mei Wang; Wei Liu; Song Cui; Takayoshi Koike (Climatic Change, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Optimization of fermentation conditions for production of xylanase by a newly isolated strain, Penicillium thiersii ZH-19 - Fengjie Cui; Yin Li; Zhiqiang Liu; Hui Zhao; Lifeng Ping; Liying Ping; Yinan Yang; Yaping Xue; Lijiao Yan (World Journal of Microbiology and Biotechnology, 2009)

Halomonas sediminis sp. nov., a new halophilic bacterium isolated from salt-lake sediment in China - Heng-Yu Huang; Yi-Guang Chen; Yong-Xia Wang; Ji-Hui Liu; Shu-Kun Tang; Qian Peng; Meng-Liang Wen; Hong Yu; Xiao-Long Cui (Extremophiles, 2008)

A novel derivative of xanomeline improved memory function in aged mice - Yi-Hui Cui; Wen Si; Liang Yin; Shu-Ming An; Jing Jin; Shi-Ning Deng; Xiao-Hua Cao (Neuroscience Bulletin, 2008)

Advanced primary peritoneal carcinoma: clinicopathological and prognostic factor analyses - Chao Zhang; Xiao-ping Li; Heng Cui; Dan-hua Shen; Li-hui Wei (Journal of Zhejiang University-SCIENCE B, 2008)

Effects and complications of placement of motility coupling post in porous polyethylene orbital implants - Hong-guang Cui; Rong-rong Hu; Hui-yan Li; Wei Han (Journal of Zhejiang University-SCIENCE B, 2008)

Molecular identification and the complete nucleotide sequence of TYLCV isolate from Shanghai of China - Zhang Yongping; Zhu Weimin; Cui Huimei; Qiu Yang; Sha Kun; Wan Yanhui; Zhu Longying; Yu Li; Hui Zhang (Virus Genes, 2008)

Expression of the Vicia faba VfPIP1 gene in Arabidopsis thaliana plants improves their drought resistance - Xiang-Huan Cui; Fu-Shun Hao; Hui Chen; Jia Chen; Xue-Chen Wang (Journal of Plant Research, 2008)

Formation of archegonium chamber is associated with nucellar-cell programmed cell death in Ginkgo biloba - Da-Hui Li; Xiong Yang; Ke-Ming Cui (Protoplasma, 2007)

Effect of basic fibroblast growth factor (bFGF) on the treatment of exposure of the orbital implants - Hong-guang Cui; Hui-yan Li (Journal of Zhejiang University-SCIENCE B, 2007)

Production of xylanase from a newly isolated Penicillium sp. ZH-30 - Yin Li; Zhiqiang Liu; Fengjie Cui; Yingying Xu; Hui Zhao (World Journal of Microbiology and Biotechnology, 2007)

Increased protein and mRNA expression of endostatin in the ischemic brain tissue of rabbits after middle cerebral artery occlusion - Heng-Li Tian; Hao Chen; Yu-Hui Cui; Tao Xu; Liang-Fu Zhou (Neuroscience Bulletin, 2007)

Apelin suppresses apoptosis of human osteoblasts - Hui Xie; Ling-Qing Yuan; Xiang-Hang Luo; Jiao Huang; Rong-Rong Cui; Li-Juan Guo; Hou-De Zhou; Xian-Ping Wu; Er-Yuan Liao (Apoptosis, 2007)

Construction and application of a promoter-trapping vector with methyl parathion hydrolase gene mpd as the reporter - Zhong-Li Cui; Xiao-Zhou Zhang; Zhong-Hui Zhang; Shun-Peng Li (Biotechnology Letters, 2004)

Characterization of protoplasts prepared from the edible fungus, Stropharia rugoso-annulata - Pei-Sheng Yan; Jia-Hui Jiang; Wen-Shan Cui (World Journal of Microbiology and Biotechnology, 2004)